Method for producing positive electrode active material, and positive electrode active material

By forming a composite oxide with a stable crystal structure in the positive electrode active material of the lithium-ion secondary battery, the problem that the lithium-ion secondary battery is difficult to take into account between large capacity and safety is solved, and the high potential and high temperature state is achieved stability and safety.

CN119487652APending Publication Date: 2025-02-18SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380050291.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries are difficult to take into account both the large capacity and the safety. Especially in the positive electrode active substances with layered rock salt-type crystal structures, it is easy to cause thermal runaway due to the collapse of the crystal structure.

Method used

By forming a cobalt-nickel hydroxide suspension, mixed with lithium compounds after multiple suction filtration, a composite oxide with a stable crystal structure is formed, the atomic ratio of nickel is controlled to be below 0.01, and elements such as magnesium and fluorine are added. to stabilize the crystal structure.

Benefits of technology

The positive electrode active material that remains stable under high potential and high temperature conditions is achieved, the crystal structure collapse is avoided, and the safety and circulation characteristics of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487652A_ABST
    Figure CN119487652A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material having high capacity and high safety. The present invention is a method for producing a positive electrode active material, comprising the steps of: forming a mixed solution in which a cobalt compound and a nickel compound are dissolved; reacting the mixed solution with an alkaline aqueous solution to obtain a suspension of cobalt-nickel hydroxide precipitate; carrying out first suction filtration on the suspension liquid by using water; in the cobalt-nickel hydroxide, the atomic ratio of nickel to the sum of the atomic ratio of cobalt and the atomic ratio of nickel is greater than 0 and 0.01 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to an object, method or manufacturing method. One embodiment of the present invention relates to a process, machine, product or composition of matter. One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device or an electronic device or a method for manufacturing the same. In particular, one embodiment of the present invention relates to a positive electrode active material for a lithium ion secondary battery and a method for manufacturing the same. Background Art

[0002] In recent years, the demand for high-output, large-capacity lithium-ion secondary batteries (also referred to as lithium-ion batteries) has increased dramatically, and they have become a necessity in modern society as a reusable energy source.

[0003] It is said that it is difficult to ensure both high capacity and safety of lithium-ion secondary batteries. For example, in a positive electrode active material having a layered rock salt type crystal structure, lithium ions migrate two-dimensionally within the crystal structure, so a large capacity is expected. However, it is believed that in a positive electrode active material having a layered rock salt type crystal structure, when too many lithium ions are released during charging, thermal runaway is easily caused due to the collapse of the crystal structure, so there are problems in terms of safety.

[0004] As positive electrode active materials having a layered rock salt type crystal structure, lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) are known. Lithium cobalt oxide has a layered rock salt type crystal structure, in which lithium ions can migrate in two dimensions between layers composed of CoO6 octahedrons, so the cycle characteristics are also excellent. However, lithium cobalt oxide has the problem of phase change with charging and discharging. For example, when a certain degree of lithium ion detachment occurs during charging, a phase change of lithium cobalt oxide from hexagonal to monoclinic occurs. Therefore, in order to utilize lithium cobalt oxide with excellent cycle characteristics, the amount of lithium ion detachment is limited. In order to solve the above problems, a structure in which an additive element is added to lithium cobalt oxide is proposed in Patent Document 1.

[0005] Lithium nickel oxide also has a layered rock salt crystal structure, so it is expected to have the same cycle characteristics as lithium cobalt oxide. In addition, nickel is cheaper than cobalt, and the energy density can be increased in proportion to the nickel content, so lithium nickel oxide is being studied as an alternative material to lithium cobalt oxide. However, lithium nickel oxide has problems with thermal stability and its safety is worse than lithium cobalt oxide, so it has not yet been put into practical use.

[0006] In addition, there are problems caused by changes in the valence of nickel. Specifically, during manufacturing, nickel is easily reduced to divalent nickel. The ionic radius of nickel ions is close to the ionic radius of lithium ions, so nickel (divalent) replaces the site where lithium ions exist. This phenomenon is called cation mixing. Due to cation mixing, the lithium content of lithium nickelate decreases, resulting in a decrease in discharge capacity. Therefore, in order to achieve high energy density and improve cycle life, Patent Document 2 proposed a LiCo obtained by a solid phase method. 0.8 Ni 0.1 Mn 0.1 O2, etc. In addition, as shown in Non-Patent Document 1, research has been conducted on LiNi 1 / 2 Co 1 / 2 02 research.

[0007] In addition, X-ray diffraction (XRD) is one of the methods for analyzing the crystal structure of the positive electrode active material. XRD data can be analyzed by using ICSD (Inorganic Crystal Structure Database) introduced in non-patent document 2. For example, ICSD can be used to refer to the lattice constant of lithium cobalt oxide described in non-patent document 3. In addition, analysis using the Rietveld method can use, for example, the analysis program RIETAN-FP (refer to non-patent document 4). In addition, as a crystal structure drawing software, VESTA (non-patent document 5) can be used.

[0008] [Prior technical literature]

[0009] [Patent Document]

[0010] [Patent Document 1] WO2020 / 026078

[0011] [Patent Document 2] Japanese Patent Application Publication No. 2006-344509

[0012] [Non-patent literature]

[0013] [Non-patent document 1] WE Counts, R. Roy, and EFOsborn, "Fluoride Model Systems: II, The Binary Systems CaF2-BeF2, MgF2-BeF2, and LiF-MgF2", Journal of the AmericanCeramic Society, 36[1]12-17(1953);

[0014] [Non-patent document 2] Belsky, A. et al., "New developments in the InorganicCrystal Structure Database (ICSD): accessibility in support of materials research and design", Acta Cryst., (2002) B58 364-369.

[0015] [Non-patent document 3] Akimoto, J.; Gotoh, Y.; Oosawa, Y. "Synthesis and structurerefinement of LiCoO2 single crystals" Journal of Solid State Chemistry (1998) 141, p. 298-302.

[0016] [Non-patent document 4] F. Izumi and K. Momma, Solid State Phenom., 130, 15-20 (2007)

[0017] [Non-patent document 5] K. Momma and F. Izumi, J. Appl. Cryst. (2011). 44, 1272-1276 Summary of the invention

[0018] Technical problem to be solved by the invention

[0019] Although positive electrode active materials can be obtained according to Patent Documents 1 and 2, there is still room for improvement in various aspects such as charge and discharge capacity, cycle characteristics, reliability, safety, and cost.

[0020] In view of the above description, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material and a method for manufacturing a positive electrode active material that is stable under a high potential state and / or a high temperature state. Furthermore, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material and a method for manufacturing a positive electrode active material whose crystal structure is not easily collapsed even after repeated charge and discharge.

[0021] Note that the description of the above-mentioned objects does not prevent the existence of other objects. Furthermore, objects other than the above-mentioned objects can be extracted from the description of the specification, drawings, and claims. One mode of the present invention does not need to achieve all of the above-mentioned objects, but achieves at least one of the objects.

[0022] Solutions to technical problems

[0023] In view of the above problems, one embodiment of the present invention is a method for manufacturing a positive electrode active material, comprising the following steps: forming a mixed solution in which a cobalt compound and a nickel compound are dissolved; reacting the mixed solution with an alkaline aqueous solution to obtain a suspension of cobalt nickel hydroxide precipitates; performing a first suction filtration on the suspension using water; and performing a second suction filtration using an organic solvent after the first suction filtration, wherein in the cobalt nickel hydroxide, the atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is less than 0.01.

[0024] Another embodiment of the present invention is a method for manufacturing a positive electrode active material, comprising the following steps: forming a mixed solution in which a cobalt compound and a nickel compound are dissolved; reacting the mixed solution with an alkaline aqueous solution to obtain a suspension of cobalt nickel hydroxide precipitates; subjecting the suspension to a first suction filtration using water; after the first suction filtration, subjecting the suspension to a second suction filtration using an organic solvent to recover the cobalt nickel hydroxide; subjecting the cobalt nickel hydroxide and a lithium compound to a first heat treatment to form a first composite oxide after mixing the cobalt nickel hydroxide and the lithium compound; subjecting the first composite oxide to a second heat treatment after mixing the first composite oxide and a compound containing an additive element, wherein in the cobalt nickel hydroxide, the atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is less than 0.01, and in the first composite oxide, the atomic number ratio of lithium relative to the atomic number ratio of cobalt is greater than 1.0 and less than 1.2.

[0025] In another embodiment of the present invention, the additional element is preferably one or two or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper, and gallium.

[0026] In another embodiment of the present invention, the temperature of the second heat treatment is preferably lower than the temperature of the first heat treatment.

[0027] In another embodiment of the present invention, the cobalt nickel hydroxide is preferably subjected to a drying step for 0.5 hours to 20 hours.

[0028] In another embodiment of the present invention, the cobalt nickel hydroxide is preferably subjected to a drying step for 12 hours to 20 hours.

[0029] Another embodiment of the present invention is a positive electrode active material, wherein the atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and less than 0.01, the atomic number ratio of lithium relative to the atomic number ratio of cobalt is greater than 1.0 and less than 1.2, and there is an area in which nickel is not confirmed in a mapping image of the positive electrode active material obtained by a surface SEM-EDX method.

[0030] Another embodiment of the present invention is a positive electrode active material, wherein the atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and less than 0.1, the atomic number ratio of lithium relative to the atomic number ratio of cobalt is greater than 1.0 and less than 1.2, and the positive electrode active material includes grains, and the size of the grains is greater than 200nm and less than 600nm.

[0031] In another embodiment of the present invention, the atomic number ratio of lithium to the atomic number ratio of cobalt is preferably 1.06 or more and 1.2 or less.

[0032] Effects of the Invention

[0033] According to one embodiment of the present invention, a positive electrode active material and a method for manufacturing a positive electrode active material that are stable under high potential and / or high temperature conditions can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material and a method for manufacturing a positive electrode active material whose crystal structure is not easily collapsed even after repeated charge and discharge can be provided.

[0034] Note that the description of these effects does not prevent the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of the above effects. Note that effects other than the above can be known and extracted from the description of the specification, drawings, claims, etc.

[0035] BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1A is a diagram showing a positive electrode active material, Figure 1B and Figure 1C It is a diagram showing the distribution of added elements.

[0037] Figure 2 This is an example of a TEM image where the crystal orientation is roughly uniform.

[0038] Figure 3A and Figure 3B It is a diagram showing a positive electrode active material.

[0039] FIG. 4A to FIG. 4C It is a diagram showing a positive electrode active material.

[0040] Figure 5 This is a diagram illustrating the crystal structure of a positive electrode active material according to one embodiment of the present invention.

[0041] FIG. 6A to FIG. 6C is the lattice constant calculated from XRD.

[0042] Figure 7 This is a flow chart showing a process for producing a positive electrode active material according to one embodiment of the present invention.

[0043] Figure 8This is a flow chart showing a process for producing a positive electrode active material according to one embodiment of the present invention.

[0044] Fig.9A and Fig. 9B It is a cross-sectional view illustrating a positive electrode active material layer.

[0045] Fig. 10A and Fig. 10B It is a diagram for explaining a solid electrolyte secondary battery.

[0046] Fig.11A This is an exploded perspective view of a coin-type secondary battery. Fig. 11B is a perspective view of a coin-type secondary battery. Fig. 11C It is a cross-sectional stereogram.

[0047] Fig. 12A It is a diagram showing an example of a cylindrical secondary battery. Fig. 12B It is a diagram showing an example of a cylindrical secondary battery. Fig. 12C It is a diagram showing an example of a plurality of cylindrical secondary batteries. Fig.12D 1 is a diagram showing an example of a power storage system including a plurality of cylindrical secondary batteries.

[0048] Fig.13A and Fig. 13B is a diagram illustrating an example of a secondary battery, Fig. 13C It is a diagram showing the internal state of a secondary battery.

[0049] FIG. 14A to FIG. 14C It is a diagram for explaining an example of a secondary battery.

[0050] Fig.15A and Fig. 15B It is a diagram showing the appearance of a secondary battery.

[0051] FIG. 16A to FIG. 16C It is a diagram for explaining a method for manufacturing a secondary battery.

[0052] 17A to 17D It is a diagram illustrating an example of a transport vehicle. Fig.17E This is a diagram illustrating an example of an artificial satellite.

[0053] Fig.18A is a diagram showing an electric bicycle, Fig.18B is a diagram showing a secondary battery of an electric bicycle, Fig.18C It is a diagram showing a small motorcycle.

[0054] FIG. 19A to FIG. 19E It is a diagram for explaining an example of an electronic device.

[0055] Fig. 20 is a SEM image of this example.

[0056] Fig.21 is the XRD measurement result of this example.

[0057] FIG. 22A to FIG. 22C It is the charge and discharge cycle test result of this embodiment.

[0058] FIG. 23A to FIG. 23C It is the charge and discharge cycle test result of this embodiment.

[0059] FIG. 24A to FIG. 24C It is the charge and discharge cycle test result of this embodiment.

[0060] FIG. 25A to FIG. 25C It is the charge and discharge cycle test result of this embodiment.

[0061] FIG. 26A to FIG. 26C This is the rate characteristic result of this embodiment.

[0062] FIG. 27A to FIG. 27C This is the rate characteristic result of this embodiment.

[0063] Fig.28 is the SEM image of the sample.

[0064] Fig.29 is the SEM image of the sample.

[0065] FIG. 30A to FIG. 30E These are the SEM images and mapping images of the samples.

[0066] Fig.31 It is a figure which shows the energy spectrum obtained by EDX.

[0067] Fig.32 It is a figure which shows the energy spectrum obtained by EDX.

[0068] Fig.33 It is a figure which shows the energy spectrum obtained by EDX.

[0069] Fig.34 It is a figure which shows the energy spectrum obtained by EDX.

[0070] Fig.35 It is a figure which shows the energy spectrum obtained by EDX.

[0071] Fig.36 It is a figure which shows the energy spectrum obtained by EDX.

[0072] FIG. 37A to FIG. 37E These are the SEM images and mapping images of the samples.

[0073] Fig.38 It is a figure which shows the energy spectrum obtained by EDX.

[0074] Fig.39It is a figure which shows the energy spectrum obtained by EDX.

[0075] Fig.40 It is a figure which shows the energy spectrum obtained by EDX.

[0076] Fig.41 It is a figure which shows the energy spectrum obtained by EDX.

[0077] Fig.42 It is a figure which shows the energy spectrum obtained by EDX.

[0078] Fig.43 It is a figure which shows the energy spectrum obtained by EDX.

[0079] Fig.44 is a graph showing the XRD measurement results of the samples.

[0080] Fig.45A and Fig.45B is a graph showing the grain size of the sample.

[0081] Fig.46 is a graph showing the particle size distribution measurement results of the samples.

[0082] FIG. 47A to FIG. 47C It is a graph showing the change in discharge capacity of the samples at 25°C.

[0083] FIG. 48A to FIG. 48C This is a graph showing changes in discharge capacity of samples at 45°C.

[0084] FIG. 49A to FIG. 49C It is a graph showing the change in the discharge capacity retention rate of the samples at 25°C.

[0085] FIG. 50A to FIG. 50C It is a graph showing the change in the discharge capacity retention rate of the samples at 45°C.

[0086] FIG. 51A to FIG. 51C It is a graph showing the change in rate characteristics of samples at 25°C.

[0087] FIG. 52A to FIG. 52C It is a graph showing the change in rate characteristics of samples at 25°C.

[0088] Fig.53 is the SEM image of the sample.

[0089] Fig.54 is the SEM image of the sample.

[0090] Fig.55 is a graph showing the XRD measurement results of the samples.

[0091] Fig.56 is a graph showing the grain size of the sample.

[0092] Fig.57 is a graph showing the particle size distribution measurement results of the samples.

[0093] FIG. 58A to FIG. 58C It is a graph showing the change in discharge capacity of the samples at 25°C.

[0094] FIG. 59A to FIG. 59C This is a graph showing changes in discharge capacity of samples at 45°C.

[0095] FIG. 60A to FIG. 60C It is a graph showing the change in the discharge capacity retention rate of the samples at 25°C.

[0096] Figures 61A to 61C It is a graph showing the change in the discharge capacity retention rate of the samples at 45°C.

[0097] Figures 62A to 62C It is a graph showing the change in rate characteristics of samples at 25°C.

[0098] Figures 63A to 63C It is a graph showing the change in rate characteristics of samples at 25°C.

[0099] Fig.64 It is a graph showing the XRD measurement results of the sample during charging.

[0100] Modes for Carrying Out the Invention

[0101] Hereinafter, the embodiments of the present invention will be described using the accompanying drawings and the like. Note that the present invention is not limited to the following description, and a person skilled in the art can easily understand that the mode and details thereof can be transformed into various forms. In addition, the present invention should not be interpreted as being limited to the contents described in the embodiments shown below.

[0102] In this specification, etc., the positive electrode active material is sometimes recorded as a composite oxide, a positive electrode material, a positive electrode material for a lithium ion secondary battery, etc. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composite.

[0103] In this specification, etc., the space group is represented by the short notation of the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and crystal orientation. In crystallography, the space group, crystal plane and crystal orientation are represented by a superscript bar to the number. However, in this specification, etc., due to the symbol limitation in the patent application, - (minus sign) is sometimes attached to the number to represent the space group, crystal plane and crystal orientation, instead of attaching a superscript bar to the number. In addition, "[]" is used to represent the individual orientation of the orientation in the crystal, "<>" is used to represent the collective orientation of all equivalent orientations, "()" is used to represent the individual face of the crystal face, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal system represented by the space group R-3m is represented by a compound hexagonal lattice of the hexagonal lattice. In this specification, etc., unless otherwise specified, the space group R-3m is also represented by a compound hexagonal lattice. Sometimes, (hkil) is used as the Miller index in addition to (hkl). Here, i is -(h+k).

[0104] The space group of a lithium ion secondary battery is identified by XRD (X-ray Diffraction), electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., belonging to a certain space group or a space group means being identified as a certain space group.

[0105] In addition, the structure in which three layers of anions are stacked and deviated from each other like ABCABC is called a cubic closest packing structure. Therefore, the anions may not be strictly a cubic lattice. At the same time, in fact, the crystals all have defects, so the analysis results may not be based on theory. For example, in the FFT (Fast Fourier Transform) diagram of an electron diffraction pattern or a TEM (Transmission Electron Microscope: Transmission Electron Microscope) image, spots may also appear at a position slightly different from the theoretical position. For example, when the difference in orientation from the theoretical position is less than 5° or less than 2.5°, it can be said that there is a cubic closest packing structure.

[0106] In this specification, etc., the layered rock salt type crystal structure refers to a crystal structure having a rock salt type ion arrangement in which cations and anions are alternately arranged, and the transition metal M and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by deformation of the lattice of the rock salt type crystal.

[0107] In addition, the rock salt-type crystal structure has a cubic crystal structure such as the space group Fm-3m, in which cations and anions are arranged alternately. In addition, it may also include vacancies of cations or anions.

[0108] Furthermore, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium ions that can be inserted and removed in the positive electrode active material are removed. For example, the theoretical capacity of LiCoO2 per unit weight of the positive electrode active material is 274 mAh / g, that of LiNiO2 per unit weight of the positive electrode active material is 274 mAh / g, and the theoretical capacity of LiMn2O4 per unit weight of the positive electrode active material is 148 mAh / g.

[0109] In addition, for x in the compositional formula, for example, Li x x in MO2 represents the amount of lithium remaining in the positive electrode active material that can be inserted and removed. Here, M is a transition metal, typically cobalt, but may include multiple transition metals. In the positive electrode active material of the secondary battery, x = (theoretical capacity - charge capacity) / theoretical capacity. For example, when the secondary battery using LiMO2 in the positive electrode active material is charged to 219.2 mAh / g, it can be said that the positive electrode active material is Li 0.2 MO2 or x = 0.2. A smaller x in Li x MO2, for example, means a case where 0.1 < x ≤ 0.24. In addition, sometimes the amount of lithium detached from the positive electrode active material relative to the theoretical capacity is defined as the depth of charge. In this specification and the like, the depth of charge is equal to 1 - x.

[0110] The charge capacity and / or discharge capacity used to calculate x in Li x MO2 is preferably measured under conditions where there is no influence of short circuit and / or decomposition of the electrolyte, or the influence of short circuit and / or decomposition of the electrolyte is small. For example, data of a secondary battery in which a sharp change in capacity that may be a short circuit occurs cannot be used for the calculation of x.

[0111] When the appropriately synthesized lithium cobaltate before being used for the positive electrode approximately satisfies the stoichiometric ratio, this lithium cobaltate is LiCoO2 and x = 1. In addition, the lithium cobaltate in the secondary battery at the end of discharge can also be said to be LiCoO2 and x = 1. Here, "end of discharge" means, for example, a state where the current voltage reaches 3.0 V or 2.5 V or less at a current of 100 mA / g or less per unit weight of the positive electrode active material.

[0112] In this specification and the like, the distribution of a certain element sometimes refers to a region where the element is continuously detected within a range where it is not noise by a certain continuous analysis method.

[0113] When describing the characteristics of the positive electrode active material in this specification, etc., it is not necessary that all positive electrode active materials in the lithium ion secondary battery have the characteristics. For example, when describing the characteristics of the film of the positive electrode active material, for example, as long as more than 50%, preferably more than 70%, and more preferably more than 90% of the positive electrode active materials in three or more randomly selected positive electrode active materials have the characteristics of the film (specifically, the surface formed by the film is more than 50%, preferably more than 70%, and more preferably more than 90% of the active material), it can be said that it has the effect of fully improving the characteristics of the positive electrode active material and the lithium ion secondary battery containing the positive electrode active material.

[0114] In addition to causing defects in the charging and / or discharging operations of the lithium-ion secondary battery, the short circuit of the lithium-ion secondary battery can also cause thermal runaway, heating and fire. There are internal short circuits and external short circuits as short circuits. In this specification, etc., the internal short circuit of the lithium-ion secondary battery refers to the phenomenon that the positive and negative electrodes are in contact inside the battery. In addition, the external short circuit of the lithium-ion secondary battery is assumed to be used incorrectly, and refers to the phenomenon that the positive and negative electrodes are in contact outside the battery.

[0115] Note that, unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) contained in the lithium-ion secondary battery in the state before degradation are described. In addition, the following situation is not called degradation: the discharge capacity decreases due to aging treatment and burn-in treatment in the stage of manufacturing the lithium-ion secondary battery. For example, the following situation can be called the state before degradation: the discharge capacity is more than 97% of the rated capacity of the lithium-ion secondary battery composed of a single cell or a battery pack. When using lithium-ion secondary batteries for portable devices, the rated capacity is based on JIS C 8711:2019. When using lithium-ion secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, and is based on various JIS, IEC standards, etc. for electric vehicle propulsion and industrial use.

[0116] In this specification, etc., lithium ion secondary battery is sometimes referred to as lithium ion battery, which refers to a battery using lithium ion as a carrier ion, but the carrier ion of the present invention is not limited to lithium ion. For example, alkali metal ions or alkaline earth metal ions can be used as the carrier ion of the present invention, specifically sodium ions can be used. At this time, lithium ions can be referred to as sodium ions to understand the present invention. In addition, when there is no restriction on the carrier ion, it is sometimes referred to as a secondary battery.

[0117] In this specification, etc., active materials are sometimes referred to as active material particles, but their shapes are not limited to particles and can be in various shapes. For example, in a cross section, the shape of the active material (active material particle) can be an ellipse, a square, a trapezoid, a triangle, a quadrilateral with rounded corners, or an asymmetric shape in addition to a circle.

[0118] In this specification, when the surface concavo-convex information is quantified based on the measurement data on a cross section of the active material, it can be said that the surface smoothness of the active material is a state with a surface roughness of at least 10 nm or less. In this specification, a cross section is, for example, a cross section obtained when observing using a STEM (Scanning Transmission Electron Microscope) image.

[0119] In this specification, "A and / or B" may be described, which is an example of description including "only A", "only B" or "A and B".

[0120] In this specification, etc., secondary particles refer to particles formed by aggregation of primary particles. In addition, in this specification, etc., single particles refer to single crystal particles in which no grain boundary is apparent.

[0121] (Implementation Method 1)

[0122] In this embodiment, a positive electrode active material 100 according to one embodiment of the present invention will be described with reference to FIGS. 1 to 6 .

[0123] Figure 1A FIG. 1 is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. Figure 1A As shown in FIG. 1 , the positive electrode active material 100 includes a surface layer portion 100 a and an inner portion 100 c. Figure 1A In the figures, the boundary between the surface layer portion 100a and the inner portion 100c is shown by a dotted line.

[0124] <Single Particle>

[0125] The positive electrode active material 100 preferably has high crystallinity. In addition, the positive electrode active material 100 is preferably a single crystal (also referred to as a single particle) rather than a secondary particle. When the positive electrode active material 100 of one embodiment of the present invention includes a single particle, it can be expected that cracks are suppressed even if the volume of the positive electrode active material changes due to charge and discharge.

[0126] <Surface layer>

[0127] In this specification, the surface layer 100a of the positive electrode active material 100 refers to, for example, a region within 200 nm from the surface to the inside, preferably within 100 nm, more preferably within 50 nm, and further preferably within 20 nm. The surface generated by the crack can also be referred to as the surface. The surface layer is synonymous with the vicinity of the surface, the shell, or the vicinity of the surface.

[0128] <Surface>

[0129] The positive electrode active material 100 is a composite oxide in which lithium ions can be inserted and removed, and therefore does not contain carbonates, hydroxyls, etc. chemically adsorbed after manufacturing. In addition, it does not contain electrolytes, binders, conductive materials, or compounds derived from them that are attached to the positive electrode active material 100. Therefore, the surface of the positive electrode active material 100 refers to the surface of the composite oxide in which lithium ions can be inserted and removed, and materials that cannot be called the above-mentioned composite oxides do not constitute the surface of the positive electrode active material 100.

[0130] <Inside>

[0131] In addition, a region deeper than the surface layer portion 100a in the positive electrode active material 100 is referred to as an inner portion 100c. The inner portion 100c is synonymous with an inner region or a core.

[0132] <Contains elements>

[0133] In order to maintain charge neutrality even when lithium ions are inserted and removed, the positive electrode active material 100 needs to contain a transition metal that can undergo oxidation and reduction. The positive electrode active material 100 of one embodiment of the present invention preferably uses cobalt as the transition metal M that undergoes oxidation and reduction reactions. There may also be multiple transition metals M used, in which case cobalt is preferably used as the main component of the transition metal M. Note that the main component of the transition metal M in this specification, etc. refers to the component with the highest atomic number ratio among the multiple transition metals M contained in the positive electrode active material. In addition, the positive electrode active material 100 preferably uses nickel in addition to cobalt. A composite oxide containing cobalt and nickel as transition metals is sometimes called lithium cobalt nickel oxide, and the composition formula can be expressed as LiCo 1- y Ni y O2.LiCo 1-y Ni y The crystal structure of O2 belongs to the space group R-3m.

[0134] In the positive electrode active material 100, LiCo 1-y Ni y y in O2 is preferably greater than 0 and equal to or less than 0.1, more preferably greater than 0 and equal to or less than 0.05, and still more preferably greater than 0 and equal to or less than 0.01.

[0135] For example, when expressing the ratio of the number of transition metal atoms in the positive electrode active material 100, “LiCo 1-y Ni y "y in O2 is 0.01", which means Co:Ni=99:1. Therefore, in the positive electrode active material 100, it is preferred that Co:Ni=99:1 and its vicinity, Co:Ni=99.5:0.5 and its vicinity, or Co:Ni=99.9:0.1 and its vicinity are satisfied. Note that the above-mentioned vicinity for the ratio of the number of atoms includes 0.9 times or more and 1.1 times or less of its value.

[0136] When the positive electrode active material 100 of one embodiment of the present invention contains nickel, the deviation of the layered structure is suppressed or the crystal structure becomes stable, so it can be considered that the secondary battery using the above-mentioned positive electrode active material is not easy to catch fire and the degradation after charging and discharging is suppressed. In order to obtain the above-mentioned positive electrode active material 100, it is preferably used by a coprecipitation method, which is also described in the following embodiments, etc.

[0137] In the positive electrode active material 100 of one embodiment of the present invention, nickel is preferably dissolved in the positive electrode active material 100. Therefore, for example, when performing line analysis of STEM-EDX (Scanning Transmission Electron Microscope-Energy Dispersive X-ray spectroscopy), nickel is preferably located inside 100c of the positive electrode active material 100. Specifically, the depth at which the detected amount of nickel increases is preferably located at a position deeper than the depth at which the detected amount of cobalt increases.

[0138] As described later, in the positive electrode active material 100 of one embodiment of the present invention, lithium is mixed in such a manner that the atomic ratio is greater than 1, so there is no restriction on the atomic ratio of lithium. That is, in the positive electrode active material 100, when cobalt and / or nickel are used as M, the composition is not strictly limited to Li:M:O=1:1:2.

[0139] As described later, the positive electrode active material 100 according to one embodiment of the present invention preferably has a unique crystal structure during charge.

[0140] <Add Elements>

[0141] More preferably, the positive electrode active material 100 of one embodiment of the present invention contains an additive element. In other words, the positive electrode active material 100 preferably contains lithium, cobalt, nickel, oxygen and the additive element. In other words, the additive element is preferably added to lithium cobalt nickel oxide (LiCo 1-y Ni yAs the additive element, one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium can be used.

[0142] If the amount of the additive element is too small, the effect of chemically stabilizing the positive electrode active material 100 cannot be fully exerted, but if the amount is too large, it may have a negative impact on the discharge capacity, etc. Therefore, for example, when the positive electrode active material 100 containing the additive element A is represented as LiCo 1-y-z Ni y O2A z When z is greater than 0 and less than 0.3, z is preferably greater than 0 and less than 0.1, and more preferably greater than 0 and less than 0.05.

[0143] The added element is preferably dissolved in the positive electrode active material 100. Alternatively, the added element is preferably substituted at any one of the sites of the transition metal, oxygen, and lithium constituting the positive electrode active material 100. The added element that is judged to exist in this state when the positive electrode active material 100 is subjected to STEM-EDX line analysis is located on the inner side of the positive electrode active material 100. In other words, the depth at which the detected amount of the added element increases is preferably located at a position deeper than the depth at which the detected amount of the transition metal M, etc. increases.

[0144] Regarding the distribution of magnesium as an added element, it is preferred that the detected amount in the surface portion 100a is larger than the detected amount in the inner portion 100c when the positive electrode active material 100 is subjected to STEM-EDX line analysis. In addition, it is preferred that a detected amount peak is present in an area closer to the surface in the surface portion 100a. In this specification, etc., the detected amount of the STEM-EDX line analysis includes the result output as a count ratio or the result output as an atomic number ratio, and the peak of the detected amount can also be referred to as the position indicating the highest atomic number ratio.

[0145] Regarding the distribution of fluorine of the added element, it is preferred that the detected amount in the surface portion 100a is larger than the detected amount in the internal 100c when the positive electrode active material 100 is subjected to STEM-EDX line analysis. In addition, it is preferred that a fluorine detection amount peak is present in the surface portion 100a in an area closer to the surface. The distribution of fluorine may also overlap with the distribution of magnesium. The distribution and overlap include situations where the peak positions of the detected amounts coincide with each other. In addition, the distribution of fluorine may also not overlap with the distribution of magnesium.

[0146] Regarding the distribution of calcium as an added element, it is preferred that the detected amount in the surface portion 100a is larger than the detected amount in the inner portion 100c when the positive electrode active material 100 is subjected to STEM-EDX line analysis. It is preferred that a detected amount peak is present in a region closer to the surface in the surface portion 100a. The distribution of calcium may also overlap with the distribution of magnesium. In addition, the distribution of calcium may not overlap with the distribution of magnesium.

[0147] Regarding the distribution of aluminum as an added element, it is preferred that, when the positive electrode active material 100 is subjected to STEM-EDX line analysis, the detected amount peak is located inside compared to magnesium. The reason why aluminum is distributed inside compared to magnesium is that aluminum diffuses more easily than magnesium. On the other hand, it is speculated that since aluminum exists more stably in a region that is not a region where magnesium or the like is solid-dissolved at a high concentration than in a region where magnesium or the like is solid-dissolved at a high concentration, the detected amount of aluminum in the region closest to the surface is small.

[0148] In addition, the distribution of aluminum and the distribution of magnesium may overlap, or the distribution of aluminum and the distribution of magnesium may hardly overlap. The detection peak of aluminum may exist in the surface portion 100a or in a position deeper than the surface portion 100a. For example, it is preferred to have a detection peak in a region of more than 5nm and less than 30nm from the surface to the inside.

[0149] As described above, the additional element may not have the same concentration gradient or distribution in all regions of the surface layer portion 100 a of the positive electrode active material 100 .

[0150] As described later, the above-mentioned additive elements can further stabilize the crystal structure of the positive electrode active material 100 during charging. Of course, as long as the crystal structure of the positive electrode active material 100 can be further stabilized during charging, the additive elements may not be included. In other words, magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper, and gallium are not necessarily included as additive elements.

[0151] In the positive electrode active material 100 of one embodiment of the present invention, nickel can also be used as an additive element. Nickel has the above-mentioned effects of suppressing the deviation of the layered structure or stabilizing the crystal structure, and when this effect occurs, nickel can be located both in the interior 100c and in the surface portion 100a. In addition, the nickel concentration may be different between the interior 100c and the surface portion 100a. When the nickel concentration of the interior 100c is higher than that of the surface portion 100a, the above-mentioned effect is efficiently produced in the interior 100c that occupies most of the positive electrode active material 100, so it is preferred. In addition, when the nickel concentration of the surface portion 100a is higher than that of the interior 100c, the above-mentioned effect is efficiently produced in the surface portion 100a where the degradation of the positive electrode active material 100 begins, so it is preferred. As one of the methods for increasing the nickel concentration of the surface portion 100a, there is a method of adding nickel as an additive element after forming a composite oxide.

[0152] Regarding the added element other than nickel, the atomic number ratio of the added element relative to the atomic number ratio of the transition metal contained in the positive electrode active material 100 (when there are multiple transition metals, the sum of the atomic number ratios) is preferably less than 30at%, more preferably less than 10at%, and further preferably less than 5at%. As described above, the added element is preferably located in the surface portion 100a, so it can be said that as long as the atomic number ratio of the added element other than nickel is satisfied at least in the surface portion 100a.

[0153] The atomic number ratio of the added element can be identified by, for example, XPS (Energy Dispersive X-ray Spectroscopy) line analysis or EPMA (Electron Probe Microanalysis) in addition to EDX line analysis.

[0154] As described above, by including the added element, the crystal structure of the positive electrode active material is stabilized, especially when charged at a high voltage. In addition, it can be considered that the crystal structure can also be stabilized when exposed to a high temperature environment, for example, when charged at a higher voltage under a 45°C environment. A secondary battery using this positive electrode active material is not prone to ignition, so it is preferred.

[0155] <Crystalline surface>

[0156] Figure 1A The positive electrode active material 100 shown is a composite oxide having a layered rock salt type crystal structure in the interior 100c, wherein the surface portion 100a and the interior 100c both have faces parallel to the (001) plane. In this specification, etc., the (001) plane and the (003) plane are sometimes collectively referred to as the (001) plane. Note that in this specification, etc., the (001) plane is sometimes referred to as the C plane, the basal plane, etc. In addition, it can be said that the diffusion path of lithium ions in the positive electrode active material 100 exists along the basal plane. In this specification, etc., sometimes the plane where the diffusion path of lithium ions is exposed, that is, the plane where lithium is inserted and removed, specifically the plane other than the (001) plane is referred to as the edge plane.

[0157] <Differences in distribution of added elements between crystal planes>

[0158] It has been explained that the distribution of the added elements does not necessarily need to be the same in all regions of the surface layer portion 100a of the positive electrode active material 100. Figure 1A The surface of the region AB is included in the surface having a surface other than the (001) surface. Figure 1A The surface of the region to which the CD is attached includes a surface having a (001) plane.

[0159] In the positive electrode active material 100, the same additive element may be present but the distribution of the additive element may be different between the (001) plane and the plane parallel to the plane and between the plane other than the (001) plane and the plane parallel to the plane. Figure 1B As shown in FIG. 1 , in the surface layer 100a and the inner portion 100c of the region where AB is attached, the concentration of the added element increases toward the surface. Figure 1C As shown, in the surface part 100a and the inner part 100c of the area with CD, sometimes there is a distribution in which the same additive element is present but the concentration increases toward the boundary between the surface part 100a and the inner part 100c. In the layered rock salt type crystal structure, sometimes the planes to which each additive element is easily added are different. For example, magnesium is easily added to the plane other than the (001) plane.

[0160] In the case where the added elements are different from each other, sometimes there is Figure 1B The added element A of the distribution shown and the Figure 1C The distribution of the additive element B shown is shown. Although not shown, there may be an additive element whose detection amount is below the detection limit on the surface with the (001) plane of CD, the surface layer portion 100a having the plane, and the inner portion 100c.

[0161] In addition, in the positive electrode active material 100, preferably Figure 1C Compared with the surface of the (001) plane with CD shown in the figure and the surface layer part 100a having the same plane, Figure 1B The concentration of the added element is high in the surface of the plane other than the (001) plane to which AB is attached and the surface layer portion 100a having the plane. Magnesium can be cited as an example of the added element in this case.

[0162] In the layered rock salt type crystal structure belonging to R-3m, cations are arranged parallel to the (001) plane. This crystal structure can be said to be a structure in which MO2 layers (M is cobalt and / or nickel) and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion path of lithium ions also exists on the surface parallel to the (001) plane. In addition, the main diffusion path of lithium ions during charging and discharging is not exposed on the (001) plane. Because the MO2 layer is relatively stable, the surface having the (001) plane and the surface layer including the surface are very stable.

[0163] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) surface. Therefore, the surface having the surface other than the (001) surface and the surface layer portion 100a having the surface are important areas for maintaining the diffusion path of lithium ions, and tend to be unstable because lithium ions are initially separated. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is important to strengthen the surface layer portion 100a having the surface other than the (001) surface.

[0164] For example, it is preferred to utilize the diffusion path of lithium ions to add the additive element to the surface portion 100a having a surface other than the (001) surface. In order to efficiently add the additive element to the surface portion 100a having a surface other than the (001) surface, it is preferred to add the additive element after forming the composite oxide. As the above-mentioned additive element, magnesium substituted at the lithium site is preferably used.

[0165] In addition, in the following embodiments, since the positive electrode active material 100 is obtained by a coprecipitation method, an additive element may be added to a hydroxide serving as a precursor of a composite oxide. This is because a diffusion path for lithium ions is sometimes formed in the hydroxide. Note that in this specification, etc., a hydroxide at a stage before the composite oxide is generated is referred to as a precursor.

[0166] In order to maintain the overall crystal structure of the positive electrode active material 100 , the additive element is preferably located in the surface portion 100 a where degradation is likely to begin. Therefore, regardless of the timing of adding the additive element, the additive element may be located in the surface portion 100 a in a manner that stabilizes the crystal structure.

[0167] <roughly consistent>

[0168] Due to the concentration gradient of the added element, for example, the inner part 100c may have a layered rock salt type crystal structure, and the surface and the surface layer 100a may have a rock salt type crystal structure or a crystal structure having characteristics of both the rock salt type and the layered rock salt type. In this case, it is preferred that the crystal structure changes continuously from the inner part 100c to the surface layer 100a. Alternatively, the crystal orientations of the surface layer 100a and the inner part 100c are preferably substantially consistent.

[0169] Figure 2 An example of a TEM image showing that the orientation of the layered rock salt type crystals LRS in the inner part 100c and the rock salt type crystals RS in the surface part 100a are roughly consistent. The contrast derived from the crystal plane can be obtained from the high-resolution TEM image, etc. Due to the diffraction and interference of the electron beam, for example, when the electron beam is incident on the c-axis perpendicular to the layered rock salt type composite hexagonal lattice, the repetition of bright bands (bright band lines) and dark bands (dark band lines) of contrast derived from the (0003) plane can be obtained. Therefore, the repetition of bright lines and dark lines is observed in the TEM image, and in the bright lines (for example, Figure 2 L RS and L LRS ) is less than 5° or less than 2.5°, it can be judged that the crystal planes are roughly consistent, that is, the crystal orientations are roughly consistent. Similarly, when the angle formed by the dark lines is less than 5° or less than 2.5°, it can also be judged that the crystal orientations are roughly consistent.

[0170] In addition to TEM images, images reflecting the crystal structure can also be obtained using HAADF-STEM images, ABF-STEM images, and the like.

[0171] In the HAADF-STEM image, a contrast ratio proportional to the atomic number is obtained, and the larger the atomic number of the element, the brighter it is observed. For example, in the case of layered rock salt type lithium cobalt nickel oxide belonging to the space group R-3m, because the atomic numbers of cobalt (atomic number 27) and nickel (atomic number 28) are large, the electron beam is strongly scattered at the positions of cobalt atoms and nickel atoms, and the arrangement of cobalt atoms and nickel atoms is observed as an arrangement of bright lines or points with high brightness. Therefore, when the lithium cobalt nickel oxide having a layered rock salt type crystal structure is observed along the direction perpendicular to the c-axis, the arrangement of cobalt atoms and nickel atoms is observed as an arrangement of bright lines or points with high brightness in the direction perpendicular to the c-axis, and the arrangement of lithium atoms and oxygen atoms is observed as dark lines or areas with low brightness. When fluorine (atomic number 9) and magnesium (atomic number 12) are included as additive elements of lithium cobalt nickel oxide, the arrangement of fluorine atoms and magnesium atoms is also observed as dark lines or areas with low brightness.

[0172] Therefore, in the HAADF-STEM image, when the repetition of bright and dark lines is observed in two regions with different crystal structures, when the angle formed by the bright lines is less than 5 or less than 2.5, it can be judged that the atomic arrangement is roughly consistent, that is, the crystal orientation is roughly consistent. Similarly, when the angle formed by the dark lines is less than 5 or less than 2.5, it can also be judged that the crystal orientation is roughly consistent.

[0173] In addition, in ABF-STEM, the smaller the atomic number, the brighter the element is observed, but the contrast corresponding to the atomic number can be obtained in the same way as HAADF-STEM, so the orientation of the crystal can be determined in the same way as the HAADF-STEM image.

[0174] In addition, it can be determined by electron diffraction, TEM images, cross-sectional STEM images, and the like that the surface layer portion 100 a and the like have characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure.

[0175] In cross-sectional STEM images, when the layered rock salt type crystal structure is observed in a direction perpendicular to the c-axis, layers observed with high brightness and layers observed with low brightness are observed alternately. There is no difference in the site of the cation of the rock salt type, so the above characteristics cannot be confirmed. When a crystal structure having characteristics of both the rock salt type and the layered rock salt type is adopted, when observed from a specific crystal orientation, layers observed with high brightness and layers observed with low brightness are observed alternately in cross-sectional STEM images, and a metal having an atomic number greater than lithium exists in a layer with lower brightness, that is, a part of the lithium layer.

[0176] The anions of the layered rock salt type crystal and the rock salt type crystal respectively form a cubic closest packing structure (face-centered cubic lattice structure). Thus, when the layered rock salt type crystal contacts the rock salt type crystal, there is a crystal face with the same orientation of the cubic closest packing structure formed by the anions. In this specification, sometimes in the layered rock salt type crystal and the rock salt type crystal, the state of the same orientation of the cubic closest packing structure formed by the anions refers to the state of roughly consistent crystal orientation. In addition, the state of having roughly consistent three-dimensional structural similarity or the same orientation in crystallography is called topological derivative (topotaxy).

[0177] <Smooth Surface>

[0178] Figure 1A The surface of the positive electrode active material 100 shown is preferably smooth and has few irregularities. A smooth surface means that there are few irregularities, and the positive electrode active material 100 is curved as a whole and has curved corners. In addition, a state in which there are few foreign matters attached to the surface is also called "smooth". It is believed that foreign matters are the cause of irregularities and are preferably not attached to the surface.

[0179] <Secondary particles with large grain size>

[0180] The positive electrode active material 100 according to one embodiment of the present invention may be a secondary particle as long as the crystal particle size is large. Figure 3A and Figure 3B The cross-sectional view of the positive electrode active material 100 is shown, which is a secondary particle and includes primary particles having a large crystal size. Figure 3A and Figure 3B The surface layer 10a may have a grain boundary 101. The grain boundary 101 is called a crystal boundary. Figure 3A As shown in FIG. 1 , it does not exist around the grain boundary 101, and can also be Figure 3B As shown, it exists around or along the grain boundary 101 .

[0181] In the positive electrode active material 100, a large grain size means that the grain size calculated from the half width of the diffraction pattern of XRD is large, which is correlated with the large size of the primary particles. When calculating the grain size from the half width, for example, the Scherrer formula can be used. As long as the size of the primary particle is large, it does not need to be a secondary particle. That is, the positive electrode active material 100 of one embodiment of the present invention may include secondary particles with a large grain size, and there are no grain boundaries that may be generated between the primary particles in such a positive electrode active material 100, or there are very few grain boundaries that may be generated between the primary particles. In addition, cracks are sometimes caused by grain boundaries, but in the positive electrode active material 100 of one embodiment of the present invention, it can be expected that the occurrence of cracks can be suppressed even if the volume of the positive electrode active material 100 changes due to charging and discharging. That is, secondary particles with a large grain size can produce the same effect as the above-mentioned single particles.

[0182] For example, in the positive electrode active material 100 , the lower limit of the crystallite size calculated from the half width of the XRD diffraction pattern is preferably 200 nm or more, more preferably 210 nm or more, and even more preferably 220 nm or more.

[0183] Note that in order to increase the grain size, it is sufficient to add excess lithium and heat it. However, excess lithium may cause gelation of the binder when manufacturing electrodes such as the positive electrode. It is preferred to set the upper limit of the grain size to avoid this disadvantage. For example, by setting the grain size calculated from the diffraction pattern of XRD to less than 800nm, preferably to less than 750nm, the above disadvantage can be avoided. This upper limit value can be arbitrarily combined with the lower limit of the above grain size.

[0184] In addition, the XRD diffraction pattern when calculating the half width is preferably obtained in the state of only the positive electrode active material, but it can also be obtained in the state of the positive electrode including the current collector, the binder and the conductive material in addition to the positive electrode active material. However, in the state of the positive electrode, the positive electrode active material may be oriented by the influence of the pressurization in the manufacturing process, etc. When the orientation degree is high, it is possible that the grain size cannot be accurately calculated, so it is more preferable to obtain the XRD diffraction pattern by the following method: taking out the positive electrode active material layer from the positive electrode, removing the binder in the positive electrode active material layer to some extent by using a solvent, etc., and filling it into the sample holder, etc.

[0185] <xrd>

[0186] The measurement conditions of XRD when calculating the grain size are described. For example, the diffraction pattern obtained under the following conditions and ICSD coll.code.172909 can be used as the literature value of lithium cobalt oxide: Bruker D8ADVANCE is used as the XRD device, CuKα source is used as the X-ray source, 2θ is greater than 15° and less than 90°, increment is set to 0.01°, and LYNX EYE is used as the detector. As a crystal structure analysis software, DIFFRAC.TOPAS ver.3 can be used for analysis. It is preferred to use the value of Cry Size Lorentzian calculated by this method as the grain size.

[0187] There are no particular limitations on the apparatus and conditions for XRD measurement as long as appropriate adjustment and calibration are performed. As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) can be used.

[0188] When the sample to be measured is a powder of a positive electrode active material, the sample is mounted by placing it in a glass sample holder, or by sprinkling the sample on a silicon non-reflective plate coated with grease, etc. When the sample to be measured is a positive electrode, the positive electrode active material layer in the positive electrode is mounted according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0189] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD diffraction pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to remove the peak passing through the CuKα2 ray and extract only the peak passing through the CuKα1 ray. In addition, the software can also be used to perform background removal, etc.

[0190] <Grain Boundary>

[0191] Figure 3A and Figure 3B The grain boundary 101 shown is equivalent to, for example: the interface between the primary particles bonded together; the surface where the crystal orientation changes inside the positive electrode active material 100, that is, the surface where the bright lines and dark lines in the STEM image are repeatedly discontinuous; the surface containing a large number of crystal defects; the surface with disordered crystal structure, etc. In addition, crystal defects include defects that can be observed using cross-sectional TEM (transmission electron microscope), cross-sectional STEM images, etc., that is, structures and voids where other elements enter the lattice. In addition, the vicinity of the grain boundary 101 refers to a region where there are primary particles within 10nm at least from the grain boundary 101.

[0192] The crystal structure of the surface layer portion 100 a , the grain boundary 101 , and the like can be analyzed by performing electron diffraction or the like on a cross section of the positive electrode active material 100 .

[0193] The grain boundary 101 is one of the surface defects. Therefore, the grain boundary 101 tends to be unstable like the surface layer 100a and the crystal structure therein tends to change easily. Therefore, the concentration of the added element in the grain boundary 101 and its vicinity is high, and as described later, the change of the crystal structure can be more effectively suppressed. Therefore, the added element is preferably located in the Figure 3B The surface layer portion 100a is shown.

[0194] When the concentration of the added element at the grain boundary 101 and its vicinity is high, even if cracks are generated due to the grain boundary 101 in the positive electrode active material 100 of one embodiment of the present invention, the concentration of the added element is high at the surface newly generated due to the cracks or its vicinity. Therefore, the crystal structure can be stabilized by the added element in the surface portion generated due to the cracks.

[0195] For example, the concentration of the added element in the grain boundary 101 and its vicinity of the positive electrode active material 100 is typically preferably higher in magnesium concentration than in other regions of the interior 100c. Also, the concentration of nickel in the grain boundary 101 and its vicinity is preferably higher than in other regions of the interior 100c.

[0196] When fluorine is used as an additive element, the fluorine concentration in the grain boundary 101 and its vicinity is preferably higher than that in other regions of the inner portion 100 c. This can also improve the corrosion resistance of the positive electrode active material to hydrofluoric acid after cracks are generated.

[0197] <Lamination>

[0198] The positive electrode active material 100 may include a coating on at least a portion of the surface. Figure 4A Show Figure 1A The positive electrode active material 100 shown in the figure is provided with a coating 104. Figure 4B and Figure 4C Show respectively Figure 3A and Figure 3B The positive electrode active material 100 shown is an example in which a coating film 104 is provided.

[0199] For example, the coating 104 is preferably a film formed by the deposition of decomposition products of the electrolyte as the charge and discharge proceeds. When the surface of the positive electrode active material 100 has a coating derived from the electrolyte, it can be expected that the charge and discharge cycle characteristics will be improved. This is because of the following reasons: suppressing the increase in impedance on the surface of the positive electrode active material; or suppressing the dissolution of cobalt; etc. The coating 104 preferably contains carbon, oxygen and fluorine, for example. Furthermore, a high-quality coating is easily obtained when LiBOB and / or SUN (suberonitrile) is used as part of the electrolyte. Therefore, the coating 104 containing at least one or more than two selected from boron, nitrogen, sulfur and fluorine is sometimes a high-quality coating, so it is preferred. In addition, the coating 104 may not cover the entire positive electrode active material 100.

[0200] <Crystal Structure>

[0201] The positive electrode active material 100 of one embodiment of the present invention has a unique crystal structure. The crystal structure is described by comparing it with the existing lithium cobalt oxide. When describing the crystal structure, the amount of lithium ion released is x, and the positive electrode active material 100 is represented as Li x Co (1-y) Ni y O2, the explanation will focus on this x. Note that the desorption amount x is different from the addition amount of lithium.

[0202] < <Li x Co (1-y) Ni y When x is 1 in O2 >>

[0203] Figure 5 FIG. 2 shows the crystal structure of the positive electrode active material 100 according to one embodiment of the present invention. The positive electrode active material 100 according to one embodiment of the present invention is preferably in a discharged state, that is, in a state where Li x Co (1-y) Ni y When x=1 in O2, it has a layered rock salt type crystal structure. In particular, the inner portion 100c occupying most of the volume of the positive electrode active material 100 preferably has a layered rock salt type crystal structure belonging to the space group R-3m.

[0204] exist Figure 5 In the formula, R-3m O3 represents a layered rock salt type crystal structure. Figure 5 In the case of O3, O3 is attached to the position adjacent to the space group. However, in this crystal structure, lithium occupies the octahedral site, and there are three layers (hereinafter referred to as MO2 layers) composed of transition metal M (M is cobalt and / or nickel) and oxygen octahedra in the unit cell, so this crystal structure is sometimes called an O3 type crystal structure. Note that the MO2 layer refers to a structure in which six oxygens are coordinated to the octahedral structure of the transition metal M and the edge lines are shared on one plane. In addition, although in Figure 5 2 shows the case where all lithium ions are present at the lithium site, but as described above, there are cases where an added element such as magnesium ion is located at the lithium site.

[0205] The surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention may have a layered structure composed of MO2 layers in the inner portion 100c, which can be strengthened to prevent the layered structure from collapsing even if lithium is separated from the positive electrode active material 100 due to charging. Alternatively, the surface portion 100a is preferably used as a barrier film of the positive electrode active material 100. Alternatively, the surface portion 100a of the outer peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening refers to suppressing the detachment of oxygen and / or the deviation of the layered structure composed of MO2 layers, etc., and / or suppressing the decomposition of the organic electrolyte on the surface of the positive electrode active material 100. Magnesium can suppress the detachment of surrounding oxygen, so the above-mentioned strengthening can be performed by including at least magnesium as an added element.

[0206] For example, the surface portion 100a may have a different crystal structure from the inner portion 100c. In addition, when the surface portion 100a has a crystal structure that is more stable at room temperature (25°C) than the inner portion 100c, the above-mentioned reinforcement effect can be produced, so it is preferred. For example, at least a portion of the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has the characteristics of both a layered rock salt type crystal structure and a rock salt type crystal structure.

[0207] The surface part 100a is the area where lithium ions are first separated during charging, and is also the area where the lithium concentration tends to be lower than that of the inner part 100c. In addition, it can be said that part of the bonds among the atoms on the surface of the particles of the positive electrode active material 100 contained in the surface part 100a are cut. Therefore, the surface part 100a can also be said to be an area that tends to be unstable and where crystal structure degradation is easy to begin. For example, it can be considered that: when the crystal structure of the layered structure composed of MO2 layers in the surface part 100a deviates, its influence extends to the inner part 100c and the crystal structure of the layered structure in the inner part 100c also deviates, resulting in the degradation of the overall crystal structure of the positive electrode active material 100. On the other hand, as long as the surface part 100a is sufficiently stabilized, in the case of Li x Co (1-y) Ni y When x in O2 is small, the layered structure composed of the MO2 layer in the inner part 100c can be less likely to collapse. In addition, the deviation of the MO2 layer in the inner part 100c can be suppressed.

[0208] It has also been explained that the distribution of the added elements in the (001) plane of the positive electrode active material 100 may be different from that in the planes other than the (001) plane. This may be because: in the layered rock salt type crystal structure, the MO2 layer is relatively stable, so it is more stable when the surface of the positive electrode active material 100 is the (001) plane, but the diffusion path of lithium ions is exposed on the planes other than the (001) plane. Although the main diffusion path of lithium ions is not exposed on the above-mentioned (001) plane during charging and discharging, the main diffusion path of lithium ions is exposed on the planes other than the (001) plane, which is an important area for maintaining the diffusion path of lithium ions. Furthermore, since the planes other than the (001) plane are the areas where lithium ions initially leave, they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is preferred to strengthen the planes other than the (001) plane.

[0209] Therefore, in the case of magnesium, the half width of the distribution in the (001) plane and the surface portion 100a having the plane is preferably 5 nm or more and 150 nm or less, more preferably 10 nm or more and 100 nm or less, and further preferably 20 nm or more and 80 nm or less. In addition, the half width of the distribution of magnesium in the surface portion 100a other than the (001) plane and the surface portion 100a having the plane is preferably greater than 150 nm and 280 nm or less, more preferably greater than 180 nm and 250 nm or less, and further preferably 200 nm or more and 230 nm or less. When the half width is regarded as the distribution width, the distribution width of the (001) plane and the surface portion 100a having the plane in the distribution of magnesium is preferably 10 nm or more and 300 nm or less. In addition, the distribution width of magnesium in the surface portion 100a other than the (001) plane and the surface portion 100a having the plane is preferably greater than 300 nm and 500 nm or less. Since magnesium may increase the resistance value of the surface layer portion 100 a , magnesium is preferably distributed so as to have the above-mentioned small width.

[0210] In the manufacturing method of heating after mixing the additive elements shown in the following embodiment, the additive elements sometimes diffuse mainly through the diffusion path of lithium ions. Therefore, in order to distribute the additive elements on the surface other than the (001) surface and the surface portion 100a having the surface within a preferred range, it is preferred to adopt a method of mixing the additive elements after manufacturing the composite oxide containing lithium cobalt nickel oxide or to the hydroxide as a precursor of the composite oxide. Note that magnesium has a large ionic radius, so it is easy for magnesium to remain on the surface portion 100a no matter which process it is added in, so it is preferred.

[0211] 〔magnesium〕

[0212] Since the ionic radius of magnesium is close to that of lithium ions, magnesium ions easily enter the lithium sites in the layered rock salt type crystal structure. When magnesium is present at an appropriate concentration at the lithium sites of the surface portion 100a, the crystal structure of the inner portion 100c can be easily maintained. This is because the magnesium present at the lithium sites acts as a pillar to support the MO2 layers. In addition, when magnesium is present, even in the presence of Li x Co (1-y) Ni y When x in O2 is small, oxygen separation around magnesium can be suppressed, thereby suppressing thermal decomposition reaction. In addition, when the magnesium concentration of the surface layer 100a is high, it is expected to improve the corrosion resistance to hydrofluoric acid generated by decomposition of organic electrolytes, etc.

[0213] 〔fluorine〕

[0214] Fluorine ions are anions and can also replace part of oxygen, which is also an anion. That is, fluorine can also replace part of the oxygen in the surface layer portion 100a at an appropriate concentration. In addition, the redox potential of cobalt ions as lithium is separated is different depending on whether fluorine is contained or not. That is, for example, when fluorine is not contained, cobalt ions change from trivalent to tetravalent as lithium is separated. On the other hand, when fluorine is contained, cobalt ions change from divalent to trivalent as lithium is separated. The redox potential of cobalt ions is different between the two, and the energy when lithium is separated from the positive electrode active material 100 is small when fluorine is contained. Therefore, the insertion and separation of lithium ions near fluorine tend to occur smoothly. Therefore, fluorine is preferably present on the surface or surface layer portion 100a of the positive electrode active material 100. When the positive electrode active material 100 containing fluorine is used in a secondary battery, the charge and discharge characteristics, large current characteristics, etc. can be improved.

[0215] In addition, when fluorine is present on the surface or surface layer of the portion in contact with the electrolyte or when fluoride is adsorbed or attached to the surface, excessive reaction between the positive electrode active material 100 and the electrolyte can be suppressed. In addition, when fluorine is present on the surface or surface layer of the portion in contact with the electrolyte, it can be expected to improve the corrosion resistance to hydrofluoric acid generated by decomposition of organic electrolytes, etc. The above-mentioned adsorption includes chemical adsorption or physical adsorption. Chemical adsorption refers to the formation of a chemical bond through a chemical reaction between fluorine and the surface of the positive electrode active material 100, and physical adsorption refers to adsorption using the intermolecular force (van der Waals force) acting between fluorine and the surface of the positive electrode active material 100.

[0216] In addition, the melting point of fluorine compounds such as lithium fluoride (sometimes also called fluoride) considered as fluorine sources is sometimes lower than the melting point of other additive element sources. In other words, fluorine compounds and the like may be used as fluxes (also called auxiliary solvents) to lower the melting points of other additive element sources. When the fluorine compound includes LiF and MgF2, the eutectic point of LiF and MgF2 is around 742°C, so in the heating process after mixing the additive elements, the heating temperature is preferably 742°C or thereabouts.

[0217] 〔nickel〕

[0218] Nickel has a lower redox potential than cobalt, so it is easy to lose lithium during charging, for example. Therefore, it is expected that the charge and discharge speed of the positive electrode active material 100 having a relatively high number of nickel atoms will be increased.

[0219] In addition, the order of ionization tendency from large to small is magnesium, aluminum, cobalt, and nickel. Therefore, during charging, nickel is less likely to dissolve in the electrolyte than the other elements. Therefore, nickel has a high effect of stabilizing the crystal structure of the surface portion in the charging state, and nickel is preferably present in the inner portion 100c and the surface portion 100a.

[0220] 〔aluminum〕

[0221] Aluminum may exist at the cobalt site in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence remains unchanged, so lithium around aluminum is not easy to migrate during charge and discharge. Therefore, aluminum and the lithium around it can maintain the interval between adjacent MO2 layers, which may inhibit changes in the crystal structure. Therefore, even if the positive electrode active material 100 is stretched and contracted in the c-axis direction due to the insertion and removal of lithium ions, that is, the force of stretching and contracting in the c-axis direction due to changes in the depth of charge or the charging rate, the degradation of the positive electrode active material 100 can be suppressed.

[0222] In addition, aluminum has the effect of suppressing the dissolution of surrounding cobalt and improving continuous charging tolerance. In addition, the Al-O bond is stronger than the MO bond, specifically, the CoO bond, so the oxygen around the aluminum can be suppressed from detaching. Through the above effect, thermal stability is improved. Therefore, when aluminum is included as an added element, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. In addition, a positive electrode active material 100 that is not prone to crystal structure collapse even after repeated charge and discharge can be achieved.

[0223] [Synergistic effect of multiple elements]

[0224] Furthermore, when magnesium and nickel coexist in the surface layer portion 100a, nickel may be more stably present near magnesium. x Co (1-y) Ni y When x in O2 is small and magnesium and nickel coexist in the surface portion 100a, the dissolution of magnesium may be suppressed, thereby contributing to the stabilization of the surface portion 100a.

[0225] When a plurality of additive elements are included as described above, each additive element synergistically contributes to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are included, the effect of achieving a stable composition and crystal structure is high, and therefore, it is preferred.

[0226] Note that it is not preferred that lithium is not easily inserted and removed when only the compound of the added element and oxygen is present in the surface portion 100a. For example, it is not preferred that only MgO is dissolved in the surface portion 100a. Therefore, the surface portion 100a needs to contain at least cobalt, and also contain lithium in the discharge state, and have a path for the insertion and removal of lithium. In order to fully ensure the path for the insertion and removal of lithium, the cobalt concentration of the surface portion 100a is preferably higher than the magnesium concentration. In addition, it is permitted that the nickel concentration of the surface portion 100a is higher than the magnesium concentration.

[0227] In addition, the concentration of magnesium in the surface layer portion 100a, which is part of the additive element, is preferably higher than that in the interior 100c, but magnesium is preferably also present irregularly and in small amounts in the interior 100c. When magnesium is present at an appropriate concentration at the lithium sites in the interior 100c, there is an effect of easily maintaining the layered rock salt-type crystal structure in the same manner as described above.

[0228] In addition, the concentration of aluminum in the surface layer portion 100a, which is part of the additive element, is preferably higher than that in the interior 100c, but aluminum is preferably also present irregularly and in small amounts in the interior 100c. When aluminum is present at an appropriate concentration at the lithium sites in the interior 100c, there are effects such as easily maintaining the layered rock salt-type crystal structure in the same manner as described above.

[0229] When nickel is present in the interior 100c, the deviation of the layered structure composed of the MO2 layer can be suppressed in the same manner as described above. In addition, when nickel is present in the surface layer portion 100a, the deviation of the layered structure composed of the MO2 layer can be suppressed in the same manner as described above.

[0230] <<Li x Co (1-y) Ni y O2 in the case where x is small>>

[0231] Since the positive electrode active material 100 according to one embodiment of the invention has the above-described additive element distribution and / or crystal structure, the crystal structure in the state where x in Li x Co (1-y) Ni y O2 is small, that is, in the state of charging at a high voltage, is different from that of the existing lithium cobaltate. Note that x being small here means, for example, the case where 0.1 < x ≤ 0.24. In addition, the high voltage in the charged state means 4.5 V or more, 4.6 V or more, preferably 4.7 V or more, and more preferably 4.8 V or more.

[0232] Refer to Figure 5 Comparing the existing lithium cobaltate with the positive electrode active material 100 according to one embodiment of the invention to explain the crystal structure change accompanying the change in x in Li x Co (1-y) Ni y O2.

[0233] First, the existing lithium cobaltate will be described. It is known that: the existing lithium cobaltate has a crystal structure belonging to the monoclinic space group P2 / m with improved lithium symmetry when x is around 0.5. In this structure, the unit cell includes one CoO2 layer. Therefore, it is sometimes referred to as the O1 type structure or the monoclinic O1 type structure.

[0234] When x=0, the existing lithium cobalt oxide has a crystal structure of the space group P-3m1 of the trigonal system, and the unit cell includes one CoO2 layer. Therefore, this crystal structure is sometimes called O1 type structure or trigonal O1 type structure. In addition, the trigonal system is sometimes converted into a composite hexagonal lattice and called hexagonal O1 type.

[0235] In addition, the existing lithium cobalt oxide has a crystal structure belonging to the space group R-3m when x=0.12. It can also be said that the structure is a structure in which a CoO2 structure such as a trigonal O1 type structure and a LiCoO2 structure such as a R-3m O3 are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. Note that the actual insertion and removal of lithium does not necessarily occur uniformly in the positive electrode active material, so the change in the crystal structure is not strictly relative to the amount of lithium removal, and the value of the lithium removal amount can also be the value of the timing of starting the crystal change.

[0236] In conventional lithium cobalt oxide, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure changes between the H1-3 type crystal structure and the R-3m O3 structure in the discharge state (ie, non-equilibrium phase transition) are repeated.

[0237] The CoO2 layer of the above two crystal structures deviates greatly. In the H1-3 type crystal structure, the CoO2 layer deviates greatly from the R-3m O3 in the discharge state. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.

[0238] Furthermore, the volume difference between the two crystal structures is also large. When comparing the same number of cobalt atoms, the volume difference between the H1-3 structure and the R-3m O3 structure in the discharged state exceeds 3.5%, typically 3.9% or more.

[0239] In addition to the above, the structure of the H1-3 type crystal structure in which the CoO2 layer is continuous, such as the trigonal O1 type, is likely to be unstable.

[0240] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure will cause the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and lithium insertion and extraction become difficult.

[0241] Next, a positive electrode active material 100 according to one embodiment of the present invention is described. Figure 5 The positive electrode active material 100 of one embodiment of the present invention shown in the figure is different from the conventional lithium cobalt oxide. x Co (1-y) Ni y When x in O2 is small, for example, when x=0.2, the crystal structure changes differently. Figure 5 In the case of x=0.2, the positive electrode active material 100 of one embodiment of the present invention shows a crystal structure belonging to the space group R-3m of the trigonal system. The symmetry of the MO2 layer of this structure is the same as that of O3. Therefore, this crystal structure is called an O3' type crystal structure. Figure 5 In the embodiment of the present invention, the crystal structure is labeled R-3m O3'. In addition, the XRD pattern of the crystal structure sometimes appears similar to that of the spinel structure, so the crystal structure can also be called a pseudo-spinel structure.

[0242] As in Figure 5 Indicated by the dotted line, in the positive electrode active material 100 of one embodiment of the present invention, there is almost no deviation of the Mo2 layer between the R-3m O3 type crystal structure and the O3' type crystal structure in the discharge state. In other words, in the positive electrode active material 100 of one embodiment of the present invention, the deviation of the MoO2 layer between the state where x is 1 and the state where x is smaller is small. In addition, in the positive electrode active material 100 of one embodiment of the present invention, the volume change when compared per transition metal atom can be reduced. Therefore, in the positive electrode active material 100 of one embodiment of the present invention, even if charging and discharging are repeatedly performed so that x becomes about 0.2, specifically, becomes less than 0.24, the crystal structure is not easy to collapse, and the site where lithium can exist stably is maintained, thereby achieving good cycle characteristics.

[0243] In the positive electrode active material 100 of one embodiment of the present invention, more lithium can be stably used than in conventional lithium cobalt oxide, so the positive electrode active material 100 has a larger discharge capacity per unit weight and per unit volume. Therefore, by using the positive electrode active material 100, a secondary battery with a larger discharge capacity per unit weight and per unit volume can be manufactured.

[0244] The positive electrode active material 100 of one embodiment of the present invention is Li x Co (1-y) Ni y When x in O2 is 0.24 or less, it can have a more stable crystal structure than the existing lithium cobalt oxide. Therefore, it can be inferred that the positive electrode active material 100 of one embodiment of the present invention can maintain Li x Co (1-y) Ni y When x in O2 is 0.24 or less, oxygen is not easily released and thermal decomposition reaction can be suppressed, and a lithium ion secondary battery using the positive electrode active material 100 does not catch fire even in a needle penetration test. That is, the safety of a secondary battery using the positive electrode active material 100 of one embodiment of the present invention is further improved, so it is preferred.

[0245] Note that in this specification, no fire in the needle penetration test means that no open flame is observed outside the outer package or thermal runaway of the secondary battery occurs. That is, even if sparks and / or smoke are observed, no fire spreads, which means no fire.

[0246] The coordinates of typical cobalt and oxygen in the unit cell of the O3' type crystal structure possessed by the positive electrode active material 100 can be represented by Co(0, 0, 0.5) and O(0, 0, x) respectively, and are within the range of 0.20≤x≤0.25. In addition, the lattice constant of the unit cell of the O3' type crystal structure is as follows: the a-axis is preferably 2.797×10 -10 ≤a≤2.837×10 -10 (m), more preferably 2.807×10 -10 ≤a≤2.827×10 -10 (m), typically a = 2.817 × 10 -10 (m). The c-axis is preferably 13.681×10 -10 ≤c≤13.881×10 -10 (m), more preferably 13.751×10 -10 ≤c≤13.811×10 -10 (m), typically c = 13.781 × 10 -10 (m).

[0247] In addition, in order to achieve Li x Co (1-y) Ni y In the state where x in O2 is small, it is generally necessary to charge with a high charging voltage. x Co (1-y) Ni y The state in which x in O2 is smaller is referred to as the state of charging at a high charging voltage. For example, when constant current (CC) charging is performed at a voltage of 4.6V or more at 25°C based on the potential of lithium metal and then constant voltage (CV) charging is performed (this charging is referred to as CCCV charging), the existing lithium cobalt oxide begins to present an H1-3 type crystal structure. On the other hand, the positive electrode active material 100 of one embodiment of the present invention can also maintain a crystal structure with R-3m O3 symmetry under a high charging voltage, such as CCCV charging at a voltage of 4.6V or more at 25°C, so it is preferred.

[0248] In this specification, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal. Note that the potential of the positive electrode when a material other than lithium metal is used as the counter electrode is different from that of a secondary battery. For example, when focusing on the potential of the positive electrode, charging at 4.5V when using graphite as the counter electrode is roughly equivalent to charging at 4.6V when using lithium as the counter electrode.

[0249] In addition, although Figure 5 In the O3' type crystal structure, lithium exists in all lithium sites with equal probability, but it is not limited to this. In addition, lithium may exist concentratedly in a part of the lithium sites. The distribution of lithium can be analyzed by neutron diffraction, for example.

[0250] As described above, the positive electrode active material 100 of one embodiment of the present invention is preferably based on Li x Co (1-y) Ni y The change of x in O2 has a unique crystal structure different from the existing lithium cobalt oxide. x Co (1-y) Ni y The change in x in O2 is equal to the change in depth of charge, and the depth of charge when x=0.2 is equivalent to 1-0.2=0.8.

[0251] <Particle size>

[0252] In the particle size distribution curve where the horizontal axis represents the integral %, the particle size that intersects the point where the horizontal axis is 10% is called the 10% diameter or D10, the particle size that intersects the point where the horizontal axis is 50% is called the 50% diameter or D50, and the particle size that intersects the point where the horizontal axis is 90% is called the 90% diameter or D90. Sometimes D50 is called the median particle size. When expressing the particle size, D50 is used in many cases. When the particle size of the positive electrode active material 100 in one embodiment of the present invention is too large, there are the following problems: the diffusion of lithium becomes difficult; when applied to the current collector, the surface of the active material layer is too rough, etc. On the other hand, when the particle size of the positive electrode active material 100 is too small, there are the following problems: excessive reaction with the electrolyte, etc. Therefore, in the positive electrode active material 100, D50 is preferably greater than 1 μm and less than 100 μm, more preferably greater than 15 μm and less than 40 μm, and further preferably greater than 15 μm and less than 35 μm.

[0253] In addition, by mixing particles of different particle sizes and using them for the positive electrode, the electrode density can be increased, and a secondary battery with high energy density can be realized, so it is preferred. The positive electrode active material 100 with a relatively small particle size is expected to have high charge and discharge rate characteristics. The positive electrode active material 100 with a relatively large particle size is expected to have high charge and discharge cycle characteristics and can maintain a large discharge capacity.

[0254] <<Analysis Method>>

[0255] In order to determine whether a positive electrode active material has an O3' type crystal structure during discharge, the Li x Co (1-y) Ni y The positive electrode of the positive electrode active material with a smaller x in O2 can be determined by analysis using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. For example, x can be 0.2.

[0256] Note that the positive electrode active material in a state where x is small may undergo a change in crystal structure when exposed to air. Therefore, all samples used in analyzing the crystal structure are preferably handled in an inert atmosphere such as an argon atmosphere.

[0257] In particular, XRD is preferred because of the following advantages: the symmetry of the transition metal contained in the positive electrode active material can be analyzed with high resolution; the height of crystallinity and the orientation of crystallinity can be compared; the periodic distortion of the lattice and the grain size can be analyzed; sufficient accuracy can be obtained when directly measuring the positive electrode obtained by disassembling a secondary battery, etc. In XRD, powder XRD can obtain a diffraction peak reflecting the crystal structure of the inner 100c of the positive electrode active material 100 that occupies most of the volume of the positive electrode active material 100.

[0258] <<Charging Method>>

[0259] For example, a coin-shaped battery (also called a coin battery, CR2032 type, 20 mm in diameter, 3.2 mm in height) using lithium metal as a counter electrode can be manufactured and charged to determine whether a certain positive electrode active material is the positive electrode active material 100 of one embodiment of the present invention.

[0260] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0261] As described above, lithium metal can be used as the counter electrode, but materials other than lithium metal can also be used. When materials other than lithium metal are used, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification, etc. are the potential of the positive electrode.

[0262] As the lithium salt contained in the electrolyte, 1 mol / L lithium hexafluorophosphate (LiPF6) is used, and as the electrolyte, an electrolyte obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a ratio of EC:DEC=3:7 (volume ratio) can be used. In the electrolyte, 2 wt% of vinylene carbonate (VC) can also be mixed as an additive.

[0263] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.

[0264] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).

[0265] The coin cell manufactured under the above conditions is charged at any voltage (for example, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). For example, when charging with CCCV, the current in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until it is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. The XRD measurement temperature is preferably 25°C. After charging in the above manner, the coin cell is disassembled in a glove box with an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charging capacity, that is, any charging depth. When performing various analyses later, in order to prevent reactions with external components, it is preferably sealed under an argon atmosphere. For example, XRD can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode for analysis immediately after charging. Specifically, the analysis is preferably performed within 1 hour after completion of charging, and more preferably within 30 minutes after completion of charging.

[0266] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may be different from the above-mentioned charging conditions. For example, the charging may be CC charged to any voltage (e.g., 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V) at a current value of 20mA / g or more and 100mA / g or less, and then CV charged until the current value reaches 2mA / g or more and 10mA / g or less, and the discharging may be CC discharged to 2.5V at a current value of 20mA / g or more and 100mA / g or less.

[0267] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge and discharge, for example, CC discharge to 2.5 V can be performed at a current value of 20 mA / g or more and 100 mA / g or less.

[0268] In this specification, etc., the data processing when the value of 2θ of a certain diffraction peak is described. First, the calculation model is fitted to the XRD pattern using crystal structure analysis software to obtain the calculated pattern. In the calculated pattern, the value of 2θ appearing at the peak of the diffraction peak is referred to as the value of 2θ of the diffraction peak. There is no particular restriction on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker Corporation) can be used.

[0269] The 2θ range of the positive electrode active material 100 of one embodiment of the present invention when using a CuKα1 source is shown. When the positive electrode active material 100 has an O3' type crystal structure, diffraction peaks appear at 2θ=19.30±0.20° (19.10° or more and less than 19.50°) and 2θ=45.55±0.10° (45.45° or more and less than 45.65°).

[0270] It can be said that: in Li x Co (1-y) Ni y When x in O2 is small, for example, when x is 0.24 or less, the presence of diffraction peaks at least at 2θ=19.30±0.20° and 2θ=45.55±0.10° is a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0271] It can be said that the positions of the diffraction peaks observed by XRD of the crystal structure of x=1 and the crystal structure of x≤0.24 are close. More specifically, it can be said that the difference in 2θ of the diffraction peaks appearing at 2θ of 42° or more and 46° or less among the main diffraction peaks of the crystal structure of x=1 and the crystal structure of x≤0.24 is 0.7° or less, preferably 0.5° or less.

[0272] Note that the positive electrode active material 100 of one embodiment of the present invention is Li x Co (1-y) Ni y When x in O2 is small, it has an O3' type crystal structure, but not all particles need to have the O3' type crystal structure. In addition, it may have other crystal structures or be partially amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type crystal structure preferably accounts for more than 50%, more preferably more than 60%, and further preferably more than 66%. There is no particular limitation on the crystal structure analysis software used for Rietveld analysis, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker) can be used. GOF (Goodness of fit) is preferably less than 1.3, which can be said to be a sufficient fit.

[0273] Similarly, when the Rietveld analysis is performed, the H1-3 type and O1 type crystal structures preferably account for 40% or less.

[0274] In addition, the sharpness of the diffraction peak in the XRD diagram indicates the height of crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half width (e.g., half maximum full width) is preferably narrow. The half width of the peak of the same crystalline phase varies depending on the measurement conditions of XRD and the value of 2θ.

[0275] As described above, the influence of the Jan-Teller effect in the positive electrode active material 100 of one embodiment of the present invention is preferably small. XRD analysis was performed to examine the range of the ratio and lattice constant of nickel in the positive electrode active material where the influence of the Jan-Teller effect is estimated to be small.

[0276] FIG. 6 shows the results of calculating the lattice constants of the a-axis and the c-axis by XRD when the positive electrode active material 100 according to one embodiment of the present invention has a layered rock salt type crystal structure and contains cobalt and nickel. Fig. 6A The results of the a-axis are shown. Figure 6B The results of the c-axis are shown. The XRD patterns used for these calculations are the powders after the positive electrode active material is synthesized and before being assembled into the positive electrode. The nickel concentration on the horizontal axis is equal to the atomic ratio of nickel when the sum of the atomic ratios of cobalt and nickel is 100%.

[0277] Figure 6C Shown in Fig. 6A and Figure 6B The result of the lattice constant shown in is a value obtained by dividing the lattice constant of the a-axis of the positive electrode active material by the lattice constant of the c-axis (a-axis / c-axis).

[0278] exist Figure 6C It was confirmed that the a-axis / c-axis tended to change significantly when the nickel concentration increased from 5 at% to 7.5 at%, as shown in FIG. Fig. 6A It can be seen that the distortion of the a-axis becomes larger when the nickel concentration is 7.5 at%. This distortion may be caused by the Jan-Teller distortion of trivalent nickel. When the nickel concentration is lower than 7.5 at%, an excellent positive electrode active material with small Jan-Teller distortion can be obtained. Therefore, it can be considered that: when LiCo is used as the positive electrode active material 100 1-y-z Ni y O2A z When z is greater than 0 and less than or equal to 0.3, a positive electrode active material having a small Jahn-Teller distortion can be obtained.

[0279] The composite oxide with small Jan-Teller distortion is preferably contained in the interior 100c of the positive electrode active material 100. That is, the above nickel concentration range does not necessarily apply to the surface portion 100a of the positive electrode active material 100. That is, the nickel concentration of the surface portion 100a may be higher than the above concentration.

[0280] In summary, when examining the preferred range of the lattice constant, it can be seen that in the positive electrode active material 100 of one embodiment of the present invention, the lattice constant of the a-axis in the layered rock salt type crystal structure of the positive electrode active material 100 in the non-charged or discharged state, which can be inferred from the XRD diagram, is preferably greater than 2.814×10 -10 m and less than 2.817×10 - 10 m, and the lattice constant of the c-axis is preferably greater than 14.05×10 -10 m and less than 14.07×10 -10 m. The state in which charging and discharging are not performed may refer to, for example, the state of powder before the positive electrode of the secondary battery is produced.

[0281] It can be said that in the positive electrode active material 100 in the non-charge and discharge state or in the discharge state, the value of the a-axis lattice constant divided by the c-axis lattice constant (a-axis / c-axis) is preferably larger than 0.20000 and smaller than 0.20049.

[0282] When the positive electrode active material 100 in a non-charged or discharged state is subjected to XRD analysis, a first peak at 2θ of 18.50° to 19.30° and a second peak at 2θ of 38.00° to 38.80° may be observed.

[0283] < <xps>>

[0284] In the XPS analysis of inorganic oxides, when monochromatized aluminum Kα rays are used as the X-ray source, the analysis of the region with a depth of about 2nm to 8nm (generally less than 5nm) from the surface can be performed, so the concentration of each element in the region of about half the depth of the surface portion 100a of the positive electrode active material 100 can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. The quantitative accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.

[0285] In the positive electrode active material 100 of one embodiment of the present invention, the concentration of one or more selected from the added elements in the surface part 100a is preferably higher than the concentration in the inner part 100c. This means that the concentration of one or more selected from the added elements in the surface part 100a is preferably higher than the average concentration of the positive electrode active material 100 as a whole. Therefore, for example, it can be said that the concentration of one or more selected from the added elements in the surface part 100a measured by XPS or the like is preferably higher than the average concentration of the positive electrode active material 100 as a whole measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry analysis). For example, the magnesium concentration of at least a portion of the surface part 100a measured by XPS or the like is preferably higher than the average concentration of magnesium in the positive electrode active material 100 as a whole. In addition, the nickel concentration of at least a portion of the surface part 100a is preferably higher than the average concentration of nickel in the positive electrode active material 100 as a whole. In addition, the aluminum concentration of at least a portion of the surface part 100a is preferably higher than the average concentration of aluminum in the positive electrode active material 100 as a whole. Furthermore, the fluorine concentration of at least a portion of the surface layer portion 100 a is preferably higher than the average fluorine concentration of the entire positive electrode active material 100 .

[0286] In addition, the concentration of the added element can also be compared with the ratio of cobalt. By using the ratio with cobalt, the influence of carbonates chemically adsorbed after manufacturing the positive electrode active material can be reduced for comparison, so it is preferred. For example, the ratio of the number of atoms of magnesium and cobalt obtained by XPS analysis Mg / Co is preferably 0.4 or more and 1.5 or less. On the other hand, the Mg / Co obtained by ICP-MS analysis is preferably 0.001 or more and 0.06 or less.

[0287] Similarly, in order to fully ensure the path of insertion and extraction of lithium, the concentration of lithium and cobalt in the surface portion 100a of the positive electrode active material 100 is preferably higher than the concentration of each added element. This means that the concentration of lithium and cobalt in the surface portion 100a is preferably higher than the concentration of one or more added elements selected from the added elements contained in the surface portion 100a measured by XPS or the like.

[0288] Furthermore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to XPS analysis, the atomic number ratio of magnesium relative to the atomic number ratio of cobalt is preferably 0.4 times or more and 1.2 times or less, more preferably 0.65 times or more and 1.0 times or less. In addition, the atomic number ratio of aluminum relative to the atomic number ratio of cobalt is preferably 0.12 times or less, more preferably 0.09 times or less. The ratio within the above range means that each added element is widely distributed in the surface layer 100a of the positive electrode active material 100 at a preferred concentration.

[0289] When performing XPS analysis, for example, monochromatized aluminum Kα rays are used as an X-ray source. In addition, for example, the extraction angle may be 45°. For example, the measurement may be performed with the following apparatus and conditions.

[0290] Measuring device: Quantera II manufactured by PHI

[0291] X-ray source: monochromated aluminum Kα (1486.6 eV)

[0292] Detection area:

[0293] Detection depth: about 4nm to 5nm (extraction angle is 45°)

[0294] Measurement spectrum: wide scan, narrow scan for each detected element

[0295] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak of the bond energy between fluorine and other elements is preferably 682 eV or more and less than 685 eV, and more preferably about 684.3 eV. This value is different from the bond energy of lithium fluoride of 685 eV and the bond energy of magnesium fluoride of 686 eV.

[0296] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak of the bond energy between magnesium and other elements is preferably 1302 eV or more and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bond energy of magnesium fluoride of 1305 eV, and is close to the bond energy of magnesium oxide.

[0297] < <edx>>

[0298] One or two of the selected added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, the positive electrode active material 100 preferably has a concentration peak with a different depth from the surface according to the added element. The concentration gradient of the added element can be evaluated by, for example, exposing a cross section of the positive electrode active material 100 by FIB (Focused Ion Beam) or the like and analyzing the cross section by EDX, EPMA, or the like.

[0299] In EDX measurement, the method of measuring while scanning in a region to evaluate the region in two dimensions is called EDX surface analysis. In addition, the method of measuring while scanning in a line to evaluate the atomic concentration distribution in the positive electrode active material is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring without scanning in a certain area is called point analysis.

[0300] By EDX surface analysis (e.g., element mapping), the concentration of the added element in the surface layer 100a, the interior 100c, and the vicinity of the grain boundary 101 of the positive electrode active material 100 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and the maximum value of the added element can be analyzed. In addition, in the analysis of thinning the sample such as STEM-EDX, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0301] Therefore, when EDX surface analysis or EDX point analysis is performed on the positive electrode active material 100 of one embodiment of the present invention, the concentration of each additional element, especially the additional element, in the surface layer portion 100 a is preferably higher than the concentration of each additional element in the inner portion 100 c .

[0302] In addition, when EDX line analysis, EDX surface analysis or EDX point analysis is performed on the positive electrode active material 100, the ratio of the number of magnesium atoms Mg to the number of cobalt atoms Co in the magnesium concentration peak (Mg / Co) is preferably 0.05 or more and 0.6 or less, and more preferably 0.1 or more and 0.4 or less. The ratio of the number of aluminum atoms Al to the number of cobalt atoms Co in the aluminum concentration peak (Al / Co) is preferably 0.05 or more and 0.6 or less, and more preferably 0.1 or more and 0.45 or less.

[0303] In addition, based on the EDX line analysis results, the surface of the positive electrode active material 100 can be estimated as follows, for example: the point where the detected amount of an element uniformly present in the inner part 100c of the positive electrode active material 100, such as oxygen or cobalt, is 1 / 2 of the detected amount in the inner part 100c is used as the surface of the positive electrode active material 100.

[0304] The positive electrode active material 100 is a composite oxide, so the surface can be estimated using the detected amount of oxygen. Specifically, first, the average oxygen concentration O is obtained from the region where the oxygen detected amount in the inner portion 100c is stable. ave At this time, when oxygen O due to chemical adsorption or background is detected in a region that can be judged to be clearly outside the surface, bg When O is subtracted from the measured value bg To find the average oxygen concentration O ave It can be inferred that the value closest to the average value is O ave 1 / 2 of the value, that is, O ave The measurement point of the measured value of / 2 is the surface of the positive electrode active material 100.

[0305] In addition, the detected amount of cobalt can also be used to estimate the surface of the positive electrode active material 100 in the same manner as described above. Alternatively, the total amount of the detected amounts of multiple transition metals can also be used to make the same estimate. The detected amount of transition metals such as cobalt is not easily affected by chemical adsorption, so it is suitable for estimating the surface.

[0306] This embodiment mode can be used in combination with other embodiment modes or examples.

[0307] (Implementation Method 2)

[0308] In this embodiment, refer to Figure 7 and Figure 8 The flowchart and the like shown in the figure illustrate a method for producing a positive electrode active material 100 according to one embodiment of the present invention. Figure 8 is omitted Figure 7 The flowchart of some steps is an example of a process with high productivity. Figure 7 and Figure 8 The described manufacturing method includes coprecipitation, and is therefore suitable for mass production. Coprecipitation refers to a method in which a sparingly soluble salt is precipitated from an aqueous solution containing two or more metal ions when the ion concentration is in a supersaturated state. Compared with the case of mixed solid materials, the mixing uniformity of the metal salts in the precipitate in the coprecipitation method is sometimes high, so it is preferred.

[0309] <Cobalt source>

[0310] like Figure 7 and Figure 8 As shown, prepare a cobalt source 81 (represented as Co source in the figure). The cobalt source 81 is one of the starting materials of the positive electrode active material. In addition, the cobalt source 81 uses a compound containing cobalt (represented as a cobalt compound). The cobalt compound can use, for example, cobalt sulfate, cobalt chloride or cobalt nitrate or their hydrates. In addition, as the cobalt compound, a cobalt alkoxide or an organic cobalt complex can also be used. In addition, as the cobalt compound, an organic acid of cobalt such as cobalt acetate or their hydrates can also be used. Note that in this specification, etc., organic acids include citric acid, oxalic acid, formic acid or butyric acid in addition to acetic acid.

[0311] When a solution is used as the cobalt source 81 , an aqueous solution containing the above-mentioned cobalt compound (referred to as a cobalt aqueous solution) is prepared.

[0312] <Nickel source>

[0313] like Figure 7 and Figure 8 As shown, prepare a nickel source 82 (referred to as Ni source in the figure). The nickel source 82 is one of the starting materials of the positive electrode active material. In addition, the nickel source 82 uses a compound containing nickel (referred to as a nickel compound). For example, nickel sulfate, nickel chloride, nickel nitrate, or a hydrate thereof can be used as the nickel compound. In addition, nickel alkoxides or organic nickel complexes can also be used as the nickel compound. In addition, organic acids of nickel such as nickel acetate or hydrates thereof can also be used as the nickel compound.

[0314] When a solution is used as the nickel source 82 , an aqueous solution containing the above-mentioned nickel compound (referred to as a nickel aqueous solution) is prepared.

[0315] When lithium cobalt oxide is obtained as the positive electrode active material 100, the proportion of nickel can be smaller than the proportion of cobalt. 1-y Ni y The cobalt source and the nickel source may be prepared in such a manner that y in O2 is greater than 0 and less than 0.5, preferably greater than 0 and less than 0.1, more preferably greater than 0 and less than 0.05, and further preferably greater than 0 and less than 0.01.

[0316] In other words, the atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is preferably greater than 0 and less than 0.5, more preferably greater than 0 and less than 0.1, preferably greater than 0 and less than 0.05, more preferably greater than 0 and less than 0.01, and the cobalt source and the nickel source are prepared in a manner that satisfies this relationship. The atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is sometimes recorded as Ni / (Ni+Co), which can also be said to be the proportion of nickel in the sum of cobalt and nickel. Note that, as shown in this paragraph, the atomic number ratio of cobalt and nickel prepared as the starting material may not satisfy the same atomic number ratio in the positive electrode active material 100.

[0317] Furthermore, excess lithium may be mixed in the positive electrode active material 100. Therefore, in the present invention, there is no limitation on the ratio of lithium. That is, when a transition metal such as cobalt or nickel is used as M, the composition is not strictly limited to Li:M:O=1:1:2.

[0318] The positive electrode active material of the present invention may contain manganese, but more preferably, substantially does not contain manganese. The positive electrode active material substantially not containing manganese has the advantages of being easier to synthesize, easier to handle, and having excellent cycle characteristics. "Substantially not containing manganese" can be considered to mean that the content in the positive electrode active material is small. Specifically, the weight of manganese in the positive electrode active material is less than 600 ppm, more preferably less than 100 ppm.

[0319] <Chelating Agents>

[0320] like Figure 7 As shown, a chelating agent 83 is prepared. Alternatively, the chelating agent 83 may be omitted, for example Figure 8 The flowchart is shown in which the chelating agent 83 is not prepared.

[0321] The chelating agent 83 is an aqueous solution in which a compound is dissolved, and this solution is recorded as a chelating aqueous solution. The chelating agent 83 is an aqueous solution in which, for example, glycine, oxine, 1-nitroso-2-naphthol, 2-mercaptobenzothiazole or EDTA (ethylenediaminetetraacetic acid) is dissolved as the above-mentioned compound, and this aqueous solution is recorded as a chelating aqueous solution. In addition, multiple substances selected from glycine, oxine, 1-nitroso-2-naphthol and 2-mercaptobenzothiazole can also be used. As the above-mentioned solvent, water is used, and preferably pure water is used.

[0322] The above-mentioned chelating agent is a complexing agent that forms a chelate compound, and therefore is preferred over a general complexing agent. Of course, ammonia water or the like, which is a general complexing agent, may be used instead of the chelating agent.

[0323] By using a chelating agent, the generation of unwanted nuclei can be suppressed and the growth of crystals can be promoted, so it is preferred. When the generation of unwanted core is suppressed, the generation of microparticles is suppressed, so a hydroxide (sometimes referred to as a precursor) with good particle size distribution can be obtained. In addition, by using a chelating agent, acid-base reaction can be delayed, and by reacting gradually, a spherical hydroxide can be obtained.

[0324] By using a glycine aqueous solution, it is easy to control Figure 7 and Figure 8 The pH of the solution in the reaction container in the coprecipitation reaction of step S31 is preferably adjusted. In addition, the glycine concentration of the glycine aqueous solution is 0.05 mol / L or more and 0.5 mol / L or less, preferably 0.1 mol / L or more and 0.2 mol / L or less.

[0325] <Pure Water>

[0326] The pure water used in the above chelate aqueous solution refers to water with a resistivity of 1MΩ·cm or more, preferably water with a resistivity of 10MΩ·cm or more, and more preferably water with a resistivity of 15MΩ·cm or more. Water that meets the above resistivity has high purity and contains very few impurities, so it is preferably used for acid-base reactions.

[0327] <Step S14>

[0328] Next, explain Figure 7 and Figure 8 Step S14 shown. In step S14, the cobalt source 81 and the nickel source 82 are mixed. By mixing in this step, a mixed solution 91 of the cobalt compound and the nickel compound is obtained. The cobalt compound and the nickel compound are dissolved in the mixed solution. As the water in this step, the above-mentioned pure water is preferably used. The mixed solution 91 is an acidic solution and can be called an acid solution.

[0329] <Alkaline aqueous solution>

[0330] Next, explain Figure 7 and Figure 8 An alkaline aqueous solution 84 is shown.

[0331] The alkaline aqueous solution 84 may be, for example, an aqueous solution containing sodium hydroxide, potassium hydroxide, lithium hydroxide or ammonia, but is not limited to these aqueous solutions as long as it is used as a pH adjuster. For example, an aqueous solution in which a plurality of selected from sodium hydroxide, potassium hydroxide and lithium hydroxide are dissolved in water may also be used. The above-mentioned pure water is preferably used as water.

[0332] <Chelating agent (filling liquid)>

[0333] like Figure 7 As shown, a chelating agent 85 is prepared. The chelating agent 85 can use the same material as the above-mentioned chelating agent 83. In addition, the chelating agent 85 can be omitted, for example Figure 8 The flowchart is shown without preparing the chelating agent 85. Note that Figure 8 In this case, it is preferred that water 86, preferably pure water, is placed in the reaction container as a filling liquid.

[0334] Additional Notes Figure 7 The chelating agent 85 shown. The chelating agent 85 is preferably placed in a reaction vessel for step S31 described later, and is sometimes referred to as a filling liquid or an adjustment liquid. In other words, the chelating agent 85 refers to an aqueous solution in the initial state of the reaction. Here, by using the chelating agent 85, the extra generation of crystal nuclei can be suppressed as described above to promote growth, and the generation of microparticles can be suppressed when the extra generation of nuclei is suppressed, so the following effects can be obtained: a hydroxide with a good particle size distribution can be obtained; an acid-base reaction can be delayed, whereby the reaction gradually progresses and a hydroxide close to a spherical shape can be obtained.

[0335] <Step S31>

[0336] illustrate Figure 7 and Figure 8 Step S31 shown. In step S31, a mixed solution 91 and an alkaline aqueous solution 84 are mixed in a reaction container. Through the mixing in step S31, the mixed solution 91 reacts with the alkaline aqueous solution 84, thereby producing a hydroxide 95 as a precursor. The chemical reaction in step S31 can be recorded as a neutralization reaction, an acid-base reaction, or a coprecipitation reaction. Through the above-mentioned coprecipitation reaction, a composite hydroxide 95 (abbreviated as hydroxide 95) containing cobalt and nickel as a transition metal M is precipitated. The hydroxide 95 can be called a precursor of the positive electrode active material 100. In addition, because the hydroxide 95 can also be called a compound of cobalt and nickel, it is sometimes recorded as a cobalt-nickel compound.

[0337] In step S31, preferably, the solution is stirred in advance using a stirring unit in the reaction vessel. The stirring unit includes an agitator or a stirring wing, etc. When the solution is stirred, it is preferably stirred at a rotation speed of more than 500 rpm and less than 1500 rpm, more preferably more than 800 rpm and less than 1200 rpm. In addition, more than two and less than six stirring wings can be provided, for example, when four stirring wings are provided, the stirring wings are preferably configured in a cross-shaped manner when viewed from above.

[0338] By the coprecipitation reaction as in step S31, nickel and cobalt can be uniformly mixed. That is, the hydroxide 95 having nickel in the inner part 100c can be obtained. The positive electrode active material 100 formed by the hydroxide 95 can enjoy the effect of nickel.

[0339] Note that when nickel is not easily dissolved in cobalt or after heat treatment described later, nickel may be concentrated in the surface portion 100a rather than in the inner portion 100c in the positive electrode active material 100. When nickel is present in the surface portion 100a, the positive electrode active material 100 can also enjoy the effect of nickel.

[0340] <Reaction Conditions>

[0341] When the mixed solution 91 and the alkaline aqueous solution 84 are reacted according to the coprecipitation reaction, the pH of the solution in the reaction container is 9 or more and 13 or less, preferably 9.8 or more and 12.5 or less. Within the above range, the particle size of the hydroxide 95 can be increased, so it is preferred. Outside the above range, the productivity may be reduced and the obtained hydroxide 95 may easily contain impurities.

[0342] When the mixed solution 91 is placed in a reaction container and the alkaline aqueous solution 84 is added dropwise to the reaction container, the pH of the solution in the reaction container is preferably maintained within the above-mentioned range. In addition, when the alkaline aqueous solution 84 is placed in a reaction container and the mixed solution 91 is added dropwise, the pH of the solution in the reaction container can also be maintained within the above-mentioned range.

[0343] When the solution in the reaction container is 200 mL or more and 350 mL or less, the infusion rate (also referred to as the dripping rate) of the mixed solution 91 or the alkaline aqueous solution 84 is preferably 0.01 mL / min or more and 1 mL / min or less, and more preferably 0.1 mL / min or more and 0.8 mL / min or less. The tank storing the mixed solution 91 or the alkaline aqueous solution 84 is provided with a pump, and the dripping rate can be controlled by the pump. The pump can also control the dripping amount. The dripping rate can also be changed in multiple stages, and specifically, it is preferred to gradually increase the dripping rate.

[0344] The temperature of the solution in the reaction container is adjusted to 50° C. or higher and 90° C. or lower. It is preferred to start dropping after checking the temperature of the solution. The above range is preferred because the particle size of the obtained hydroxide 95 can be increased.

[0345] In addition, the atmosphere in the reaction container is preferably an inert gas atmosphere. For example, in the case of a nitrogen atmosphere, nitrogen is preferably introduced at a flow rate of 0.5 L / min or more and 1.2 L / min or less. Furthermore, nitrogen can also be introduced into the liquid in the reaction container by bubbling.

[0346] Furthermore, the reaction vessel is preferably equipped with a reflux cooler. By means of the reflux cooler, nitrogen can be released from the reaction vessel and water can be returned to the reaction vessel.

[0347] Through the above reaction, a precipitate 92 is obtained as a reaction product in the reaction container.

[0348] <Step S32, Step S33>

[0349] right Figure 7 The filtration process of step S32 and the drying process of step S33 shown in the figure are explained. The precipitate 92 contains impurities in addition to the hydroxide 95. Therefore, in order to recover the hydroxide 95, it is preferred to perform the filtration of step S32. The filtration can be performed by suction filtration or vacuum filtration. In addition to filtration, centrifugal separation can also be used. When using suction filtration, it is preferred to use water (such as pure water, etc.) to wash the reaction product precipitated in the reaction container, and then use an organic solvent with a low boiling point (such as acetone, etc.) to wash it. In addition, it is preferred to perform suction filtration multiple times. Note that, as Figure 8 As shown, step S32 may not be performed.

[0350] The filtered product is preferably dried in step S33. For example, the drying is performed at a temperature of 60°C to 90°C for 0.5 hours to 20 hours, preferably 12 hours to 20 hours. In this way, hydroxide 95 can be obtained. In order to fully dry, it is preferred to dry in an atmosphere with less oxygen. By fully drying, impurities in hydroxide 95, such as water or hydroxyl groups, are reduced, so it is preferred. Note that, if Figure 8 As shown, step S33 may not be performed. For example, when drying under vacuum, a bell-shaped vacuum device may be used, which includes a container (denoted as a bell) capable of evacuating the interior to a vacuum and a vacuum pump connected to the bell. In addition, when drying in a vacuum atmosphere, a vacuum drying furnace may be used, and the vacuum drying furnace includes a vacuum pump connected to the drying furnace. The vacuum pumps of the bell-shaped vacuum device and the vacuum drying furnace may use a drying pump, a turbomolecular pump, an oil transfer pump, a cryogenic pump, or a mechanical booster pump. The vacuum atmosphere in the bell-shaped vacuum device and the vacuum drying furnace includes an atmosphere in which the pressure difference gauge of each device is reduced in a manner of -0.1MPa or more and less than -0.08MPa. When drying under a nitrogen atmosphere, a nitrogen-containing gas may be passed through the container of the bell-shaped vacuum device and the vacuum drying furnace.

[0351] In addition, heating may be performed instead of or in addition to the drying in step S33. The heating temperature is preferably 700° C. or higher and lower than 1200° C., more preferably 800° C. or higher and lower than 1100° C., and further preferably 900° C. or higher and lower than 1000° C. The heating time may be, for example, 1 hour or higher and 100 hours or lower, and preferably 2 hours or higher and 20 hours or lower.

[0352] The hydroxide 95 obtained by the above process can be represented as Co 1-y Ni y (OH)2, also known as nickel cobalt hydroxide. The hydroxide 95 may be a single particle or a secondary particle, preferably with a large grain size.

[0353] <Lithium Source>

[0354] As Figure 7 and Figure 8 The lithium source 88 shown (denoted as Li source in the drawings) prepares a lithium compound.

[0355] As a lithium compound, lithium hydroxide, lithium carbonate, lithium oxide or lithium nitrate is prepared. In the positive electrode active material, the atomic number ratio of lithium (Li) relative to the atomic number ratio of cobalt (Co) (referred to as Li / Co) is preferably 0.9 or more and 1.2 or less, more preferably 1.0 or more and 1.09 or less. The lithium compound is weighed in a manner that satisfies the above range. When a reduced hydroxide 95 is obtained using water or hydroxyl groups, Li / Co becomes an appropriate value, so it is preferred.

[0356] The lithium compound is preferably crushed. For example, the crushing is performed using a mortar for more than 5 minutes and less than 15 minutes. The mortar is preferably made of a material that does not easily release impurities. Specifically, it is preferred to use an aluminum oxide (hereinafter referred to as alumina) mortar with a purity of more than 90%, preferably more than 99%. In addition, a wet crushing method using a ball mill or the like can also be used. In the wet crushing method, acetone or dehydrated acetone can be used as a solvent, and the rotation speed is more than 200 rpm and less than 400 rpm, and the crushing is preferably performed for more than 10 hours and less than 15 hours. In addition, a sieve can also be used to screen the crushed lithium compound.

[0357] <Step S51>

[0358] illustrate Figure 7 and Figure 8 Step S51 is shown. In step S51, hydroxide 95 and lithium source 88 are mixed. Then, a mixed mixture 96 is obtained. As a means for mixing hydroxide 95 and lithium source 88, an automatic mortar or a revolving and rotating stirring device is preferably used.

[0359] When the hydroxide 95 and the lithium source 88 are mixed and crushed at the same time, a ball mill or a sand mill is preferably used as a medium. Alumina balls or zirconia balls can be used as the ball mill or the sand mill. When a ball mill or a sand mill is used, the medium is subjected to centrifugal force so that micronization can be achieved. Note that when there is a concern about contamination from the medium, etc., it is preferred to use the above-mentioned zirconia balls and set the peripheral speed to be greater than 100 mm / second and less than 2000 mm / second.

[0360] As a pulverization method that can be used when mixing and pulverizing are performed simultaneously, dry pulverization and wet pulverization can be mentioned. Dry pulverization is a method of pulverizing in an inert gas or air, and can pulverize to a particle size of 3.5 μm or less, preferably 3 μm or less. Wet pulverization is a method of pulverizing in a liquid, and can pulverize to a particle size of 1 μm or less. That is, wet pulverization is preferably used when reducing the particle size.

[0361] In this way, a mixture 96 was obtained.

[0362] <Step S52>

[0363] Reference Figure 7 Step S52 and step S53 shown are supplementary explanations of the heating process.

[0364] Next, explain Figure 7 The heating process may be performed multiple times. In step S52, heating is performed at a temperature of 400°C or higher and 800°C or lower before step S54 described later. Since step S52 is performed at a lower temperature than step S54, it is sometimes referred to as pre-baking. Sometimes, gas components contained in hydroxide 95 or lithium source 88 are released by step S52. By using a material from which gas components are released, oxide 98 with less impurities can be obtained. However, if Figure 8 As shown, oxide 98 can be obtained even without performing the pre-baking of step S52.

[0365] The heating atmosphere in step S52 is preferably an atmosphere containing oxygen or so-called dry air and an oxygen-containing atmosphere with less water (for example, a dew point of -50°C or less, more preferably -80°C or less).

[0366] For example, when heating is performed at 700°C for 10 hours, the heating rate is preferably 100°C / hour or more and 20.0°C / hour or less. In addition, the flow rate of dry air that can form a dry atmosphere is preferably 3L / min or more and 10L / min or less. The cooling time from the specified temperature to room temperature is preferably 10 hours or more and 50 hours or less, and the cooling rate can be calculated from the cooling time, etc.

[0367] The crucible, shell, setter or container used for heating is preferably made of a material that does not easily release impurities. For example, a 99.9% pure alumina crucible is preferably used. In mass production, a shell made of mullite-cordierite (Al2O3, SiO2, MgO) is preferably used.

[0368] <Step S53>

[0369] Next, explain Figure 7 Step S53 is shown. In step S53, a grinding process is performed. For example, it is preferred to use a sieve with a pore size of 40 μm or more and 60 μm or less for classification. However, if Figure 8 As shown, oxide 98 can be obtained even without performing the grinding process of step S53.

[0370] <Step S54>

[0371] Next, explain Figure 7 and Figure 8 Step S54 is shown. In step S54, the mixture obtained through the grinding process of step S53 is heated. This step S54 is sometimes referred to as main roasting. In order to distinguish it from step S52, etc., it is sometimes appropriately numbered and referred to as first heating, second heating, etc.

[0372] In step S54, the heating temperature is preferably 700° C. or higher and lower than 1200° C., more preferably 800° C. or higher and lower than 1100° C., and further preferably 900° C. or higher and lower than 1000° C. When the oxide 98 is produced by this heat treatment, the heating is performed at a temperature at which at least the hydroxide 95 and the lithium source 88 diffuse into each other.

[0373] The heating time in step S54 may be, for example, not less than 1 hour and not more than 100 hours, and preferably not less than 2 hours and not more than 20 hours.

[0374] The heating atmosphere in step S54 is preferably an atmosphere containing oxygen or so-called dry air and an oxygen-containing atmosphere with less water (for example, a dew point of -50°C or lower, more preferably -80°C or lower).

[0375] For example, when heating is performed at 750°C for 10 hours, the heating rate is preferably 150°C / hour or more and 250°C / hour or less. In addition, the flow rate of dry air that can form a dry atmosphere is preferably 3L / min or more and 10L / min or less. The cooling time from the specified temperature to room temperature is preferably 10 hours or more and 50 hours or less, and the cooling rate can be calculated from the cooling time, etc.

[0376] The crucible, shell, setter or container used for heating is preferably made of a material that does not easily release impurities. For example, a 99.9% pure alumina crucible is preferably used. In mass production, a shell made of mullite-cordierite (Al2O3, SiO2, MgO) is preferably used.

[0377] Furthermore, when recovering the heated material, it is preferred that the heated material is first moved from the crucible to the mortar and then recovered so that impurities are not mixed into the material. In addition, the mortar is also preferably made of a material that does not easily release impurities, and specifically, it is preferred to use an alumina or zirconia mortar with a purity of 90% or more, preferably 99% or more.

[0378] <Step S55>

[0379] illustrate Figure 7 Step S55 is shown. In step S55, a grinding process is performed. For example, it is preferred to use a sieve with a pore size of 40 μm or more and 60 μm or less for classification. However, if Figure 8 As shown, oxide 98 can be obtained even without performing the grinding process of step S55.

[0380] <Compound Oxide>

[0381] right Figure 7 and Figure 8 The oxide 98 shown will be described. The oxide 98 is formed at least through the heating in step S54 and is sometimes called a composite oxide. In addition, the oxide 98 can also be used as the positive electrode active material 100.

[0382] <Add element source>

[0383] illustrate Figure 7 and Figure 8 The additive element source 89 is shown. The additive element source 89 is preferably a compound of one or more selected from magnesium, aluminum, calcium, zirconium, fluorine, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine and beryllium.

[0384] When the additive element is magnesium, the additive element source 89 can be recorded as a magnesium source. A compound containing magnesium is used as the magnesium source. As the compound containing magnesium, for example, magnesium fluoride, magnesium oxide, magnesium hydroxide, or magnesium carbonate can be used. In addition, a plurality of the above magnesium sources can also be used.

[0385] When the added element is fluorine, the added element source 89 can be recorded as a fluorine source. As the fluorine source, a compound containing fluorine is used. As a compound containing fluorine, for example, lithium fluoride, magnesium fluoride, aluminum fluoride, titanium fluoride, cobalt fluoride, nickel fluoride, zirconium fluoride, vanadium fluoride, manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride, calcium fluoride, sodium fluoride, potassium fluoride, barium fluoride, cerium fluoride, lanthanum fluoride or sodium aluminum hexafluoride can be used. Among them, lithium fluoride has a relatively low melting point, i.e., 848°C, and is easily melted in the heating step described later, so it is preferred.

[0386] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can be used as both a fluorine source and a lithium source.

[0387] The fluorine source may be a gas, or fluorine, carbon fluoride, sulfur fluoride, or oxygen fluoride may be used and mixed in the atmosphere in the heating step described later.

[0388] When preparing the additive element source 89, two or more additive elements may be used. For example, when lithium fluoride and magnesium fluoride are used as the additive element source 89, the molar ratio of lithium fluoride to magnesium fluoride is preferably LiF:MgF2=x:1 (0≤x≤1.9), more preferably LiF:MgF2=x:1 (0.1≤x≤0.5), and further preferably LiF:MgF2=x:1 (x=0.33 or its vicinity). In addition, near a certain value refers to a value greater than 0.9 times the value and less than 1.1 times the value.

[0389] When two or more additional element sources 89 are used, it is preferred to mix these additional element sources 89 first. There are the following methods for mixing: a method of mixing while pulverizing the raw materials; and a method of mixing without pulverizing. When two or more additional element sources 89 are mixed first, it is preferred to mix while pulverizing. This is because the particle size in the additional element source 89 can be made uniform and the particle size can be made small.

[0390] Furthermore, when the additive element source 89 is recovered after mixing or the like, it may be classified using a sieve having an aperture of 250 μm or more and 350 μm or less. Thus, the particle size can be made uniform.

[0391] As a method of mixing while pulverizing, dry pulverizing or wet pulverizing can be cited. Compared with the dry pulverizing method, the wet pulverizing method can further reduce the particle size, so it is preferred. When performing wet pulverizing, a solvent is prepared. As a solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. As a solvent, dehydrated acetone with a purity of 99.5% or more is preferably used. By using dehydrated acetone of the above purity, impurities that may be mixed in can be reduced.

[0392] In the method of mixing while crushing, a medium such as a ball mill or a sand mill can be used. As the medium of the ball mill and the sand mill, an alumina ball or a zirconia ball can be used. In the ball mill and the sand mill, the medium is added with centrifugal force so that micronization can be achieved. Note that when there is a concern about contamination from the medium, etc., it is preferred to use the above-mentioned zirconia ball and set the peripheral speed to be more than 100 mm / second and less than 2000 mm / second.

[0393] In the above, an example in which two types of additional element sources 89 are prepared is shown, but the additional element source 89 may be a mixture of one type or three or more types.

[0394] As a method for introducing the additive element into the oxide 98, a solid phase method, a liquid phase method such as a sol-gel method, a sputtering method, a vapor deposition method, a CVD (chemical vapor deposition) method, or a PLD (pulsed laser deposition) method can be used. In this embodiment, a case where a solid phase method is used is described.

[0395] <Step S71>

[0396] exist Figure 7 and Figure 8 In step S71 shown, the element source 89 and the oxide 98 are mixed and added. Then, the mixture 99 is formed. The mixing can be dry mixing or wet mixing. During the mixing, the rotation speed is preferably set to 100 rpm or more and 200 rpm or less to prevent the oxide 98 from being damaged.

[0397] <Step S72>

[0398] illustrate Figure 7 and Figure 8 Step S72 is shown. In step S72, the mixture 99 is heated.

[0399] Here, the heating temperature is supplemented. The heating temperature of step S72 needs to be above the temperature at which the reaction of the oxide 98 and the additive element source 89 progresses. The temperature at which the reaction progresses can be the temperature at which the oxide 98 and the additive element source 89 diffuse mutually, and can also be lower than the melting temperature of the above materials. Taking the oxide as an example, it can be seen that from the melting temperature T m 0.757 times the temperature (Taman temperature T d ) begin to diffuse mutually. Therefore, the heating temperature of step S72 may be 500° C. or higher.

[0400] Of course, it is preferable that the temperature is higher than the temperature at which the oxide 98 and part of the additive element source 89 are melted, because the reaction is easy to progress. For example, when LiF and MgF2 are included as the additive element source 89, the heating in step S72 is preferably performed at 700° C. or higher. In particular, the eutectic point of LiF and MgF2 is around 742° C., so the heating in step S72 is preferably performed at 742° C. or higher.

[0401] A higher heating temperature is preferred because the reaction easily proceeds, the heating time is shortened, and the productivity is improved.

[0402] Note that the heating temperature is set to a temperature lower than the decomposition temperature of the oxide 98. That is, the heating temperature in step S72 is preferably lower than the heating temperature in step S52. In addition, the heating temperature in step S72 is preferably lower than the heating temperature in step S54. At a temperature near the decomposition temperature, a trace amount of the oxide 98 may be decomposed. The melting point of lithium cobalt oxide is 1130°C. From about 1000°C before that, lithium evaporation or cation mixing of lithium and cobalt is likely to occur. The heating temperature is more preferably below 1000°C, more preferably below 950°C, and even more preferably below 900°C.

[0403] In summary, the heating temperature of step S72 is preferably 500°C or higher and lower than 1130°C, more preferably 700°C or higher and 1000°C or lower, further preferably 700°C or higher and 950°C or lower, and further preferably 700°C or higher and 900°C or lower. In addition, it is preferably 742°C or higher and 1130°C or lower, more preferably 742°C or higher and 1000°C or lower, further preferably 742°C or higher and 950°C or lower, and further preferably 742°C or higher and 900°C or lower. In addition, it is preferably 800°C or higher and 1130°C or lower, more preferably 830°C or higher and 1130°C or lower, further preferably 830°C or higher and 1000°C or lower, further preferably 830°C or higher and 950°C or lower, and further preferably 830°C or higher and 900°C or lower.

[0404] When the mixture 99 is heated, it is preferable to control the partial pressure of fluorine or fluoride derived from the fluorine source or the like in the heating environment to be within an appropriate range.

[0405] In this manufacturing method, LiF as a fluorine source is sometimes used as a flux. This function can be used to reduce the heating temperature of step S72 to a temperature lower than the decomposition temperature of the oxide 98, for example, to a temperature above 742°C and below 950°C, and the additive element source can also be uniformly diffused in the surface layer. As a result, the positive electrode active material 100 containing the additive element in the surface layer can be manufactured.

[0406] However, the specific gravity of LiF in the gas state is lighter than that of oxygen, so it is possible that LiF is sublimated by heating, and the sublimation causes a decrease in LiF in the mixture 99. At this time, the function of LiF as a flux is reduced. Therefore, it is necessary to suppress the sublimation of LiF while heating. Note that even if LiF is not used as a fluorine source, it is possible that Li on the surface of the oxide 98 reacts with F of a fluorine source other than LiF, and LiF is generated and sublimated. Therefore, even if a fluoride having a higher melting point than LiF is used as a fluorine source other than LiF, it is also necessary to suppress sublimation.

[0407] As a method for suppressing sublimation, there is a method of heating the mixture 99 in an atmosphere containing F. This method is a method of making the atmosphere in the heating furnace for heating the mixture 99 a state where the partial pressure of LiF is high. As another method, there is a method of covering the reaction container in which the mixture 99 is placed. By the above method and the like, the sublimation of LiF in the mixture 99, that is, the reduction of LiF, can be suppressed.

[0408] The heating in step S72 can be performed using a roller hearth kiln. The roller hearth kiln can heat the mixture 99 while moving it in the kiln in a state where a lid is placed on the container containing the mixture 99. By covering the container, the mixture 99 can be heated in an atmosphere containing LiF, thereby suppressing the sublimation of LiF in the mixture 99, that is, reducing the amount of LiF.

[0409] In addition, a rotary kiln may be used for heating in step S72. The atmosphere in the rotary kiln contains oxygen, and it is preferred to heat while controlling the oxygen flow rate. In order to suppress the sublimation of LiF in the mixture 99, that is, to reduce it, it is preferred to reduce the oxygen flow rate. As a method for reducing the oxygen flow rate, there is a method such as first introducing oxygen into the kiln and maintaining it for a certain period of time, and then not introducing oxygen.

[0410] It is considered that the above-mentioned steps can provide the positive electrode active material 100 having a smooth surface and few irregularities.

[0411] <Step S73>

[0412] illustrate Figure 7 Step S73 shown in FIG. 1 is a step of grinding. For example, it is preferred to use a sieve with a pore size of 40 μm or more and 60 μm or less for classification. This can prevent particles from sticking together. However, if Figure 8 In this way, the positive electrode active material 100 can be obtained without performing the grinding process of step S73.

[0413] The positive electrode active material 100 can be manufactured based on the above. The positive electrode active material 100 can reflect the shape of the hydroxide 95 as a precursor. In addition, according to the above manufacturing method, lithium cobalt oxide in which nickel is still present can be obtained. Nickel that cannot be dissolved in the solid layer sometimes diffuses to the surface layer of the lithium cobalt oxide. In addition, lithium cobalt oxide in which the added element remains in the surface layer can be obtained. The added element is preferably dissolved in the lithium cobalt oxide in the surface layer.

[0414] In addition, the lithium cobalt oxide has fewer impurities, so it is preferred. Note that when a sulfide is used as a starting material, sulfur is sometimes detected from the lithium cobalt oxide. The sulfur concentration can be measured by elemental analysis of the entire particle of the positive electrode active material by GD-MS, ICP-MS, etc.

[0415] This embodiment mode can be used in combination with other embodiment modes or examples.

[0416] (Implementation 3)

[0417] In this embodiment, an example of a secondary battery which is one embodiment of the present invention is described with reference to FIG. 9 .

[0418] <Structural Example 1 of Secondary Battery>

[0419] Hereinafter, a secondary battery in which a positive electrode, a negative electrode, and an electrolyte solution are accommodated in an outer package will be described as an example.

[0420] [positive electrode]

[0421] Fig.9A An example of a cross-sectional view of a positive electrode 503 used in a secondary battery 500 described later is shown. The positive electrode 503 includes a positive electrode active material layer 502 on a positive electrode current collector 501. The positive electrode active material layer 502 includes a positive electrode active material 100, a positive electrode active material 562, a conductive material 553, a conductive material 554, and an electrolyte 530. The positive electrode active material layer 502 further includes a binder (not shown). The secondary battery may also have a structure of either the conductive material 553 or the conductive material 554.

[0422] The median particle size (D50) of the positive electrode active material 100 is greater than 1 μm and less than 50 μm, preferably greater than 5 μm and less than 30 μm. In order to increase the packing density, it is preferred to add a positive electrode active material 562 having a different median particle size (D50). The median particle size (D50) of the positive electrode active material 562 is preferably greater than 1 / 10 and less than 1 / 6 of the median particle size (D50) of the positive electrode active material 100. When the particle size distribution of the active material mixed with the positive electrode active material 100 and the positive electrode active material 562 is measured, two peaks with different maxima are confirmed. Of course, more than two peaks can also be confirmed. In addition, the packing density can be increased even if the positive electrode active material 562 is not included.

[0423] Both the positive electrode active material 100 and the positive electrode active material 562 preferably include a shell. The positive electrode active material including a shell can improve insulation and is less likely to cause thermal runaway. Fig.9A Although the boundary between the surface and the interior is marked with a dotted line, the boundary is not necessarily Fig.9A So clear.

[0424] The active material of the positive electrode active material 100 may be the same as or different from the active material of the positive electrode active material 562. The same active material includes materials with the same main raw material of the active material, which may or may not have added elements, etc. Different active material includes materials with different main raw materials of the active material.

[0425] Although it has been described, the positive electrode active material 100 and the positive electrode active material 562 preferably contain an added element. The added element can be distributed in a concentrated manner or distributed in the interior at a low concentration. Concentrated distribution means that the added element is unevenly distributed or exists in a biased manner. Therefore, sometimes the state in which the concentration of the added element increases from the interior to the shell is referred to as the added element being concentratedly distributed in the shell. Concentrated distribution can also be recorded as segregation.

[0426] The added element may also be included in the surface portion. Preferably, there is a concentration difference between the concentration of the added element in the surface portion and the concentration of the added element in the interior, and the concentration of the added element in the surface portion is preferably higher than the concentration in the interior. This is sometimes referred to as the added element being concentratedly distributed in the surface portion. Concentrated distribution may also be referred to as segregation or precipitation.

[0427] The positive electrode active material 100 and the positive electrode active material 562 are sometimes referred to as positive electrode active material particles, but the positive electrode active material has various shapes other than particle shape. Fig. 9B Shown contains with Fig.9A The positive electrode 503 has a positive electrode active material in a shape other than a particle shape. Fig. 9B In addition to the shape of the positive electrode active material Fig.9A Likewise, the description is therefore omitted.

[0428] Although Fig.9A and Fig. 9B The positive electrode active material 100 and the positive electrode active material 562 are shown as primary particles, but may be secondary particles.

[0429] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and may also include a conductive material (synonymous with a conductive aid) and a binder. As the positive electrode active material, a positive electrode active material manufactured by the manufacturing method described in the above embodiment can be used, for example, a positive electrode active material with a relatively small median particle size (D50) and a positive electrode active material with a relatively large median particle size (D50) can also be mixed and used.

[0430] Furthermore, the positive electrode active material of one embodiment of the present invention may be mixed with other positive electrode active materials for use.

[0431] As other positive electrode active materials, there are composite oxides having an olivine crystal structure, a layered rock salt crystal structure or a spinel crystal structure, etc. For example, compounds such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2 can be cited.

[0432] In addition, as other positive electrode active materials, it is preferable to mix lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 < x < 1) (M = Co, Al, etc.)) in a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4. By adopting this structure, the characteristics of the secondary battery can be improved.

[0433] In addition, as other positive electrode active materials, a lithium manganese composite oxide represented by the composition formula Li a Mn b M c O d can be used. Here, the element M is preferably a metal element selected from metal elements other than lithium and manganese, or silicon or phosphorus, and more preferably nickel. In addition, when measuring the entire particle of the lithium manganese composite oxide, it is preferable that 0 < a / (b + c) < 2, c > 0, and 0.26 ≤ (b + c) / d < 0.5 are satisfied during discharging (note that a, b, c, and d are not 0). The composition of metals, silicon, phosphorus, etc. of the entire particle of the lithium manganese composite oxide can be measured, for example, by ICP-MS (inductively coupled plasma mass spectrometry). In addition, the composition of oxygen of the entire lithium manganese composite oxide can be measured, for example, by EDX. In addition, it can also be calculated by using valence evaluation of fusion gas analysis and XAFS (X-ray absorption fine structure) analysis together with ICP-MS analysis. Note that the lithium manganese composite oxide refers to an oxide containing at least lithium and manganese, and may also contain one or more elements selected from the group consisting of chromium, cobalt, aluminum, nickel, iron, magnesium, molybdenum, zinc, indium, gallium, copper, titanium, niobium, silicon, and phosphorus.

[0434] [Conductive Material]

[0435] The conductive material serves to assist the current path between the active material and the current collector or the current path between multiple active materials, etc. To serve this purpose, the conductive material preferably contains a material having a lower resistance than the active material. The conductive material is sometimes referred to as a conductive aid or a conductivity imparting agent depending on its function.

[0436] Typically, carbon materials or metal materials are used as the conductive material. The conductive material is in particle form, and carbon black (furnace black, acetylene black, graphite, etc.) is used as the particle-shaped conductive material. There is a lot of carbon black having a smaller particle size than the positive electrode active material. The conductive material is in fibrous form, and carbon nanotubes (CNT), VGCF (registered trademark) are used as the fibrous conductive aids. There is also a flaky conductive material, for example, multilayer graphene is used as the flaky conductive aid. In the cross-section of the positive electrode, the flaky conductive aid is sometimes observed as a line.

[0437] The particle-shaped conductive material can enter the gap between the positive electrode active material and the like and easily aggregate. Therefore, the particle-shaped conductive material can assist the conductive path between the positive electrode active materials arranged near the particle-shaped conductive material. Although it has a bending area, the fibrous conductive material is larger than the positive electrode active material. Therefore, the fibrous conductive material can assist the conductive path between the separated positive electrode active materials in addition to the adjacent positive electrode active materials. In this way, the shape of the conductive auxiliary agent preferably mixed is two or more.

[0438] When multilayer graphene is used as a thin sheet-like conductive material and carbon black is used as a particulate conductive auxiliary material, the weight of the carbon black in a slurry mixed with them is preferably 1.5 times or more and 20 times or less, and more preferably 2 times or more and 9.5 times or less.

[0439] When the mixing ratio of multilayer graphene and carbon black is set to the above range, carbon black does not aggregate and is easily dispersed. In addition, when the mixing ratio of multilayer graphene and carbon black is set to the above range, the electrode density can be increased compared to the case where only carbon black is used as a conductive additive. By increasing the electrode density, the capacity per unit weight can be increased.

[0440] Furthermore, by setting the mixing ratio of multilayer graphene and carbon black to the above range, rapid charging can be achieved.

[0441] In this specification, graphene includes multi-layer graphene and multi-graphene. In other words, graphene refers to a compound containing carbon and having a two-dimensional structure formed by a six-membered ring of carbon atoms in a flat plate, a thin sheet, etc. In addition, the two-dimensional structure formed by the six-membered ring composed of carbon atoms is sometimes referred to as a carbon sheet. Graphene compounds include graphene oxide, multi-layer graphene oxide, multi-graphene oxide, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-graphene oxide, graphene quantum dots, etc. In other words, graphene compounds may also have functional groups. In addition, graphene or graphene compounds preferably have a curved shape. In addition, graphene or graphene compounds may also be curled, and curled graphene is sometimes referred to as carbon nanofiber.

[0442] In this specification and the like, graphene oxide refers to a graphene compound containing carbon and oxygen, having a flaky shape, and including a functional group, particularly including an epoxy group, a carboxyl group, or a hydroxyl group.

[0443] In this specification, etc., reduced graphene oxide contains carbon and oxygen, has a flaky shape, and has a two-dimensional structure formed by a six-membered ring composed of carbon atoms. One layer of reduced graphene oxide can function, but a stacked structure can also be used. The reduced graphene oxide preferably has a portion with a carbon concentration greater than 80 atomic% and an oxygen concentration of 2 atomic% or more and 15 atomic% or less. By having this carbon concentration and oxygen concentration, a small amount of reduced graphene oxide can also have the function of a conductive material with high conductivity. In addition, it is preferred that the intensity ratio G / D of the G band to the D band of the Raman spectrum of the reduced graphene oxide is greater than 1. Reduced graphene oxide having this intensity ratio can have the function of a conductive material with high conductivity even in a small amount.

[0444] Fluorine-containing graphene can also be used as a graphene compound. The fluorine in the graphene compound is preferably adsorbed on the surface. Fluorine-containing graphene can be manufactured by contacting graphene with a fluorine compound (called fluorination treatment). Fluorine (F2) or a fluorine compound is preferably used in the fluorination treatment. As the fluorine compound, hydrogen fluoride, halogen fluoride (ClF3, IF5, etc.), gaseous fluorides (BF3, NF3, PF5, SiF4, SF6, etc.), metal fluorides (LiF, NiF2, AlF3, MgF2, etc.) and the like are preferably used. In the fluorination treatment, a gaseous fluoride is preferably used, and the gaseous fluoride can also be diluted with an inert gas. The temperature of the fluorination treatment is preferably room temperature, preferably above 0°C and below 250°C including the room temperature. By performing the fluorination treatment at a temperature above 0°C, fluorine can be adsorbed on the surface of the graphene.

[0445] Graphene compounds sometimes have excellent electrical properties such as high conductivity and excellent physical properties such as high flexibility and high mechanical strength. In addition, graphene compounds have a flake shape. Graphene compounds sometimes have a curved surface, which can achieve surface contact with low contact resistance. Graphene compounds sometimes have very high conductivity even if they are thin, so a conductive path can be formed in the active material layer with a small amount and high efficiency. Therefore, by using graphene compounds as conductive materials, the contact area between the active material and the conductive material can be increased. The graphene compound preferably covers more than 80% of the area of ​​the active material. Note that it is preferred that the graphene compound clings to at least a portion of the active material particles. It is preferred that the graphene compound covers at least a portion of the active material particles. It is preferred that the shape of the graphene compound is consistent with at least a portion of the shape of the active material particles. The shape of the active material particle refers to, for example, a concave-convex surface such as a single active material particle or a concave-convex surface formed by a plurality of active material particles. It is preferred that the graphene compound surrounds at least a portion of the active material particles. The graphene compound may have holes.

[0446] When using active material particles with a small particle size, for example, when using active material particles with a particle size of 1 μm or less, the specific surface area of ​​the active material particles is large, so more conductive paths connecting the active material particles are required. In this case, it is preferred to use a graphene compound that can efficiently form a conductive path even in a small amount.

[0447] Due to the above properties, it is particularly effective to use graphene compounds as conductive materials for secondary batteries that require rapid charging and rapid discharging. For example, two-wheeled or four-wheeled vehicle-mounted secondary batteries, drone secondary batteries, etc. sometimes require rapid charging and rapid discharging. Mobile electronic devices, etc. sometimes need to have rapid charging characteristics. Rapid charging and discharging, for example, refers to charging and discharging of 200mA / g, 400mA / g or 1000mA / g or more.

[0448] Preferably, the flake-shaped graphene or graphene compound is uniformly dispersed in the active material layer. Since the plurality of graphene or graphene compounds are formed in a manner of covering a portion of the plurality of active materials or in a manner of being attached to the surface of the plurality of granular active materials, the plurality of graphene or graphene compounds are in surface contact with the plurality of active materials.

[0449] Here, by combining a plurality of graphene or graphene compounds with each other, a meshed graphene compound sheet (hereinafter referred to as a graphene compound net or graphene net) can be formed. When the graphene net covers the active material, the graphene net can be used as an adhesive for combining the active materials with each other. Therefore, the amount of the adhesive can be reduced or the adhesive can be omitted, thereby increasing the ratio of the active material in the electrode volume and the electrode weight. In other words, the discharge capacity of the secondary battery can be increased.

[0450] Here, it is preferred that graphene oxide is used as graphene or graphene compound, the graphene oxide is mixed with an active material to form an active material layer, and then reduced. That is, the completed active material layer preferably contains reduced graphene oxide. By using highly dispersible graphene oxide in a polar solvent in the formation of graphene or graphene compound, graphene or graphene compound can be dispersed roughly uniformly inside the active material layer. The solvent is volatilized and removed from the dispersion medium containing uniformly dispersed graphene oxide, and the graphene oxide is reduced, so that the graphene or graphene compound remaining in the active material layer partially overlap each other and are dispersed in a manner of forming surface contact, thereby forming a three-dimensional conductive path. In addition, as the reduction of graphene oxide, it can be carried out by heat treatment or using a reducing agent.

[0451] Therefore, unlike granular conductive materials such as acetylene black that form point contact with active materials, graphene or graphene compounds can form surface contact with low contact resistance, so the conductivity between active materials and graphene or graphene compounds can be improved compared to general conductive materials.

[0452] In addition, by using a spray drying device in advance, a graphene compound serving as a conductive material of a covering portion can be formed so as to cover the entire surface of the active material, and a conductive path can be formed between the active materials using the graphene compound.

[0453] In addition, a material used in forming the graphene compound may be mixed with the graphene compound and used in the active material layer. For example, particles used as a catalyst in forming the graphene compound may be mixed with the graphene compound. Examples of catalysts used in forming the graphene compound include silicon oxide (SiO2, SiO x (x<2)), particles of aluminum oxide, iron, nickel, ruthenium, iridium, platinum, copper, germanium, etc. The median particle size (D50) of the particles is preferably 1 μm or less, more preferably 100 nm or less.

[0454] As a conductive material, acetylene black (denoted as AB) can be used in addition to graphene. Fluorine-containing acetylene black can also be used. The fluorine in the fluorine-containing acetylene black is preferably adsorbed on the surface. Alternatively, the fluorine-containing acetylene black can be produced by contacting acetylene black with a fluorine compound (also called fluorination treatment). As for the fluorination treatment, the relevant description of graphene can be applied to acetylene black.

[0455] As the conductive material, in addition to graphene and acetylene black, carbon fiber materials (referred to as carbon nanotubes or CNTs) can also be used. Furthermore, fluorine-containing carbon nanotubes can also be used. The fluorine in the fluorine-containing carbon nanotubes is preferably adsorbed on the surface. In addition, the fluorine-containing carbon nanotubes can be manufactured by contacting the carbon nanotubes with a fluorine compound (referred to as fluorination treatment). As for the fluorination treatment, the relevant description when graphene can be used for carbon nanotubes.

[0456] [Adhesive]

[0457] The binder is required to strengthen the adhesion of the active material in the powder state without covering the surface of the active material. Furthermore, the binder needs to be adhesive to the current collector. That is, the binder preferably contains a material showing an adhesive component. In addition, considering the expansion of the active material, the binder preferably has sufficient flexibility and preferably responds to the state change of the active material. In addition, the binder also needs to be compatible with the electrolyte. In addition, violent oxidation reactions and reduction reactions occur in secondary batteries, so an adhesive that does not deteriorate or has low reactivity relative to the reaction is required.

[0458] As the adhesive, for example, preferably used are rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Fluorine rubber can also be used as the adhesive.

[0459] In addition, as a binder, for example, a water-soluble polymer is preferably used. As a water-soluble polymer, for example, polysaccharides can also be used. As polysaccharides, one or more of cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, and starch can be used. It is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0460] Alternatively, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0461] As the binder, a plurality of the above-mentioned materials may be used in combination.

[0462] For example, materials with particularly good viscosity regulating effects can also be used in combination with other materials. For example, although rubber materials and the like have high cohesive force and / or high elasticity, it is sometimes difficult to regulate viscosity when mixed in a solvent. In such a case, for example, it is preferably mixed with materials with particularly good viscosity regulating effects. As materials with particularly good viscosity regulating effects, for example, water-soluble polymers are preferably used. In addition, as water-soluble polymers with particularly good viscosity regulating functions, the above-mentioned polysaccharides can be used, for example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose and diacetyl cellulose, regenerated cellulose, starch, etc. can be used.

[0463] Note that cellulose derivatives such as carboxymethyl cellulose, for example, can be easily effective as viscosity modifiers by increasing their solubility by converting them into salts such as sodium salts and ammonium salts of carboxymethyl cellulose. Due to the increased solubility, the dispersibility of active materials and other components can be improved when forming electrode slurry. In this specification, cellulose and cellulose derivatives used as binders for electrodes include their salts.

[0464] By dissolving a water-soluble polymer in water to stabilize its viscosity, the active material and other materials used as a binder combination, such as styrene-butadiene rubber, can be stably dispersed in an aqueous solution. Since the water-soluble polymer has functional groups, it is expected to be easily and stably adsorbed on the surface of the active material. Most cellulose derivatives such as carboxymethyl cellulose have functional groups such as hydroxyl and carboxyl. Because of the functional groups, the polymer is expected to interact with each other and widely cover the surface of the active material.

[0465] When the binder covering or contacting the surface of the active material forms a film, it is also expected to be used as a passivation film to produce an effect of inhibiting the decomposition of the electrolyte. Here, the passivation film is a film that has no conductivity or extremely low conductivity. For example, when the passivation film is formed on the surface of the active material, it inhibits the decomposition of the electrolyte at the battery reaction potential. More preferably, the passivation film can transmit lithium ions while inhibiting conductivity.

[0466] [current collector]

[0467] As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0468] 〔negative electrode〕

[0469] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may also include a conductive material and a binder.

[0470] [Negative electrode active material]

[0471] As the negative electrode active material, for example, an alloy material and / or a carbon material can be used.

[0472] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing one or more selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The charge and discharge capacity of this element is larger than that of carbon, especially the theoretical capacity of silicon is large, that is, the unit weight of the active material is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Here, an element capable of performing a charge-discharge reaction through an alloying / de-alloying reaction with lithium, a compound containing the element, and the like are sometimes referred to as an alloy-based material.

[0473] In this specification, SiO refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value near 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less. Alternatively, x is preferably 0.2 or more and 1.2 or less. Alternatively, x is preferably 0.3 or more and 1.5 or less.

[0474] As the carbon-based material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon nanotube, graphene, carbon black, and the like can be used.

[0475] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0476] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion secondary batteries can show high operating voltages. Graphite also has the following advantages: large charge and discharge capacity per unit volume; small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0477] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), etc.

[0478] In addition, as the negative electrode active material, Li 3 N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N shows a large charge and discharge capacity (active material unit weight 900 mAh / g), and is therefore preferred.

[0479] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, so the negative electrode active material can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, so it is preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0480] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorine compounds such as FeF3, BiF3.

[0481] As the conductive material and the binder which may be contained in the negative electrode active material layer, the same conductive material and the binder which may be contained in the positive electrode active material layer may be used.

[0482] [Negative electrode current collector]

[0483] As the negative electrode current collector, the same material as the positive electrode current collector can be used. In addition, as the negative electrode current collector, a material that does not alloy with carrier ions such as lithium is preferably used.

[0484] 〔Electrolyte〕

[0485] The electrolyte contains a solvent and a lithium salt. As the solvent of the electrolyte, an aprotic organic solvent is preferably used. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc. can be used, or two or more of the above can be used in any combination and proportion.

[0486] When the electrolyte contains ethylene carbonate (EC) and diethyl carbonate (DEC), in a state where the total content of ethylene carbonate and diethyl carbonate is 100 vol%, a mixed organic solvent with a volume ratio of ethylene carbonate to diethyl carbonate of x:100 - x (note that 20 ≤ x ≤ 40) can be used. More specifically, a mixed organic solvent containing EC and DEC in a volume ratio of EC:DEC = 30:70 (volume ratio) can be used.

[0487] In addition, when the electrolyte contains ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), in a state where the total content of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is 100 vol%, a mixed organic solvent with a volume ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate of x:y:100 - x - y (note that 5 ≤ x ≤ 35 and 0 < y < 65) can be used. More specifically, a mixed organic solvent containing EC, EMC, and DMC in a volume ratio of EC:EMC:DMC = 30:35:35 (volume ratio) can be used.

[0488] In addition, as the electrolyte, a mixed organic solvent containing a fluorinated cyclic carbonate or a fluorinated chain carbonate can be used. And the above mixed organic solvent preferably contains both a fluorinated cyclic carbonate and a fluorinated chain carbonate at the same time. Both the fluorinated cyclic carbonate and the fluorinated chain carbonate have substituents with electron-withdrawing properties, so the solvation energy of lithium ions becomes low, so they are preferred. Therefore, both the fluorinated cyclic carbonate and the fluorinated chain carbonate are suitable for use in the electrolyte, and these mixed organic solvents are preferably used.

[0489] As fluorinated cyclic carbonate, for example, fluorinated ethylene carbonate (sometimes denoted as fluorinated ethylene carbonate, FEC, F1EC), difluoro ethylene carbonate (sometimes denoted as DFEC, F2EC), trifluoro ethylene carbonate (sometimes denoted as F3EC) or tetrafluoro ethylene carbonate (sometimes denoted as F4EC) etc. can be used. In addition, as DFEC, isomers such as cis-4,5, trans-4,5 can be enumerated. Any fluorinated cyclic carbonate has a substituent that exhibits electron-withdrawing property, so it is considered that the solvation energy of lithium ions is low. In FEC, the electron-withdrawing substituent is a F group.

[0490] As a fluorinated chain carbonate, there is methyl 3,3,3-trifluoropropionate. Methyl 3,3,3-trifluoropropionate is abbreviated as "MTFP". In MTFP, the electron-withdrawing substituent is a CF3 group.

[0491] FEC is one of the cyclic carbonates. Because it has a high relative dielectric constant, it has the effect of promoting the dissociation of lithium salts when used in an organic solvent. Furthermore, FEC has an electron-withdrawing substituent, so it can be said that the desolvation with lithium ions is easier to proceed than ethylene carbonate (EC) which does not have an electron-withdrawing substituent. Specifically, the solvation energy of lithium ions of FEC is smaller than that of EC which does not have an electron-withdrawing substituent. Therefore, lithium ions are easy to leave on the surface of the positive electrode active material and the surface of the negative electrode active material, thereby reducing the internal resistance of the secondary battery. Furthermore, the highest occupied molecular orbital (HOMO: Highest Occupied Molecular Orbital) energy level of FEC is deep, so it is not easy to oxidize and improves the oxidation resistance. On the other hand, there is a concern about the high viscosity of FEC. Therefore, it is preferred to use a mixed organic solvent containing MTFP in addition to FEC for the electrolyte. MTFP is one of the chain carbonates, which can produce the effect of reducing the viscosity of the electrolyte or maintaining the viscosity at room temperature (typically 25°C) at low temperatures (typically 0°C). Furthermore, although the solvation energy of MTFP is smaller than that of methyl propionate (abbreviated as "MP") which does not have an electron-withdrawing substituent, MTFP can also form a solvation with lithium ions when used in an electrolyte solution.

[0492] It is preferred that the total content of the mixed organic solvent containing FEC and MTFP having such physical properties is 100 vol%, and the mixed organic solvent is used in a volume ratio of x:100-x (note, 5≤x≤30, preferably 10≤x≤20). In other words, it is preferred that the mixed organic solvent contains more MTFP than FEC.

[0493] In addition, by using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as the solvent of the electrolyte, even if the internal temperature rises due to the internal short circuit or overcharge of the secondary battery, the rupture and / or ignition of the secondary battery can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As the organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as the anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0494] [Lithium salt]

[0495] As the lithium salt (also referred to as electrolyte) dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, or two or more of the above can be used in any combination and proportion. Relative to the solvent, the lithium salt is preferably 0.5 mol / L or more and 3.0 mol / L or less. When using fluoride LiPF6, LiBF4, etc., the safety of the lithium ion secondary battery is improved.

[0496] As the above-mentioned electrolyte, it is preferred to use a highly purified electrolyte with a low content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter referred to as "impurities"). Specifically, the ratio of impurities to the weight of the electrolyte is preferably 1wt% or less, more preferably 0.1wt% or less, and further preferably 0.01wt% or less.

[0497] [additive]

[0498] In addition, additives such as vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile may be added to the electrolyte. The concentration of the added material may be set to, for example, 0.1wt% or more and 5wt% or less in the entire solvent. VC or LiBOB is particularly preferred because it is easy to form a good covering portion.

[0499] [Gel electrolyte]

[0500] As the gel electrolyte, a polymer gel obtained by swelling a polymer with an electrolyte may be used. In addition, by using a polymer gel electrolyte, a semi-solid electrolyte layer can be provided, and the safety against leakage is improved. Moreover, the secondary battery can be made thinner and lighter.

[0501] As the gelled polymer, silicone gel, acrylic acid gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. can be used.

[0502] As the polymer, for example, a polymer having a polyoxyalkylene structure such as polyethylene oxide (PEO), PVDF and polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. In addition, the formed polymer can also have a porous shape.

[0503] 〔Isolated Body〕

[0504] The secondary battery preferably includes a separator. The separator can be formed of, for example, paper, nonwoven fabric, glass fiber, ceramic, or synthetic fibers including nylon (polyamide), vinylon (polyvinyl alcohol-based fiber), polyester, acrylic resin, polyolefin, polyurethane, etc. The separator is preferably processed into a bag shape and arranged in a manner to surround either the positive electrode or the negative electrode.

[0505] The separator may also have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0506] By coating ceramic materials, the oxidation resistance is improved, thereby suppressing the degradation of the separator during high voltage charge and discharge, thereby improving the reliability of the secondary battery. By coating fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By coating polyamide materials (especially aromatic polyamide), the heat resistance is improved, thereby improving the safety of the secondary battery.

[0507] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0508] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the discharge capacity per unit volume of the secondary battery can be increased.

[0509] 〔Outer packaging〕

[0510] As the outer packaging body included in the secondary battery, for example, metal materials such as aluminum and / or resin materials can be used. In addition, a film-like outer packaging body can also be used. As the film, for example, the following three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as polyamide resin and polyester resin is also arranged on the metal film as the outer surface of the outer packaging body. Sometimes a three-layer structure film containing aluminum is called an aluminum laminated film.

[0511] <Structural Example 2 of Secondary Battery>

[0512] [Solid Electrolyte]

[0513] Solid electrolytes containing inorganic materials such as sulfides or oxides, solid electrolytes containing polymer materials such as PEO (polyethylene oxide), etc. can be used instead of electrolytes. When solid electrolytes are used, it is not necessary to set separators and / or spacers. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0514] Hereinafter, the structure of a secondary battery using a solid electrolyte layer will be described as an example of the structure of a secondary battery.

[0515] like Fig. 10A As shown, a secondary battery 400 according to one embodiment of the present invention includes a positive electrode 410 , a solid electrolyte layer 420 , and a negative electrode 430 .

[0516] The positive electrode 410 includes a positive electrode current collector 413 and a positive electrode active material layer 414. The positive electrode active material layer 414 includes a positive electrode active material 411 and a solid electrolyte 421. The positive electrode active material 411 is produced by the production method described in the above embodiment. In addition, the positive electrode active material layer 414 may also include a conductive agent and a binder.

[0517] The solid electrolyte layer 420 includes a solid electrolyte 421. The solid electrolyte layer 420 is located between the positive electrode 410 and the negative electrode 430, and does not include either the positive electrode active material 411 or the negative electrode active material 431.

[0518] The negative electrode 430 includes a negative electrode current collector 433 and a negative electrode active material layer 434. The negative electrode active material layer 434 includes a negative electrode active material 431 and a solid electrolyte 421. In addition, the negative electrode active material layer 434 may also include a conductive agent and a binder. In addition, when metallic lithium is used as the negative electrode 430, Fig. 10B As shown, it is also possible to use the negative electrode 430 that does not include the solid electrolyte 421. When metal lithium is used for the negative electrode 430, the energy density of the secondary battery 400 can be increased, which is preferable.

[0519] As the solid electrolyte 421 included in the solid electrolyte layer 420 , for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a halide-based solid electrolyte, or the like can be used.

[0520] Sulfide solid electrolytes include sulfur-silicon (Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, etc.), sulfide glass (70Li2S·30P2S5, 30Li2S·26B2S3·44LiI, 63Li2S·38SiS2·1Li3PO4, 57Li2S·36SiS2·5Li4SiO4, 50Li2S·50GeS2, etc.), sulfide crystal glass (Li7P3S 11 , Li 3.25 P 0.95 S4, etc.) Sulfide solid electrolytes have the following advantages: they are materials with high conductivity; they can be synthesized at low temperatures; they are relatively soft, so it is easy to maintain a conductive path even after charge and discharge; etc.

[0521] Oxide-based solid electrolytes include materials with a perovskite crystal structure (La 2 / 3-x Li 3x TiO3, etc.), materials with NASICON crystal structure (Li 1+X Al X Ti 2-X (PO4)3, etc.), materials with a garnet-type crystal structure (Li7La3Zr2O 12 etc.), materials with a LISICON-type crystal structure (Li 14 ZnGe4O 16 etc.), LLZO (Li7La3Zr2O 12 ), oxide glasses (Li3PO4-Li4SiO4, 50Li4SiO4·50Li3BO3, etc.), oxide crystalline glasses (Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3). Oxide-based solid electrolytes have advantages such as being stable in the atmosphere.

[0522] Halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, LiCl, LiBr, LiI, etc. In addition, a composite material formed by filling the pores of porous alumina and / or porous silica with these halide-based solid electrolytes can also be used as a solid electrolyte.

[0523] In addition, different solid electrolytes can be mixed and used.

[0524] Among them, Li 1+x Al x Ti 2-x (PO4)3 (0 < x < 1) (hereinafter denoted as LATP) contains aluminum and titanium, which are elements that can be included in the positive electrode active material of the secondary battery 400 in one embodiment of the present invention. Therefore, it can be expected to have a synergistic effect on improving the cycle characteristics and is thus preferred. In addition, a reduction in the number of processes can also be expected to improve productivity. Note that in this specification, etc., the NASICON-type crystal structure refers to a compound represented by M2(XO4)3 (M: transition metal, X: S, P, As, Mo, W, etc.), having a structure in which MO6 octahedra and XO4 tetrahedra share vertices and are arranged three-dimensionally.

[0525] This embodiment can be used in appropriate combination with other embodiments or examples.

[0526] (Embodiment 4)

[0527] In this embodiment, an example of the shape of a secondary battery including a positive electrode manufactured by the manufacturing method described in the above embodiment is described.

[0528] [Coin-type secondary battery]

[0529] An example of a coin-type secondary battery will be described. Fig.11A This is an exploded perspective view of a coin-type (single-layer flat) secondary battery. Fig. 11B This is its appearance picture. Fig. 11C Coin-type secondary batteries are mainly used in small electronic devices.

[0530] Note that in order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Fig.11A A schematic diagram is used. Therefore, Fig.11A Not with Fig. 11B Exactly the same picture.

[0531] exist Fig.11A In the embodiment, the positive electrode 304, the separator 310, the negative electrode 307, the spacer 322, and the gasket 312 are stacked. Then, the negative electrode can 302 and the positive electrode can 301 are sealed. Fig.11A The gasket used for sealing is not shown. The spacer 322 and the gasket 312 are used to protect the inside or fix the position in the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 322 and the gasket 312 are made of stainless steel or insulating material.

[0532] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0533] Fig. 11B This is a perspective view of a completed coin-type secondary battery.

[0534] In the coin-type secondary battery 300, a positive electrode can 301 serving as a positive terminal and a negative electrode can 302 serving as a negative terminal are insulated and sealed by a gasket 303 formed of polypropylene or the like. A positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. A negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector 308. The negative electrode 307 is not limited to a laminated structure, and a lithium metal foil or an alloy foil of lithium and aluminum may be used.

[0535] In the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 , the active material layer may be formed on one surface of the positive electrode and the negative electrode, respectively.

[0536] As the positive electrode tank 301 and the negative electrode tank 302, metals such as nickel, aluminum, and titanium, alloys thereof, or alloys of these and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, etc., the positive electrode tank and the negative electrode tank are preferably covered with nickel or aluminum, etc. The positive electrode tank 301 is electrically connected to the positive electrode 304, and the negative electrode tank 302 is electrically connected to the negative electrode 307.

[0537] By immersing the negative electrode 307, the positive electrode 304 and the separator 310 in an electrolyte, Fig. 11C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the separator 310, the negative electrode 307 and the negative electrode can 302 are stacked in order, and the positive electrode can 301 and the negative electrode can 302 are pressed together with the gasket 303 interposed therebetween to manufacture the coin-type secondary battery 300.

[0538] With the above structure, it is possible to manufacture the coin-type secondary battery 300 having a large discharge capacity and excellent cycle characteristics.

[0539] [Cylindrical secondary battery]

[0540] Reference Fig. 12A An example of a cylindrical secondary battery will be described. Fig. 12A As shown, the top surface of the cylindrical secondary battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0541] Fig. 12B It is a diagram schematically showing a cross section of a cylindrical secondary battery. Fig. 12B The cylindrical secondary battery shown includes a positive electrode cover (battery cover) 601 on the top surface, and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0542] A battery element is provided inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound around a separator 605. Although not shown, the battery element is wound around the central axis. One end of the battery can 602 is closed and the other end is open. As the battery can 602, metals such as nickel, aluminum, titanium, their alloys, and alloys of them and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the battery can 602 is preferably covered with nickel and aluminum. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, a non-aqueous electrolyte (not shown) is injected into the interior of the battery can 602 in which the battery element is provided. As a non-aqueous electrolyte, the same electrolyte as a coin-type secondary battery can be used.

[0543] Since the positive electrode and the negative electrode used for the cylindrical storage battery are wound, it is preferable that the active material is formed on both surfaces of the current collector.

[0544] By using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode 604 , a cylindrical secondary battery 616 having a large capacity, a large discharge capacity, and excellent cycle characteristics can be manufactured.

[0545] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. The positive terminal 603 can be made of a metal material such as aluminum. The negative terminal 607 can be made of a metal material such as copper. The positive terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cover 601 through a PTC (Positive Temperature Coefficient) element 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistance element whose resistance increases when the temperature rises, and limits the current by increasing the resistance to prevent abnormal heating. As the PTC element 611, barium titanate (BaTiO3)-based semiconductor ceramics, etc. can be used.

[0546] Fig. 12C An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616. The positive electrode of each secondary battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge and discharge control circuit for performing charge and discharge or a protection circuit for preventing overcharge and / or overdischarge can be used.

[0547] Fig.12D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of secondary batteries 616 may be connected in parallel or in series, or may be connected in parallel and then in series. By configuring the power storage system 615 including the plurality of secondary batteries 616, a large amount of electric power can be obtained.

[0548] Alternatively, a plurality of secondary batteries 616 may be connected in parallel and then connected in series.

[0549] In addition, a temperature control device may be included between the plurality of secondary batteries 616. When the secondary battery 616 is overheated, it can be cooled by the temperature control device, and when the secondary battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0550] In addition, Fig.12D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of secondary batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of secondary batteries 616 via the conductive plate 614.

[0551] [Other structural examples of secondary batteries]

[0552] Another structural example of the secondary battery will be described with reference to FIG. 13 and FIG. 14 .

[0553] Fig.13A The secondary battery 913 shown includes a winding body 950 provided with a terminal 951 and a terminal 952 inside a frame 930. The winding body 950 is impregnated with an electrolyte inside the frame 930. The terminal 952 is in contact with the frame 930, and the terminal 951 is prevented from contacting the frame 930 by an insulating material. Note that for convenience, although Fig.13A Frame 930 is shown separately in the figure, but in reality, winding body 950 is covered by frame 930, and terminals 951 and 952 extend outside frame 930. Frame 930 can be made of a metal material (such as aluminum) or a laminate of the metal material and a resin material.

[0554] In addition, if Fig. 13B As shown, multiple materials can also be used to form Fig.13A For example, in the frame 930 shown in FIG. Fig. 13B In the secondary battery 913 shown, a frame body 930 a and a frame body 930 b are bonded together, and a wound body 950 is provided in a region surrounded by the frame bodies 930 a and 930 b.

[0555] As the frame 930a, a metal material (such as aluminum, etc.) or a laminate of the metal material and a resin material can be used. In particular, by configuring an insulating material such as an organic resin on the surface where the antenna is formed, the electric field shielding caused by the secondary battery 913 can be suppressed. In addition, if the electric field shielding caused by the frame 930a is small, an antenna can also be provided inside the frame 930a. As the frame 930b, a metal material (such as aluminum, etc.) or a laminate of the metal material and a resin material can be used.

[0556] Furthermore, Fig. 13C The structure of the wound body 950 is shown. The wound body 950 includes a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is formed by overlapping the negative electrode 931 and the positive electrode 932 with the separator 933 interposed therebetween to form a laminated sheet, and then winding the laminated sheet. In addition, a plurality of layers of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked.

[0557] Alternatively, a secondary battery 913 including a wound body 950 a as shown in FIG. 14 may be used. Fig.14A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0558] By using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode 932 , a secondary battery 913 having a large capacity, a large discharge capacity, and excellent cycle characteristics can be manufactured.

[0559] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, the width of the negative electrode active material layer 931a is preferably wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferred because of its good safety and productivity.

[0560] like Fig. 14B As shown, the negative electrode 931 is electrically connected to the terminal 951 by ultrasonic welding, welding or pressing. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952 by ultrasonic bonding, welding or pressing. The terminal 952 is electrically connected to the terminal 911b.

[0561] like Fig. 14C As shown, the wound body 950a and the electrolyte are covered by the frame 930 to form a secondary battery 913. The frame 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The safety valve is a valve that is opened when the internal pressure of the frame 930 reaches a specified value to prevent battery rupture.

[0562] like Fig. 14B As shown, the secondary battery 913 may also include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a secondary battery 913 with a larger discharge capacity can be realized. Fig. 14B and Fig. 14C The other components of the secondary battery 913 shown can be referred to Fig.13A and Fig. 13B Description of the secondary battery 913 shown.

[0563] <Laminated secondary battery>

[0564] then, Fig.15A and Fig. 15B An example of an external view of an example of a laminated secondary battery is shown. Fig.15A and Fig. 15B As shown, the laminated secondary battery 500 includes a positive electrode 503 , a negative electrode 506 , a separator 507 , an outer package 509 , a positive electrode lead electrode 510 , and a negative electrode lead electrode 511 .

[0565] Fig.16A The appearance diagram of the positive electrode 503 and the negative electrode 506 is shown. The positive electrode 503 includes a positive electrode collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode collector 501. In addition, the positive electrode 503 has a region where the positive electrode collector 501 is partially exposed (hereinafter referred to as the tab region). The negative electrode 506 includes a negative electrode collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode collector 504. In addition, the negative electrode 506 has a region where the negative electrode collector 504 is partially exposed, namely, the tab region. Note that the area or shape of the tab region of the positive electrode 503 and the negative electrode 506 is not limited to Fig.16A Example shown.

[0566] <Method for manufacturing laminated secondary battery>

[0567] Reference Fig. 16B and Fig. 16C Yes Fig.15A An example of a method for manufacturing a laminated secondary battery 500 whose appearance is shown in FIG. 1 is described below.

[0568] First, the negative electrode 506, the separator 507, and the positive electrode 503 are stacked. Fig. 16B The stacked negative electrode 506, separator 507, and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes 506 and 4 sets of positive electrodes 503 is shown. The stacked negative electrode 506, separator 507, and positive electrode 503 can be called a stack. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode 503. As the joining, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode 506.

[0569] Then, if Fig. 16C As shown, the above-mentioned laminated body is arranged on the outer packaging body 509.

[0570] Below, as Fig. 16C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0571] Next, the electrolyte is introduced into the inner side of the outer packaging body 509 from the introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0572] By using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode 503 , it is possible to manufacture the secondary battery 500 having a large capacity, a large discharge capacity, and excellent cycle characteristics.

[0573] This embodiment mode can be used in combination with other embodiment modes or examples as appropriate.

[0574] (Implementation method 5)

[0575] In this embodiment, an example of a vehicle equipped with a secondary battery according to one embodiment of the present invention is described.

[0576] When the secondary battery of one embodiment of the present invention is installed in a vehicle, a new generation of clean energy vehicles such as hybrid electric vehicles (HV), electric vehicles (EV) or plug-in hybrid electric vehicles (PHV) can be realized. In addition, the secondary battery can also be installed on agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, ships, submarines, airplanes, rockets, artificial satellites, space probes, planetary probes or spacecraft. The secondary battery of one embodiment of the present invention can be a large-capacity secondary battery. Therefore, the secondary battery of one embodiment of the present invention is suitable for miniaturization and lightweight, and is suitable for transportation vehicles.

[0577] 17A to 17D An example of a transport vehicle using one embodiment of the present invention is shown. Fig.17A The car 2001 shown is an electric car using an electric motor as a power source for running. Alternatively, the car 2001 is a hybrid car that can use an electric motor and an engine as a power source for running. When the secondary battery is installed in the vehicle, the example of the secondary battery shown in the fourth embodiment is set in one or more parts. Fig.17A The illustrated automobile 2001 includes a battery pack 2200 including a secondary battery module in which a plurality of secondary batteries are connected. In addition, the battery pack 2200 preferably includes a charge control device electrically connected to the secondary battery module.

[0578] In addition, in the automobile 2001, the secondary battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method or a contactless power supply method. When charging, the charging method or the specifications of the connector can be appropriately performed according to the prescribed methods such as CHAdeMO (a registered trademark in Japan) or the combined charging system "Combined Charging System". As a charging device, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter.

[0579] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction and magnetic field resonance.

[0580] exist Fig. 17B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The transport vehicle 2002 includes a battery pack 2201, and the battery pack 2201 includes a secondary battery module in which a plurality of secondary batteries are connected. The secondary battery module of the transport vehicle 2002 is, for example, a secondary battery module in which four secondary batteries with a nominal voltage of 3.0 V or more and 5.0 V or less are used as battery cells and 48 cells are connected in series and have a maximum voltage of 170 V. The battery pack 2201 has the same characteristics as the battery pack 2201 except for the difference in the number of secondary batteries constituting the secondary battery module. Fig.17A The functions are the same, so the description is omitted.

[0581] exist Fig. 17C In the figure, a large transport vehicle 2003 including an engine controlled by electricity is shown as an example. The transport vehicle 2003 includes a battery pack 2202, and the battery pack 2202 includes a secondary battery module connecting a plurality of secondary batteries. The secondary battery module of the transport vehicle 2003 is, for example, as follows: a secondary battery module with a maximum voltage of 600V in which more than 100 secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series. Therefore, a secondary battery with less uneven characteristics is required. By using a secondary battery in which the positive electrode active material 100 described in embodiments 1, 2, etc. is used for the positive electrode, a secondary battery with stable battery characteristics can be manufactured, and mass production can be carried out at low cost from the perspective of yield.

[0582] exist Fig.17D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig.17D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a type of transportation vehicle. In the aircraft 2004, multiple secondary batteries are connected to form a secondary battery module and include a battery pack 2203 having a secondary battery module and a charging control device.

[0583] In the secondary battery module of the aircraft 2204, for example, eight 4V secondary batteries are connected in series and the maximum voltage thereof is 32V. Fig.17A The functions are the same, so the description is omitted.

[0584] exist Fig.17E 2, an artificial satellite 2005 including a secondary battery 2204 is shown as an example. Since the artificial satellite 2005 is used in the extremely low temperature space, it is preferable to include a secondary battery 2204 of one embodiment of the present invention having good low temperature resistance. In addition, the secondary battery 2204 is preferably installed inside the artificial satellite 2005 in a state covered by a heat-insulating member.

[0585] This embodiment mode can be used in combination with other embodiment modes or examples as appropriate.

[0586] (Implementation 6)

[0587] In the present embodiment, as an example of a vehicle equipped with a secondary battery, an example in which a lithium ion battery according to one embodiment of the present invention is installed in a motorcycle or a bicycle is described.

[0588] Fig.18A This is an example of an electric bicycle using the power storage device according to one embodiment of the present invention. Fig.18A The electric bicycle 8700 shown can use the power storage device of one embodiment of the present invention. For example, the power storage device of one embodiment of the present invention includes a plurality of storage batteries and a protection circuit.

[0589] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig.18B The power storage device 8702 taken out of the bicycle is shown. The power storage device 8702 has a plurality of storage batteries 8701 included in the power storage device of one embodiment of the present invention built in, and the remaining power, etc. can be displayed by the display unit 8703. In addition, the power storage device 8702 includes a control circuit 8704 that can perform charging control or abnormality detection of the secondary battery. The control circuit 8704 is electrically connected to the positive electrode and the negative electrode of the storage battery 8701. In addition, by combining with a secondary battery using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode, a synergistic effect of safety can be obtained. The secondary battery using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode and the control circuit 8704 have made a great contribution to reducing accidents such as fires caused by secondary batteries.

[0590] Fig.18C This is an example of a two-wheeled vehicle using the power storage device of one embodiment of the present invention. Fig.18C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603. In addition, the power storage device 8602 containing a plurality of secondary batteries using the positive electrode active material 100 of one embodiment of the present invention as a positive electrode can have a large capacity and contribute to miniaturization.

[0591] In addition, Fig.18C In the illustrated scooter 8600, the power storage device 8602 can be stored in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be stored in the under-seat storage section 8604.

[0592] This embodiment mode can be used in combination with other embodiment modes or examples as appropriate.

[0593] (Implementation 7)

[0594] In this embodiment, an example of installing a secondary battery of one embodiment of the present invention in an electronic device is described. As an electronic device equipped with a secondary battery, for example, a television device (also referred to as a television or a television receiver), a display for a computer, a digital camera, a digital video camera, a digital photo frame, a mobile phone (also referred to as a mobile phone, a mobile phone device), a portable game console, a portable information terminal, a sound reproduction device, a large game console such as a pinball machine, etc. can be cited. As a portable information terminal, a notebook personal computer, a tablet terminal, an e-book terminal, a mobile phone, etc. can be cited.

[0595] Fig.19A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, etc. in addition to a display portion 2102 mounted on a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. Since the secondary battery 2107 includes the positive electrode active material 100 described in Embodiments 1 and 2, etc., a large-capacity secondary battery 2107 can be realized, and space saving required for miniaturization of the housing 2101 can be achieved.

[0596] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, Internet communication, computer games, etc.

[0597] The operation button 2103 may have various functions in addition to time setting, such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0598] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0599] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0600] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0601] Fig.19B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also referred to as a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. A secondary battery using the positive electrode active material 100 of one embodiment of the present invention as a positive electrode has high energy density and high safety, so it can be used safely for a long period of time, and is therefore suitable as a secondary battery mounted on the unmanned aerial vehicle 2300.

[0602] Fig.19C An example of a robot is shown. Fig.19C The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0603] The microphone 6402 has a function of sensing the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0604] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0605] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0606] The robot 6400 is provided with a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component. The secondary battery using the positive electrode active material 100 according to one embodiment of the present invention for the positive electrode has high energy density and high safety, so it can be used safely for a long period of time, and is therefore suitable as the secondary battery 6409 installed in the robot 6400.

[0607] Fig.19D An example of a portable fan is shown. Fig.19D The portable fan 6200 shown includes a secondary battery 6209 of one embodiment of the present invention, an operation button 6205, a fan 6202, an external connection port 6204, etc., and the secondary battery 6209 is contained in a housing 6201. In the portable fan 6200, the fan 6202 can be rotated by operating the engine using the power supplied by the secondary battery 6209, and the secondary battery 6209 can be charged through the external connection port 6204. The secondary battery 6209 is shown as an example of a cylindrical secondary battery, but there is no particular limitation on its shape. The secondary battery using the positive electrode active material 100 of one embodiment of the present invention is not easy to catch fire because it has a stable crystal structure, and is therefore suitable for use as a secondary battery 6306 installed in the portable fan 6200.

[0608] Fig.19E An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk automatically, detect garbage 6310, and can suck the garbage 6310 from the suction port set below the frame 6301.

[0609] The sweeping robot 6300 can determine whether there are obstacles such as walls, furniture or steps by analyzing the image taken by the camera 6303. In addition, when an object such as a wire that may be entangled with the brush 6304 is found through image analysis, the rotation of the brush 6304 can be stopped. The internal area of ​​the sweeping robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. The secondary battery using the positive electrode active material 100 of one embodiment of the present invention for the positive electrode has high energy density and high safety, so it can be used safely for a long time, so it is suitable as a secondary battery 6306 installed in the sweeping robot 6300.

[0610] This embodiment mode can be used in combination with other embodiment modes or examples as appropriate.

[0611] [Example 1]

[0612] <Manufacturing of Positive Electrode Active Material>

[0613] In this embodiment, as the positive electrode active material described in the above embodiment, four samples (samples 1 to 4) with different manufacturing conditions are prepared. The manufacturing process of each sample is described in detail below. Note that in this manufacturing process, many conditions are common between samples. Therefore, the conditions not specifically described in the manufacturing conditions described below are common to all samples, and the content is recorded when there are differences in conditions between samples.

[0614] <Sample production>

[0615] As the above-mentioned embodiment Figure 7 As shown, cobalt sulfate (CoSO4) is prepared as the cobalt source 81, nickel sulfate (NiSO4) is prepared as the nickel source 82, and first glycine is prepared as the chelating agent 83, and they are mixed as in step S14 to obtain a mixed solution 91. In addition, the molar ratio of cobalt sulfate to nickel sulfate is set to 99: 1. In addition, in the mixed solution 91, the total amount of cobalt sulfate and nickel sulfate is set to 2 mol / L, and the first glycine is set to 0.075 mol / L.

[0616] Then, as Figure 7 The alkaline aqueous solution 84 shown is prepared by dissolving sodium hydroxide in pure water (sodium hydroxide aqueous solution). The sodium hydroxide is adjusted to 5 mol / L.

[0617] In addition, as Figure 7 The chelating agent 85 shown is prepared as an aqueous solution containing the second glycine. The aqueous solution containing the second glycine is adjusted to 0.075 mol / L. The aqueous solution containing the second glycine is referred to as a filling liquid.

[0618] The reaction container was filled with the filling liquid, stirred at a rotation speed of 1000 rpm using a stirrer, and adjusted to maintain a fixed temperature (maintained at 50°C when manufacturing sample 1 and sample 3, and maintained at 70°C when manufacturing sample 2 and sample 4), nitrogen was supplied from the upper part of the reaction container at 1 L / min, and sodium hydroxide aqueous solution was dripped to maintain a pH of 10.3. The dripping speed was changed in multiple stages, specifically, the dripping speed was gradually increased from 0.4 mL / min to 0.93 mL / min to drip the mixed solution 91 (the above is Figure 7 Step S31 shown in the figure). Since the sodium hydroxide aqueous solution is supplied while the sodium hydroxide aqueous solution tube is immersed in the filled liquid, the dripping speed can also be called the infusion speed. As the above coprecipitation device, OptiMax (manufactured by Mettler-Toledo Co., Ltd.) was used.

[0619] according to Figure 7 In step S32, the suspension generated by the coprecipitation reaction is filtered using pure water, and then filtered using acetone to obtain a precipitate. Figure 7 In step 33 shown in the figure, the precipitate is dried in a vacuum drying oven at 80°C (1 hour when manufacturing sample 1 and sample 3, and 17 hours when manufacturing sample 2 and sample 4), thereby obtaining hydroxide 95. It is considered that by performing this drying, hydroxide 95 with impurities removed can be obtained. Hydroxide 95 can be represented by Co (1-y) Ni y (OH)2, this sample was prepared so that y is 0.01. Note that, as mentioned above, hydroxide 95 is sometimes referred to as a precursor.

[0620] As Figure 7 Lithium hydroxide was prepared as a lithium source 88. The lithium hydroxide was ground in dehydrated acetone using a ball mill and sieved using a sieve with a mesh size of 300 μm.

[0621] Next, according to Figure 7 In step S51, the precursor (hydroxide 95) obtained above and lithium hydroxide are mixed using a ball mill. The mixture 96 was then screened using a sieve with a mesh size of 300 μm to obtain a mixture 96. The mixing ratio of the precursor and the lithium source 88 was set so that the molar ratio of lithium hydroxide to the precursor (represented as Li / Co) was 1.03. Note that this molar ratio may not be satisfied in the positive electrode active material 100.

[0622] Next, in samples 3 and 4, according to Figure 7 The mixture 96 is heated (pre-baked) in step S52. The heating conditions for samples 3 and 4 are both 800° C. and 10 hours. During heating, oxygen is allowed to flow through the furnace at a flow rate of 5 L / min. Note that the heating in step S52 is not performed for samples 1 and 2.

[0623] Next, according to Figure 7 In step S54, the mixture 96 is heated (main calcination). The heating conditions are 950° C. and 10 hours. During heating, oxygen is allowed to flow through the furnace at a flow rate of 5 L / min. Then, it is cooled to room temperature to obtain oxide 98. Note that oxide 98 is called a composite oxide and can also be used as a positive electrode active material at this stage.

[0624] Note that in this embodiment, no Figure 7 The grinding of step S53 and the grinding of step S55.

[0625] As Figure 7 The additive element source 89 is a mixture of LiF:MgF2=1:3 (molar ratio). First, place the mixture in dehydrated acetone. A ball mill with zirconia balls was used to mix LiF and MgF2, and then dried at 55 °C for 2 hours to evaporate acetone. Then, screening was carried out using a sieve with a mesh size of 300 μm to obtain the additive element source 89.

[0626] Next, according to Figure 7 step S71, a ball mill was used to mix the oxide 98 and the mixture containing LiF and MgF2 (additive element source 89), thereby obtaining the mixture 99.

[0627] According to Figure 7 step S72, the mixture 99 was heated. The heating conditions were 900 °C and 20 hours. Oxygen was passed through at a flow rate of 5 L / min in a heating furnace. Then it was cooled to room temperature, thereby obtaining the positive electrode active material 100.

[0628] Note that in this embodiment, the grinding in Figure 7 step S73 is not performed.

[0629] The following table shows the main manufacturing conditions of Samples 1 to 4.

[0630] [Table 1]

[0631] Sample 1 Sample 2 Sample 3 Sample 4 Temperature during coprecipitation (step S31) 50℃ 70℃ 50℃ 70℃ Drying (step S33) time 1 hour 17 hours 1 hour 17 hours Heating (step S52) conditions - - 800℃10 hours 800℃10 hours

[0632] <SEM image>

[0633] Fig. 20 The planar SEM images of the respective samples corresponding to the manufacturing processes of Samples 1 to 4 are shown, showing the precursor (hydroxide 95), Figure 7 the state after heating at 800 °C for 10 hours in step 52, the oxide 98, and the positive electrode active material 100. The SEM images were obtained using S4800 manufactured by Hitachi High-Technologies Corporation. The acceleration voltage was fixed at 5 kV and the magnification was 5000 times. It can be seen that in any sample, there is a tendency for the particle size to increase during the process of the precursor becoming the oxide 98. In particular, this tendency is obvious in Sample 2. However, differences between samples were confirmed, such as the particle size of Sample 4 being slightly smaller than that of the other three samples. On the other hand, after the positive electrode active material 100 was generated, the particle size of Sample 4 also grew to the same level as that of the other three samples, and it was difficult to confirm the particle size difference between samples.

[0634] <XRD measurement>

[0635] Fig.21 The powder XRD measurement results after the generation of the mixture 99 corresponding to the manufacturing processes of Samples 1 to 4 are shown. Note that for comparison, Fig.21 The data of LCO, Co3O4, and Co(OH)2 are shown together (obtained from ICSD (refer to Non-Patent Document 2)). The XRD measurement conditions are as follows:

[0636] XRD device: D8 ADVANCE manufactured by Bruker AXS

[0637] X-ray source: Cu Kα source (using EVA to extract Kα1)

[0638] Output: 40kV, 40mA

[0639] Emission angle: Div. Slit, 0.5°

[0640] Detector: LynxEye

[0641] Scanning mode: 2θ / θ continuous scanning

[0642] Measuring range (2θ): 15° to 90°

[0643] 2θ step width (increment): set to 0.01°

[0644] Counting time: 1 second / step

[0645] Sample stage rotation: 15rpm

[0646] In any of the above samples, the position of the diffraction peak measured by XRD overlaps with the position of the diffraction peak of lithium cobalt oxide (LCO) obtained from ICSD (see non-patent document 2), thereby confirming that perfect lithium cobalt oxide can be produced. In addition, it can be seen that the 2θ of each sample does not overlap with cobalt carbonate (Co3O4) and cobalt hydroxide (Co(OH)2) which are considered to be reaction residues.

[0647] <Manufacturing of positive electrode>

[0648] Prepare the above-mentioned samples 1 to 4 as positive electrode active materials, prepare acetylene black (AB) as a conductive material, and prepare polyvinylidene fluoride (PVDF) as a binder. Prepare PVDF that is dissolved in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Then, mix the positive electrode active material: AB: PVDF = 95:3:2 (weight ratio) to prepare a slurry, and apply the slurry to an aluminum current collector. NMP is used as a solvent for the slurry. After applying the slurry to the positive electrode current collector, the solvent is evaporated.

[0649] Then, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a roller press was used for pressing. Under the pressing conditions, the linear pressure was 210 kN / m. The upper and lower rollers of the roller press were both at 120°C. The loading of each sample was 7 mg / cm 2 about.

[0650] Through the above-mentioned process, positive electrodes including Sample 1 to Sample 4 were obtained.

[0651] <Manufacturing of test batteries>

[0652] A test cell (CR2032 coin cell, 20 mm in diameter, 3.2 mm in height) using lithium metal as a counter electrode was manufactured using the above positive electrode. A cell using lithium metal as a counter electrode is referred to as a half-cell.

[0653] As the electrolyte of the half-cell, an organic electrolyte was prepared in which lithium hexafluorophosphate (LiPF6) was dissolved at 1 mol / L in a mixed organic solvent containing EC (ethylene carbonate) and DEC (diethyl carbonate) in a ratio of EC:DEC=30:70 (volume ratio). In addition, 2 wt% of VC (vinylene carbonate) was added to the organic electrolyte as an additive.

[0654] As the separator of the half-cell, a porous polypropylene film with a thickness of 25 μm was used.

[0655] This was housed in a positive electrode can and a negative electrode can to manufacture half cells including samples 1 to 4. In order to clarify the correspondence with the positive electrode active material, the manufactured half cells are referred to as samples 1 to 4. The positive electrode can and the negative electrode can were formed of stainless steel (SUS).

[0656] <Charge and discharge cycle test>

[0657] As a charge and discharge tester, a charge and discharge evaluation system (TOSCAT-3100) manufactured by TOYO SYSTEM Co., Ltd. was used to measure the charge and discharge cycle test of a half cell. By using the charge and discharge cycle test of a half cell, the performance of a single positive electrode can be grasped.

[0658] The rate of the charge and discharge cycle test conditions is explained. The rate during discharge is called the discharge rate, which refers to the ratio of the current during discharge to the battery capacity, and is represented by the unit C. In a battery with a rated capacity of X (Ah), the current equivalent to 1C is X (A). In the case of discharging with a current of 2X (A), it can be said to be discharged at 2C, and in the case of discharging with a current of X / 2 (A), it can be said to be discharged at 0.5C. In addition, the rate during charging is called the charging rate. Similar to the charging rate, in the case of charging with a current of 2X (A), it can be said to be charged at 2C, and in the case of charging with a current of X / 2 (A), it can be said to be charged at 0.5C. The charging rate and the discharge rate are collectively referred to as the charge and discharge rate.

[0659] In the charge and discharge cycle test, the above-mentioned charge and discharge are repeated 50 times as one cycle, and the value calculated by (discharge capacity of the 50th cycle / maximum value of discharge capacity in 50 cycles) × 100 is set as the discharge capacity retention rate (capacity retention) (%) of the 50th cycle. That is, the ratio of the discharge capacity value measured at the 50th cycle to the maximum value of the discharge capacity in the entire 50 cycles (recorded as the maximum discharge capacity) is calculated. The higher the discharge capacity retention rate, the more the capacity decrease of the battery after repeated charge and discharge is suppressed, so it is suitable as a battery characteristic. Note that the above number of cycles is only an example.

[0660] In the charge and discharge cycle test, the current is measured. Specifically, in the measurement of charge and discharge, it is preferred to measure the battery voltage and the current flowing through the battery using the four-probe method. In charging, electrons flow from the positive terminal to the negative terminal through the charge and discharge measuring device, so the charging current refers to the current flowing from the negative terminal to the positive terminal through the charge and discharge measuring device. In addition, in discharging, electrons flow from the negative terminal to the positive terminal through the charge and discharge measuring device, so the discharge current refers to the current flowing from the positive terminal to the negative terminal through the charge and discharge measuring device. The charging current and the discharge current are measured using an ammeter possessed by the charge and discharge measuring device, and the cumulative amount of the current flowing in one charge and one discharge is equivalent to the charging capacity and the discharge capacity, respectively. For example, the cumulative amount of the discharge current flowing in the discharge of the first cycle can be referred to as the discharge capacity of the first cycle, and the cumulative amount of the discharge current flowing in the discharge of the 50th cycle can be referred to as the discharge capacity of the 50th cycle.

[0661] The above-mentioned charge-discharge cycle test was performed on samples 1 to 4 at ambient temperatures of 25° C. and 45° C. The ambient temperature refers to the temperature of a thermostatic chamber in which the half-cells corresponding to each of samples 1 to 4 were arranged.

[0662] The charging conditions of each half-cell configured in the thermostatic chamber are as follows: constant current charging is performed at a rate of 0.5C (in this embodiment, it is set to 1C = 200mA / g (weight of positive electrode active material)) until the upper limit voltage reaches 4.6V, 4.65V or 4.7V, and then constant voltage charging is performed while maintaining the upper limit voltage until the current reaches 0.05C. In this way, constant current charging followed by constant voltage charging is sometimes recorded as CC / CV charging, and as a charge and discharge cycle test condition, it is recorded as CC / CV charging (each upper limit voltage, rate is 0.5C, and cutoff is 0.05C). The discharge conditions are as follows: constant current discharge is performed at a rate of 0.5C until the lower limit voltage reaches 2.5V. A sleep period is set between charging and discharging, and in this embodiment, the sleep period is set to 10 minutes.

[0663] Fig.22A The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 25° C. and the upper limit voltage is 4.6 V. Fig. 22B The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 25° C. and the upper limit voltage is 4.65 V. Fig. 22C The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 25° C. and the upper limit voltage is 4.7 V. Note that the discharge capacity of the half cell in this example is calculated as a value per unit weight of the positive electrode active material.

[0664] Fig.23A The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 45° C. and the upper limit voltage is 4.6 V. Fig. 23B The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 45° C. and the upper limit voltage is 4.65 V. Fig.23C The graph shows the change in discharge capacity with respect to the number of cycles when the ambient temperature is 45° C. and the upper limit voltage is 4.7 V.

[0665] Fig.24A The graph shows the discharge capacity retention ratio when the ambient temperature is 25° C. and the upper limit voltage is 4.6V. Fig. 24B The graph shows the discharge capacity retention ratio when the ambient temperature is 25° C. and the upper limit voltage is 4.65V. Fig.24C The graph shows the discharge capacity retention ratio when the ambient temperature is 25° C. and the upper limit voltage is 4.7V.

[0666] Fig.25A The graph shows the discharge capacity retention ratio when the ambient temperature is 45° C. and the upper limit voltage is 4.6V. Fig.25B The graph shows the discharge capacity retention ratio when the ambient temperature is 45° C. and the upper limit voltage is 4.65V. Fig.25C The graph shows the discharge capacity retention ratio when the ambient temperature is 45° C. and the upper limit voltage is 4.7V.

[0667] When the ambient temperature was 25°C, the discharge capacity and discharge capacity retention rate of sample 2 showed a clear downward trend with increasing cycle number regardless of the upper limit voltage, but no significant difference was observed in the other three samples due to the difference in conditions (refer to FIG. 22A to FIG. 22C , FIG. 24A to FIG. 24C On the other hand, when the ambient temperature was 45°C, it was confirmed that the discharge capacity and discharge capacity retention rate of sample 2 decreased slightly more than those of the other three samples when the upper limit voltage was 4.6V (refer to Fig.23A , Fig.25A ), but no significant difference between samples was confirmed under other upper voltage conditions (refer to Fig. 23B , Fig.23C , Fig.25B and Fig.25C ). In addition, it can be seen that: in Samples 1, 3, and 4, the higher the upper limit voltage, the lower the discharge capacity and discharge capacity retention rate. However, in Sample 2, the changes in discharge capacity and discharge capacity retention rate based on the upper limit voltage are smaller than those in the other three samples (refer to FIG. 22A to FIG. 25C ).

[0668] <Rate Characteristics>

[0669] At an ambient temperature of 25°C, the discharge capacity of samples 1 to 4 was measured by fixing the charge rate at 0.5C until the voltage reached 4.6V, 4.65V or 4.7V and changing the discharge rate to 0.2C, 0.5C, 1C, 2C, 3C, 4C, 5C and 0.2C in sequence. This measurement is sometimes referred to as rate characteristics. In addition, the discharge capacity was measured twice for each rate.

[0670] Fig.26A The graph shows the rate characteristics when the upper limit voltage is 4.6 V, in which the rate characteristics are normalized with the initial values ​​of 0.5C / 0.2C. Fig.26B The graph shows the rate characteristics when the upper limit voltage is 4.65 V, in which the rate characteristics are normalized with the initial values ​​of 0.5C / 0.2C. Fig.26C The graph shows the rate characteristics when the upper limit voltage is 4.7 V, in which the rate characteristics are normalized with the initial values ​​of 0.5C / 0.2C.

[0671] Fig.27A The graph shows the rate characteristics when the upper limit voltage is 4.6 V, in which the energy density at the initial 0.5C / 0.2C is normalized. Fig.27B The graph shows the rate characteristics when the upper limit voltage is 4.65 V, in which the energy density at the initial 0.5C / 0.2C is normalized. Fig.27C The graph shows the rate characteristics when the upper limit voltage is 4.7 V, in which the energy density at the initial 0.5C / 0.2C is normalized.

[0672] In sample 2, a tendency that the rate characteristics are poor regardless of the upper limit voltage is confirmed, but no significant difference due to the difference in conditions is confirmed in the other three samples. In addition, it is known that even if the discharge rate is increased, the three samples other than sample 2 still show the same degree of discharge capacity and energy density as the initial level, and have excellent high rate characteristics such as more than 2C and less than 5C (refer to FIG. 26A to FIG. 26C , FIG. 27A to FIG. 27C ).

[0673] [Example 2]

[0674] In this example, a sample was prepared again as a positive electrode active material to perform various measurements. The sample was manufactured according to the above-mentioned embodiment. The manufacturing process of the sample and the like of this example will be described in detail below.

[0675] <Sample production>

[0676] As the above-mentioned embodiment Figure 7 As shown, cobalt sulfate (CoSO4) is prepared as the cobalt source 81, nickel sulfate (NiSO4) is prepared as the nickel source 82, and the first glycine is prepared as the chelating agent 83, and mixed as in step S14, thereby obtaining a mixed solution 91 in which cobalt sulfate and nickel sulfate are dissolved. In addition, the molar ratio of cobalt sulfate to nickel sulfate in sample 1 is set to 99:1. In addition, in the mixed solution 91 of sample 1, the total concentration of cobalt sulfate and nickel sulfate is set to 2 mol / L, and the concentration of the first glycine is set to 0.075 mol / L.

[0677] Then, as Figure 7 The alkaline aqueous solution 84 shown is prepared by dissolving sodium hydroxide in pure water (sodium hydroxide aqueous solution). The concentration of sodium hydroxide is adjusted to 5 mol / L.

[0678] In addition, as Figure 7 The chelating agent 85 shown is prepared as an aqueous solution containing the second glycine. In the aqueous solution containing the second glycine, the concentration of the second glycine is adjusted to 0.075 mol / L. The aqueous solution containing the second glycine is referred to as a filling liquid.

[0679] The reaction vessel of the coprecipitation device is filled with a filling liquid, stirred with a stirrer at a speed of 1000 rpm, adjusted to maintain a temperature of 70°C, nitrogen is supplied at 1 L / min from the top of the reaction vessel, and a sodium hydroxide aqueous solution is dripped to maintain a pH of 10.3. The mixed solution 91 is dripped into the reaction vessel by gradually increasing the dripping rate from 0.4 mL / min to 0.93 mL / min. Because the sodium hydroxide aqueous solution is supplied while the tube of the sodium hydroxide aqueous solution is immersed in the filling liquid, the dripping rate can also be referred to as the infusion rate. OptiMax (manufactured by Mettler-Toledo Co., Ltd.) is used as a coprecipitation device.

[0680] according to Figure 7 In step S32, the suspension generated by the coprecipitation reaction is filtered using pure water, and then filtered using acetone to obtain a precipitate. Figure 7 In step 33 shown in the figure, the precipitate is dried in a vacuum drying oven at 80° C. for 17 hours, thereby obtaining hydroxide 95 (sample 1). By fully drying as in sample 1, hydroxide 95 with impurities removed can be obtained. Hydroxide 95 is cobalt nickel hydroxide and can be represented by Co (1-y) Ni y (OH)2, the molar ratio of the raw materials was adjusted so that y was 0.01 in sample 1. However, sometimes the atomic ratio of the hydroxide obtained by the coprecipitation reaction and / or the suction filtration process is not equal to the adjusted molar ratio. Note that hydroxide 95 is sometimes referred to as a precursor.

[0681] As Figure 7 Prepare lithium hydroxide from lithium source 88. Place in dehydrated acetone Zirconia balls are prepared and lithium hydroxide is ground using a ball mill. The mixture is dried at 55°C for 2 hours to volatilize the acetone, and a sieve with a mesh size of 300 μm is used to separate the zirconium oxide balls from the lithium hydroxide. In step S42, the molar ratio of lithium hydroxide relative to the above-mentioned precursor (referred to as Li / Co) is adjusted to 1.00, 1.03, 1.06, 1.09, 1.15 and 1.20 (referred to as 1.2). The samples having the above-mentioned Li / Co are respectively referred to as sample 5-1, sample 5-2, sample 5-3, sample 5-4, sample 5-5 and sample 5-6. The table below shows the Li / Co of each sample. Note that this molar ratio may not be satisfied in the positive electrode active material 100.

[0682] [Table 2]

[0683] Li / Co (molar ratio) Sample 5-1 1.00 Sample 5-2 1.03 Sample 5-3 1.06 Sample 5-4 1.09 Sample 5-5 1.15 Sample 5-6 1.20

[0684] Next, according to Figure 7 In steps S51 and S54, the precursor and lithium hydroxide are mixed for 1 hour using an automatic mortar to obtain mixture 96, and then mixture 96 is heated. The heating conditions are 950 °C and 10 hours. Oxygen is passed through at a flow rate of 5 L / min in a heating furnace. Then it is cooled to room temperature to obtain oxide 98. Note that oxide 98 is referred to as a composite oxide and can also be used as a positive electrode active material at this stage. In addition, the atomic ratio of the positive electrode active material sometimes does not equal the molar ratio adjusted to the values in the above table.

[0685] Note that in this embodiment, heating in Figure 7 step S52 and grinding in step S53 are not performed.

[0686] As Figure 7 the additive element source 89, a compound containing the additive element is prepared. Specifically, a mixture of LiF:MgF2 = 1:3 (molar ratio) is prepared. As the additive element source 89, LiF and MgF2 adjusted to have the above molar ratio are mixed in dehydrated acetone, and then sieved using a sieve with a mesh size of 300 μm. According to Figure 7 step S71, oxide 98 and the mixture containing LiF and MgF2 are mixed for 1 hour using an automatic mortar to obtain mixture 99.

[0687] According to Figure 7 step S72, mixture 99 is heated. The heating conditions are 900 °C and 20 hours. Oxygen is passed through at a flow rate of 5 L / min in a heating furnace. Then it is cooled to room temperature to obtain the positive electrode active material 100.

[0688] Note that in this embodiment, grinding in Figure 7 step S73 is not performed. Thus, the positive electrode active materials corresponding to samples 5-1 to 5-6 are obtained.

[0689] <SEM Image 1>

[0690] Fig.28 A planar SEM image of the precursors corresponding to samples 5-1 to 5-6 is shown, where Li / Co adjusted between these samples is different as shown in the above table. In addition, Fig.28 a planar SEM image of the composite oxide corresponding to samples 5-1 to 5-6, before the addition of the additive element source and having been heat-treated at 950 °C for 10 hours, is also shown. The SEM image is obtained using S4800 manufactured by Hitachi High-Technologies Corporation, with the acceleration voltage fixed at 15 kV and the magnification at 5000 times and 20000 times.

[0691] It can be confirmed that the particle sizes of Samples 5-1 to 5-6 are larger than those of the precursor. Moreover, it was confirmed that among Samples 5-1 to 5-6, the higher the Li / Co ratio, the larger the particle size. Samples 5-5 and 5-6 look like single particles.

[0692] <SEM Image 2>

[0693] Fig.29 Fig. shows the planar SEM images of the composite oxides corresponding to Samples 5-1 to 5-6 after adding the elemental source and having been heat-treated at 900 °C for 20 hours. The SEM images were obtained using an S4800 manufactured by Hitachi High-Technologies Corporation. The acceleration voltage was fixed at 15 kV, and the magnifications were 5000 times and 20000 times.

[0694] It can be confirmed that the particle sizes of Samples 5-1 to 5-6 are larger than Fig.28 the precursor shown. Furthermore, among Samples 5-1 to 5-6, some maintained Fig.28 the appearance shown to a certain extent while being slightly pulverized. In addition, it was confirmed that: among Samples 5-1 to 5-6, the particle surface is smoother than Fig.28 that shown. The smoother surface may be because the added elemental source contains fluorine. In addition, the smoother surface may be because of the heat treatment.

[0695] <SEM Image and EDX Area Analysis and Point Analysis Measurements>

[0696] Point analysis was performed on the positive electrode active materials 5-6A and 5-6B manufactured in the same manner as Sample 5-6 using a surface scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDX) method. As the EDX measurement device, an energy dispersive X-ray spectrometer JED-2300T manufactured by JEOL Ltd. was used. The acceleration voltage was from 3 kV to 30 kV, and a silicon drift detector was used for X-ray detection. In the elemental analysis of EDX, the detection depth was set to several nm to several μm according to the acceleration voltage, the energy resolution was from 130 eV to 140 eV, and the detection limit for each element was about 1 atomic%.

[0697] Fig. 30A is the SEM image of the surface of the positive electrode active material 5-6A (denoted as the surface SEM image), and lines 1 to 6 are attached to the regions of interest for the point analysis of EDX. In the drawing, lines 1 to 6 are represented as 1 to 6 respectively. Fig.31 、 Fig.32 、 Fig.33 、 Fig.34 、 Figure 35 to Figure 36 The energy spectrum of each region (spectral line 1 to spectral line 6) is shown respectively. In the energy spectrum, the horizontal axis represents the energy of the X-ray and the vertical axis represents the X-ray intensity. The unit of X-ray intensity is cps (Count Per Second).

[0698] In the energy spectrum, the energy positions of cobalt, fluorine, and nickel are close, so sometimes the spectral lines are detected close to each other. In other words, the spectral lines of cobalt, fluorine, and nickel sometimes overlap. Figure 31 to Figure 36 In the energy spectrum shown, fluorine lines are confirmed, which indicates that fluorine exists on the surface of the positive electrode active material 5-6A. On the other hand, nickel may not exist on the surface of the positive electrode active material 5-6A in some areas. Fig.31 , Fig.33 and Fig.35 The spectrum line of nickel in the positive electrode active material 5-6A was confirmed in . In the positive electrode active material 5-6A, nickel and the cobalt source were coprecipitated together, and nickel was solid-dissolved in cobalt, so it can be considered that nickel exists inside the positive electrode active material 5-6A but not on the surface of the positive electrode active material 5-6A.

[0699] according to Figure 31 to Figure 36 The spectrum shown was subjected to waveform separation using the attached software, etc., and the atomic number ratio of each element was derived from it. The atomic number ratio of each element (unit: atomic%, expressed as at%) is shown in the table below.

[0700] [Table 3]

[0701]

[0702] The atomic number ratio of each element can be read from the above table. Note that the waveform separation of the energy spectrum is not smooth due to the accuracy of the attached software, and sometimes the energy spectrum is misdetected during fitting. In this case, the atomic number ratio may be output as 0at%, but the existence of each element can be discussed based on the energy spectrum. For example, although fluorine is 0at% in Table 3, Figure 31 to Figure 36 Since fluorine lines are confirmed in the energy spectrum of , it is considered that fluorine exists on the surface of the positive electrode active material 5-6A.

[0703] In the following table, cobalt, fluorine, magnesium, and nickel are selected to confirm the atomic ratio of transition metals and additive elements on the surface of positive electrode active material 5-6A.

[0704] [Table 4]

[0705]

[0706] The ratio of the number of atoms of each element can be read from the above table.

[0707] Next, a mapping image obtained by surface scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) method is shown. Fig. 30B is the mapping image of oxygen, Fig. 30C is the mapping image of cobalt, Fig.30D is the mapping image of magnesium. Fig.30E This is a mapping image of fluorine. By operating while irradiating an arbitrary area such as 192 pixels × 256 pixels with X-rays, the intensity of the target element is converted into brightness, thereby obtaining a mapping image. This is sometimes called surface analysis. The mapping image is an image that visualizes the existence of the target element in the target area, and can be considered FIG. 30B to FIG. 30E The bright spots in the image indicate the presence of each element. However, the presence of an element cannot be determined based on the mapping image alone, so Figure 31 to Figure 36 The energy spectrum determines the presence of elements.

[0708] Next, the energy spectra of other samples manufactured under the same conditions are obtained. Specifically, Fig.37A The surface SEM image of the positive electrode active material 5-6B (particles different from the positive electrode active material 5-6A, this condition is sometimes recorded as n = 2) is shown, and the target area of ​​the EDX point analysis is attached with spectrum lines 1 to 4, spectrum line 6 and spectrum line 7. In the figure, spectrum lines 1 to 6 are respectively represented as 1 to 6. Fig.38 , Fig.39 , Fig.40 , Fig.41 , Fig.42 and Fig.43 The energy spectrum of each region (spectral line 1 to spectral line 4, spectral line 6 and spectral line 7) is shown respectively.

[0709] In the energy spectrum, the energy positions of cobalt and fluorine are close, so sometimes the spectral lines are detected close to each other. In other words, the spectral lines of cobalt and fluorine sometimes overlap. Figures 38 to 43 In the energy spectrum shown in FIG. 1 , fluorine lines are confirmed, and it is considered that fluorine exists on the surface of the positive electrode active material 5-6B. Figures 38 to 43 No nickel lines are observed in the spectrum shown.

[0710] according to Figures 38 to 43 The spectrum shown was subjected to waveform separation using the attached software, etc., and the atomic number ratio of each element was derived therefrom. The atomic number ratio (at%) of each element is shown in the table below.

[0711] [Table 5]

[0712]

[0713] Based on the above table, the atomic ratio of each element can be read. Note that due to the precision of the attached software, the waveform separation of the energy spectrum is not smooth, and sometimes the energy spectrum is misdetected during fitting. In this case, the atomic ratio may be output as 0 at%, but the presence of each element can be discussed based on the energy spectrum. For example, although fluorine is 0 at% in Table 5, the spectral line of fluorine is confirmed in the Figures 38 to 43 energy spectrum, so it can be considered that fluorine exists on the surface of the positive electrode active material 5-6B, etc.

[0714] In the following table, cobalt, fluorine, and magnesium are selected to show the atomic ratio of transition metals and additive elements, etc. on the surface of the positive electrode active material 5-6B, etc.

[0715] [Table 6]

[0716]

[0717] Based on the above table, the atomic ratio of each element can be read.

[0718] Fig.37B is the mapping image of oxygen, Fig.37C is the mapping image of cobalt, Fig.37D is the mapping image of magnesium, Fig.37E is the mapping image of fluorine. While irradiating an arbitrary area such as 192 pixel × 256 pixel with X-rays and operating, the intensity of the target element is converted into brightness, thereby obtaining the mapping image. Sometimes it is called surface analysis. The mapping image is an image that visualizes the presence of the target element in the target area, and it can be considered that FIG. 37B to FIG. 37E the bright spots in it indicate the presence of each element. However, the presence of an element cannot be judged only based on the mapping image, so the Figures 38 to 43 energy spectrum is used to judge the presence of an element.

[0719] <XRD Measurement>

[0720] Fig.44 Shows the powder XRD measurement results of the positive electrode active materials corresponding to Samples 5-1 to 5-6. The XRD measurement conditions are as follows:

[0721] XRD device: D8 ADVANCE manufactured by Bruker AXS

[0722] X-ray source: Cu Kα source (Kα1 is extracted using EVA)

[0723] Output: 40 kV, 40 mA

[0724] Emission angle: Div. Slit, 0.5°

[0725] Detector: LynxEye

[0726] Scanning mode: 2θ / θ continuous scanning

[0727] Measuring range (2θ): 15° to 90°

[0728] Step width (2θ): set to 0.01°

[0729] Counting time: 1 second / step

[0730] Sample stage rotation: 15rpm

[0731] The 2θ values ​​of the positive electrode active materials corresponding to samples 5-1 to 5-6 overlap with lithium cobalt oxide (LCO), thereby confirming that lithium cobalt oxide has been produced. In other words, the XRD spectrum or diffraction pattern overlaps with lithium cobalt oxide (LCO), thereby confirming that lithium cobalt oxide has been produced. Furthermore, since the above-mentioned 2θ values ​​of the positive electrode active materials corresponding to samples 5-3 to 5-6 do not overlap with lithium carbonate (Li2CO3) and cobalt tetroxide (Co3O4), it can be considered that a positive electrode active material with less reaction residue is obtained. The positive electrode active materials corresponding to samples 5-3 to 5-6 do not substantially contain lithium carbonate (Li2CO3) and cobalt tetroxide (Co3O4). However, the peak of cobalt tetroxide was slightly detected in samples 5-1 and 5-2.

[0732] <Grain size>

[0733] Next, it is confirmed how the grain size (also called grain size) changes when Li / Co increases. Therefore, the grain sizes of sample 5-1, sample 5-4 with high Li / Co, sample 5-5 and sample 5-6 are measured. Grain size refers to the length of the part that can be regarded as the smallest unit of a single crystal. In this embodiment, it is confirmed how the above-mentioned samples change before and after the addition of the element source. When measuring the grain size, DIFFRAC.TOPAS ver.3 is used as the crystal structure analysis software, and the settings are as follows.

[0734] Emission Profile: CuKa5.lam

[0735] Background: Chebychev polynomial, 20 times

[0736] Instrument

[0737] Primary radius: 250mm

[0738] Secondaryradius: 250mm

[0739] Receivingslitwidth: 0.1mm

[0740] Divergenceangle: 0.5

[0741] FullAxialConvolution

[0742] FilamentLength: 12mm

[0743] SampleLength: 15mm

[0744] ReceivingSlitLength: 12mm

[0745] PrimarySollers: 2.5

[0746] SecondarySollers: 2.5

[0747] Corrections

[0748] Specimen displacement:Refine

[0749] LP Factor: 0

[0750] Fig.45A The results show the crystallite size of the composite oxide before the addition of the additive elements and after the heat treatment at 950° C. for 10 hours. Fig.45B The results show the crystal size of the positive electrode active material after adding the additive element and performing a heat treatment at 900°C for 20 hours. Fig.45A and Fig.45B It can be seen that the crystal grain size of sample 5-4 having a Li / Co ratio of 1.09 is the largest, followed by the crystal grain sizes of sample 5-5 having a Li / Co ratio of 1.15 and sample 5-6 having a Li / Co ratio of 1.2.

[0751] Depend on Fig.45A and Fig.45B It can be seen that the higher the Li / Co ratio, the larger the crystal size. When the grain size is large, it can be a single particle. In other words, it can be seen that it is preferred to increase the Li / Co ratio to obtain a single particle. In addition, it is confirmed that the grain size tends to become slightly smaller after the addition of the additive element.

[0752] like Fig.45A and Fig.45B As shown, when the crystal grain size is large, even if cracks occur in the particles, the crack area can be suppressed to be small, thereby suppressing an increase in resistance or an increase in specific surface area in the particles.

[0753] <Particle Size Distribution>

[0754] Fig.46 The particle size distribution measurement results of the positive active materials corresponding to samples 5-1 to 5-6 are shown. In the particle size distribution measurement, a laser diffraction particle size distribution measuring device (SALD-2200 of Shimadzu Corporation, Japan) is used. First, about 0.4g of sample, surfactant and distilled water of 1mL or more and 2mL or less are added to the beaker, and ultrasonic treatment is performed to stir fully. Then, the solution is injected into the stirring water tank, and the photometric distribution is measured 64 times at intervals of 2 seconds to analyze the particle size distribution data. The particle size of samples 5-1, 5-2 and 5-3 with relatively low Li / Co is small and two peaks of particle size distribution are confirmed. The particle size of samples 5-4, 5-5 and 5-6 with relatively high Li / Co is large and the peak of particle size distribution is one. It can be seen that the higher the Li / Co ratio, the narrower the distribution width. In order to obtain a positive active material with consistent particle size and narrow distribution width, the higher the Li / Co ratio, the better, for example, samples 5-5 and 5-6 are preferably used.

[0755] The following table shows the corresponding Fig.46 D50 and D90 of samples 5-1 to 5-6. Furthermore, the ratio of D50 / D90 (%) is also recorded. According to the table below, the following tendency is confirmed: the higher the Li / Co ratio, the larger the D50 and D90. The ratio of D50 / D90 (%) is preferably 35% or more, and more preferably 40% or more.

[0756] [Table 7]

[0757] D50(μm) D90(μm) D50 / D90(%) Sample 5-1 25.1 72.8 34.5 Sample 5-2 30.7 78.3 39.2 Sample 5-3 20.7 69.9 29.6 Sample 5-4 16.0 42.5 37.6 Sample 5-5 24.6 43.1 57.1 Sample 5-6 35.3 80.9 43.6

[0758] <Manufacturing of positive electrode>

[0759] Prepare the above-mentioned samples 5-1 to 5-6 as positive electrode active materials, prepare acetylene black (AB) as a conductive material, and prepare polyvinylidene fluoride (PVDF) as a binder. Prepare PVDF that is dissolved in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Then, mix the positive electrode active material: AB: PVDF = 95:3:2 (weight ratio) to prepare a slurry, and apply the slurry to an aluminum current collector. NMP is used as a solvent for the slurry. After applying the slurry to the positive electrode current collector, the solvent is evaporated.

[0760] Then, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a roller press was used for pressing. Under the pressing conditions, the linear pressure was 210 kN / m. The upper and lower rollers of the roller press were both at 120°C. The loading of samples 5-1 to 5-6 was 7 mg / cm 2 about.

[0761] Through the above-mentioned process, positive electrodes including Sample 5-1 to Sample 5-6 were obtained.

[0762] <Manufacturing of test batteries>

[0763] A test cell (CR2032 coin cell, 20 mm in diameter, 3.2 mm in height) using lithium metal as a counter electrode was manufactured using the above positive electrode. A cell using lithium metal as a counter electrode is referred to as a half cell.

[0764] As the electrolyte of the half-cell, an organic electrolyte was prepared in which lithium hexafluorophosphate (LiPF6) was dissolved at 1 mol / L in a mixed organic solvent containing EC (ethylene carbonate) and DEC (diethyl carbonate) in a ratio of EC:DEC=30:70 (volume ratio). In addition, 2 wt% of VC was added to the organic electrolyte as an additive.

[0765] As the separator of the half-cell, a porous polypropylene film with a thickness of 25 μm was used.

[0766] The positive electrode can and the negative electrode can were housed to manufacture half-cells including samples 5-1 to 5-6. In order to clarify the correspondence with the positive electrode active material, the manufactured half-cells are referred to as samples 5-1 to 5-6. The positive electrode can and the negative electrode can were made of stainless steel (SUS).

[0767] <Charge and discharge cycle test>

[0768] As a charge and discharge tester, a charge and discharge evaluation system (TOSCAT-3100) manufactured by TOYO SYSTEM Co., Ltd. was used to measure the charge and discharge cycle test of a half cell. By using the charge and discharge cycle test of a half cell, the performance of a single positive electrode can be grasped.

[0769] The above-mentioned charge-discharge cycle test was performed on samples 5-1 to 5-6 at ambient temperatures of 25° C. and 45° C. The ambient temperature refers to the temperature of the thermostatic chamber in which the half-cells corresponding to each of samples 5-1 to 5-6 were placed, and the description of the environment is sometimes omitted below.

[0770] The charging conditions of each half-cell configured in the thermostatic chamber are as follows: constant current charging is performed at a rate of 0.5C (in this embodiment, it is set to 1C = 200mA / g (weight of positive electrode active material)) until the upper limit voltage reaches 4.6V, 4.65V or 4.7V, and then constant voltage charging is performed while maintaining the upper limit voltage until the current reaches 0.05C. Sometimes the charge and discharge cycle test conditions are recorded as CC / CV charging (each upper limit voltage, rate is 0.5C, and cutoff is 0.05C). The discharge conditions are as follows: constant current discharge is performed at a rate of 0.5C until the lower limit voltage reaches 2.5V. A sleep period is set between charging and discharging, and in this embodiment, the sleep period is set to 10 minutes.

[0771] Fig.47A The graph shows the change in discharge capacity with respect to the number of cycles at 25° C. and an upper limit voltage of 4.6 V. Fig.47B The graph shows the change in discharge capacity with respect to the number of cycles at 25° C. and an upper limit voltage of 4.65 V. Fig.47C The graph shows the change in discharge capacity with respect to the number of cycles at 25° C. and an upper limit voltage of 4.7 V. Note that the discharge capacity of the half-cell in this example was calculated as a value per unit weight of the positive electrode active material.

[0772] Fig.48A The graph shows the change in discharge capacity with respect to the number of cycles at 45° C. and an upper limit voltage of 4.6 V. Fig.48B The graph shows the change in discharge capacity with respect to the number of cycles at 45° C. and an upper limit voltage of 4.65 V. Fig.48C The graph shows the change in discharge capacity with respect to the number of cycles at 45° C. and an upper limit voltage of 4.7 V.

[0773] Fig.49A The graph shows the discharge capacity retention rate at 25° C. and an upper limit voltage of 4.6 V. Fig.49B The graph shows the discharge capacity retention rate at 25° C. and an upper limit voltage of 4.65 V. Fig.49C The graph shows the discharge capacity retention rate at 25° C. and an upper limit voltage of 4.7 V.

[0774] Fig.50A The graph shows the discharge capacity retention rate at 45° C. and an upper limit voltage of 4.6 V. Fig.50B The graph shows the discharge capacity retention rate at 45° C. and an upper limit voltage of 4.65 V. Fig.50C The graph shows the discharge capacity retention rate at 45° C. and an upper limit voltage of 4.7 V.

[0775] Since samples 5-1 to 5-6 are positive electrode active materials containing nickel, the initial capacity is large. It can be seen that in the charge and discharge cycle at 25°C and 45°C, the discharge capacity of samples 5-4, 5-5 and 5-6 is larger than that of samples 5-1, 5-2 and 5-3. It can be seen that at 25°C and 45°C, the discharge capacity retention rate of samples 5-4, 5-5 and 5-6 is higher than that of samples 5-1, 5-2 and 5-3. It can be seen that the higher the Li / Co ratio, the higher the discharge capacity and discharge capacity retention rate in the charge and discharge cycle.

[0776] <Rate Characteristics>

[0777] At an ambient temperature of 25°C, the discharge capacity of samples 5-1 to 5-6 was measured by fixing the charge rate at 0.5C until the voltage reached 4.6V, 4.65V or 4.7V and changing the discharge rate to 0.2C, 0.5C, 1C, 2C, 3C, 4C, 5C and 0.2C in sequence. This measurement is sometimes referred to as rate characteristics. In addition, the discharge capacity was measured twice for each rate.

[0778] Fig.51A The graph shows the rate characteristics when the upper limit voltage is 4.6 V, in which the rate characteristics are normalized with the initial values ​​of 0.5C / 0.2C. Fig.51B The graph shows the rate characteristics when the upper limit voltage is 4.65 V, in which the rate characteristics are normalized with the initial values ​​of 0.5C / 0.2C. Fig.51C The graph of rate characteristics when the upper limit voltage is 4.7V is shown, in which the initial 0.5C / 0.2C value is normalized. It can be seen that samples 5-1 to 5-6 have the same discharge capacity as the initial value even when the discharge rate is increased, and have excellent high-rate characteristics of 2C or more and 5C or less. In particular, it can be seen that the high-rate characteristics of samples 5-4 to 5-6 are better than those of samples 5-1 to 5-3.

[0779] Fig.52A The graph shows the rate characteristics when the upper limit voltage is 4.6 V, in which the energy density at the initial 0.5C / 0.2C is normalized. Fig.52B The graph shows the rate characteristics when the upper limit voltage is 4.65 V, in which the energy density at the initial 0.5C / 0.2C is normalized. Fig.52C The graph of rate characteristics when the upper limit voltage is 4.7V is shown, in which the energy density of the initial 0.5C / 0.2C is normalized. It can be seen that samples 1-1 to 1-6 have the same energy density as the initial level even if the rate during discharge is increased, and have excellent high-rate characteristics of more than 2C and less than 5C. In particular, it can be seen that the high-rate characteristics of samples 1-4 to 1-6 are better than those of samples 1-1 to 1-3.

[0780] In addition, as other samples, according to Figure 7 Step 33 shown, the precipitate was dried in a vacuum drying oven at 80 °C for 1 hour to prepare hydroxide 95 (Sample 6). In Sample 6, lithium hydroxide was prepared as the Figure 7 lithium source, and the molar ratio of lithium hydroxide to the precursor was set to 1.00, 1.03, 1.06, and 1.09. They are respectively referred to as Sample 6-1, Sample 6-2, Sample 6-3, and Sample 6-4. Conditions not described are the same as those of Sample 5-1, etc. The following table shows the Li / Co conditions of each sample.

[0781] [Table 8]

[0782] Li / Co (molar ratio) Sample 6-1 1.00 Sample 6-2 1.03 Sample 6-3 1.06 Sample 6-4 1.09

[0783] <SEM Image 3>

[0784] Fig.53 Planar SEM images corresponding to the precursors of Samples 6-1 to 6-4 are shown, and the Li / Co adjusted between these samples is different as shown in the above table. In addition, Fig.53 Planar SEM images corresponding to Samples 6-1 to 6-4 and of the composite oxide that has been heat-treated at 950 °C for 10 hours before the addition of the element source are also shown.

[0785] It can be confirmed that the particle sizes of Samples 6-1 to 6-4 are all slightly larger than those of the precursors. It is confirmed that: even when the Li / Co ratio is increased, there is no difference in particle size among Samples 6-1 to 6-4.

[0786] <SEM Image 4>

[0787] Fig.54 Planar SEM images corresponding to Samples 6-1 to 6-4 and of the composite oxide that has been heat-treated at 900 °C for 20 hours are shown. It can be confirmed that the particle sizes of Samples 6-1 to 6-4 are all larger than those of the Fig.53 precursors shown. In addition, it is confirmed that: among Samples 6-1 to 6-4, the particle surface is smoother than that of the Fig.53 precursors. The surface being smoother may be because the added element source contains fluorine. In addition, the surface being smoother may be because of the heat treatment.

[0788] <XRD Measurement>

[0789] Fig.55 Powder XRD measurement results of the cathode active materials corresponding to Samples 6-1 to 6-4 are shown. The XRD measurement conditions are the same as those of Sample 1.

[0790] The 2θ values ​​of the positive electrode active materials corresponding to samples 6-1 to 6-4 overlap with lithium cobalt oxide (LCO), thereby confirming that lithium cobalt oxide has been produced. In other words, the XRD spectrum or diffraction pattern overlap...

Claims

1. A method for producing a positive electrode active material, comprising the following steps: forming a mixed solution in which the cobalt compound and the nickel compound are dissolved; reacting the mixed solution with an alkaline aqueous solution to obtain a suspension of cobalt nickel hydroxide precipitation; Performing a first suction filtration on the suspension using water; and After the first suction filtration, a second suction filtration is performed using an organic solvent, in, In the cobalt nickel hydroxide, the atomic number ratio of the nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is 0.01 or less.

2. A method for producing a positive electrode active material, comprising the following steps: forming a mixed solution in which the cobalt compound and the nickel compound are dissolved; reacting the mixed solution with an alkaline aqueous solution to obtain a suspension of cobalt nickel hydroxide precipitation; Performing a first suction filtration on the suspension using water; After the first suction filtration, a second suction filtration is performed using an organic solvent to recover the cobalt nickel hydroxide; performing a first heat treatment after mixing the cobalt nickel hydroxide and the lithium compound to form a first composite oxide; and After mixing the first composite oxide and the compound containing the additional element, a second heat treatment is performed, in, In the cobalt nickel hydroxide, the atomic number ratio of the nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is less than or equal to 0.01, Furthermore, in the first composite oxide, the atomic number ratio of lithium to the atomic number ratio of cobalt is 1.0 or more and 1.2 or less.

3. The method for producing a positive electrode active material according to claim 2, The additional element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

4. The method for producing a positive electrode active material according to claim 2, The temperature of the second heating treatment is lower than the temperature of the first heating treatment.

5. The method for producing a positive electrode active material according to claim 1 or 2, The cobalt nickel hydroxide is subjected to a drying step for 0.5 hours to 20 hours.

6. The method for producing a positive electrode active material according to claim 1 or 2, The cobalt nickel hydroxide is subjected to a drying process for 12 hours to 20 hours.

7. A positive electrode active material, in, The atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is 0.01 or less, and the atomic number ratio of lithium relative to the atomic number ratio of cobalt is 1.0 or more and 1.2 or less, Furthermore, the positive electrode active material has a region where nickel is not confirmed in a mapping image of the positive electrode active material obtained by a surface SEM-EDX method.

8. A positive electrode active material, in, The atomic number ratio of nickel relative to the sum of the atomic number ratio of cobalt and the atomic number ratio of nickel is greater than 0 and is equal to or less than 0.1, and the atomic number ratio of lithium relative to the atomic number ratio of cobalt is equal to or greater than 1.0 and equal to or less than 1.2, The positive electrode active material includes crystal particles, Furthermore, the size of the crystal grains is greater than or equal to 200 nm and less than or equal to 600 nm.

9. The positive electrode active material according to claim 7 or 8, The atomic number ratio of lithium to the atomic number ratio of cobalt is 1.06 or more and 1.2 or less.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2006344509A

  • Positive electrode active material and method for producing positive electrode active material

    WO2020026078A1